Sterile insect technique for key agricultural pests in Africa: successes, challenges, and future opportunities - Michael M. Githae; Reyard Mutamiswa; Pascal O. Aigbedion-Atalor; Megan Mulcahy; Candice A. Coombes; Sean D. Moore; Martin P. Hill (Crop Protection, 2026)

A concentric fractured depression in Jori crater, Mars, and associated crater floor deformation reinterpreted as a meteor impact - Alan D. Howard; Anna Grau Galofre; Jeffrey M. Moore (Icarus, 2026)

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Differences in Siderophore Production During the Growth of Phytoplankton in Southern Ocean Incubation Experiments Under High‐ and Low‐Iron Conditions - Randelle M. Bundy; Kristen N. Buck; Bethany D. Jenkins; P. Dreux Chappell; Daniel J. Repeta; Alexa Sterling; Shannon M. Yang; Laura Holland; Léo Mahieu; Laura E. Moore (Environmental Microbiology, 2026)
Iron is an important micronutrient required by marine microorganisms. The Southern Ocean is an ecosystem where primary production is limited by the availability of iron, but how microorganisms in this region adapt to low‐iron conditions or respond to episodic iron inputs is understudied. We tested how external iron additions would impact bacterial production of siderophores during phytoplankton growth using shipboard incubation experiments under a range of iron conditions. Similar heterotrophic bacteria communities and phytoplankton biomass were observed whether iron was added from the continental margin or as inorganic iron. Under both high‐ and low‐iron conditions, the heterotrophic bacteria community remained the same but produced distinct iron‐binding siderophores. Siderophores were detected in the highest concentrations when phytoplankton and heterotrophic bacteria were iron‐limited, and unique compounds were produced in low‐iron conditions compared to when iron was added. Hydrophobic siderophores dominated when iron concentrations were low, and hydrophilic compounds when iron concentrations were higher, and this was likely due to environmental factors rather than changes in the microbial siderophore producers. Our results also highlight that phytoplankton growth likely played an important role in stimulating siderophore production across both low‐ and high‐iron conditions, with important implications for phytoplankton and bacteria interactions.

Comparing the behavioral impacts of different angling tournament formats on largemouth bass - Cory D. Suski; J.C. Moore; J.C. Glomb; J.L. Busby (Fisheries Research, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Proceedings from Nourish Now: A science dialogue on improving adolescent health through nutrition - Mario G. Ferruzzi; Regan L. Bailey; Teresa A. Davis; Heather J. Leidy; Jamie I. Baum; Jill Castle; Angela De Leon; Eva C. Diaz; Victor L. Fulgoni; Carolyn Gunther; Leslie Kaplan; Bracha Kopstick; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

Fentanyl decreases arterial blood oxygen saturation more than furanylfentanyl in mice due to increased apnea - Catherine Demery; Sierra C. Moore; Kelsey E. Kochan; Mengchu Li; Thomas D. Prince; Benjamin M. Clements; Zhongqi Chen; Jessica R. Whitaker-Fornek; Erica S. Levitt; Jessica P. Anand; John R. Traynor (Psychopharmacology, 2026)
Rationale Fatal opioid overdoses involving synthetic opioids have increased >10-fold over the past 8 years. Fentanyl, a potent synthetic opioid acting at the mu-opioid receptor (MOR), has largely replaced heroin as the predominant illicit opioid available. Various analogs have been synthesized from the fentanyl scaffold, including 2-furanylfentanyl, one of the most trafficked analogs from 2019 to 2024. Despite its prevalence, the in vivo effects of furanylfentanyl are not well characterized, especially regarding respiratory depression. Objectives To characterize furanylfentanyl relative to fentanyl in vitro and compare the effects of both drugs in mouse models of antinociception and respiratory depression. Methods The affinity and potency of fentanyl and furanylfentanyl were determined in CHO cells overexpressing MOR. Male and female CD-1 mice were administered ( i.p. ) fentanyl or furanylfentanyl prior to measuring antinociception (warm-water tail withdrawal), respiration (whole-body plethysmography), or oxygen saturation (pulse oximetry). Results Furanylfentanyl behaves as a partial agonist in vitro relative to fentanyl and morphine but with similar affinity and potency at MOR. In mice, fentanyl and furanylfentanyl produced similar effects on breathing parameters (including rate and inspiration time) that were greater than those induced by morphine, yet only fentanyl caused a drastic, long-lasting depletion of blood oxygen saturation. The discrepancy between effects on breathing and oxygen saturation may be explained by a greater number of apneas induced by fentanyl. Conclusions These results highlight the complexity of fentanyl-induced respiratory depression and indicate that recreational use of 2-furanylfentanyl in humans may pose a greater risk of overdose than morphine but lesser than fentanyl.

Biological nanopore technology: developments and implications for the agricultural sciences - Minji Kim; Bach Pham; Joshua C. Foster; Matthew D. Moore (Trends in Food Science & Technology, 2026)

Adaptation and Response in Drylands: A Dryland Research Agenda and Campaign Strategy - Andrew F. Feldman; Sasha C. Reed; Konrad Wessels; Dennis Ojima; David J. P. Moore; William K. Smith; Niall P. Hanan; Cibele Amaral; Flurin Babst; Joel A. Biederman; Marcy Litvak; Natasha MacBean; et al. (Global Change Biology, 2026)
Dryland ecosystems cover 41% of Earth's land surfaces, account for 44% of cultivated lands and 60% of food sources, and make large contributions to the global water and carbon cycles. However, these ecosystems are experiencing unprecedented extremes including heatwaves, floods, and droughts as well as hotter temperatures and often declining water resource availability. These ecosystems are some of the most challenging to monitor given their high temporal variability with rapid response to their environment as well as vast spatial variability with intermixing of different plant species and life forms amongst bare soil coverage. The Adaptation and Response in Drylands (ARID) campaign was selected by National Aeronautics and Space Administration (NASA) as a scoping study to develop a research agenda for a dryland field campaign. Here, we detail our ARID science research agenda and implementation plan that were developed based on an extensive community engagement effort in over 160 events with over a thousand scientists, land managers, and Tribal communities between 2023 and 2024. The selected science themes cover drought and climate variability, ecosystem structure, function, and biodiversity, carbon cycle interannual variability and trends, and social ecological systems (land management and adaptation). We then detail our remote sensing, modeling, and field‐based strategies to capture high temporal and high spatial resolution processes. Finally, our implementation strategy is presented which includes focus area selections in a core intensive western U.S. domain and distributed international domains. This strategy includes our overarching guiding principles of using multi‐temporal airborne acquisitions and super sites as well as enhancing land management in co‐development with end‐user partners. While originally developed for NASA, our ARID report creates a blueprint for any future dryland field campaign, at any scale, that can be implemented widely for foundational and applied science objectives.

Into the Wild: Farm‐Derived Energy and Nutrients Enter Marine Food Webs With Carrying Capacity Implications for Aquaculture Management - Myriam D. Callier; Ramon Filgueira; Carrie J. Byron; Daniele Brigolin; Dror L. Angel; Sophie J. I. Koch; Bobbi Hudson; Frank Kane; Heather Moore; Antonio Agüera; Lotta C. Kluger; Christopher W. McKindsey (Reviews in Aquaculture, 2026)
Marine aquaculture is expanding globally, yet its interactions with surrounding ecosystems remain complex and insufficiently understood. This study reviews the fluxes of energy and nutrients from three major aquaculture systems: finfish cages, suspended bivalves, and seaweed farms and considers their implications for ecosystem functioning and management under the ecosystem approach to aquaculture (EAA). Using a focused literature review and expert input from International Council for the Exploration of the Sea (ICES), Working Group on Ecological Carrying Capacity of Aquaculture (ICES WGECCA), we synthesized data on farm‐derived fluxes, trophic transfers, and ecological consequences. From this synthesis, we developed three conceptual models illustrating direct and indirect pathways of energy and nutrient exchange between farms and marine food webs. Seven case studies from temperate and subtropical systems were analyzed to exemplify site‐specific effects, including organic enrichment, altered benthic‐pelagic coupling, and changes in wild species assemblages. Key findings highlight that fed aquaculture (finfish) releases substantial particulate and dissolved waste, influencing benthic geochemistry, while extractive systems (bivalves, seaweeds) modulate nutrient cycling. Integrated multi‐trophic aquaculture (IMTA) offers the potential for synergistic flux recycling within the farm system. Wild mobile fauna attracted to farm systems shelter and feed directly on the farmed product, fouling, or particulate wastes and dislodgements from the farm, thereby strengthening farm‐environment coupling. These insights underscore the need for adaptive management and carrying capacity (CC) assessments that account for energy‐nutrient fluxes to ensure sustainable aquaculture development aligned with EAA principles.

Unstable bridges—exploring the possibilities for “in between” spaces amidst divergent narratives in environmental governance - Blanca González-Mon; Violeta Cabello; Amanda Jiménez-Aceituno; María Mancilla García; Antonio J. Castro; María D. López-Rodríguez; Michele-Lee Moore; Maja Schlüter (Sustainability Science, 2026)
Social-ecological systems increasingly face polarization dynamics that challenge environmental governance. Such polarization implies the development of opposing narratives with limited interaction, each framing environmental problems and solutions in distinct ways. In this study, we analyze a case of narrative polarization around the eutrophication crises of the Mar Menor lagoon in Spain, focusing on how proposed solutions are narrated to address this complex environmental puzzle. We use a mixed-method approach that combines social network analysis and an analysis of narrative practices in interview situations, to investigate whether and how potential solutions to eutrophication in the Mar Menor can be understood as bridging spaces that create opportunities for interaction between divergent societal narratives. Our three-step analysis includes: (a) a network analysis of reports proposing solutions to identify solutions with a bridging role (i.e., those linking reports that otherwise have little overlap in the solutions proposed); (b) a thematic narrative analysis to investigate the solutions proposed by diverse actors; and (c) an analysis of narrative practices around selected bridging solutions to explore if they constitute new spaces where narratives can interact and confront positions - what we call bridging spaces. We suggest this mixed methods approach allows for the identification of potential bridging spaces to mediate polarization and outline directions for future research on both the case study specifically, and on polarization in environmental governance more generally.

Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

Access to Phones and Use of International Numbers Among Farmworkers in North Carolina, 2023–2024 - Abdul G. Zahra; Leslie E. Cofie; Catherine E. LePrevost; Tania Connaughton-Espino; Natalie D. Rivera; Lilibeth A. Benitez; Modjulie A. Moore; Mary Roby; Joseph G. L. Lee (Journal of Agromedicine, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Chronic exposure to waterborne nickel significantly reduced growth of juvenile crayfish (Faxonius virilis) - Adrian P. Moore; Mark L. Wildhaber; Zachary D. Beaman; Kendell R. Bennett; Karlie K. Ditter; Danielle Cleveland; Jenna A. Blanton; Tyler J. Grant (Ecotoxicology, 2026)

Ti solubility in biotite at low pressure in metapelitic systems: the Torres del Paine case - Maria M. Ariza-Acero; Lukas P. Baumgartner; C. Tom Foster; Marisa D. Acosta; Jo Moore; Jack Gillespie; Robert Bodner; Guillaume Siron (Contributions to Mineralogy and Petrology, 2026)
The Torres del Paine Intrusive Complex (TPIC) is a shallowly emplaced pluton surrounded by a well-defined contact aureole, providing an ideal setting to test Ti-in-biotite thermometry. We compare existing Ti-in-biotite thermometers with phase petrology constraints and found that they systematically overestimate peak metamorphic temperatures. This discrepancy arises from a significant increase in Ti solubility at low pressures $$(<1$$ kbar). In fact, we demonstrate that a pressure difference of $$\sim 0.25$$ kbar within the aureole leads to an increase of 0.1 a.p.f.u. in Ti content, suggesting that pressure plays a key role in Ti incorporation at these low pressures. At lower pressures, the Ti-oxy substitution becomes saturated, and Ti incorporation is dominated by a Ti-spinel exchange mechanism. Additionally, textural and chemical analyses reveal that composition vary between small domains of a few hundred micrometers, indicating that local compositional heterogeneities significantly influences Ti content in biotite, even when a Ti-oxide and an Al-rich silicate are nearby. Finally, biotite starts growing near to the biotite-in isograd, and keeps on growing, so that its composition does not fully adjust to the peak composition due to the short metamorphic event. These findings highlight that both pressure and temperature influence the Ti content in biotite. The application of Ti-in-biotite thermometry requires careful consideration of equilibrium domains and growth kinetics.

A cross-cohort comparison of the prevalence and clinical significance of Alzheimer’s disease biomarkers in people with versus without HIV - Lillian Ham; Olivia Villers; Judith D. Lobo; Tyler R. Bell; Debralee Cookson; Douglas Galasko; Scott L. Letendre; Mark W. Bondi; David J. Moore; Erin E. Sundermann (Journal of NeuroVirology, 2026)
With over half of people with HIV (PWH) in the U.S. entering older adulthood, identifying markers to distinguish Alzheimer’s disease (AD) and its precursor, amnestic mild cognitive impairment (aMCI), from other forms of neurocognitive impairment among PWH is urgent. We examined how HIV and aMCI status relate to AD CSF biomarkers in adult PWH and people without HIV (PWoH) characterized for aMCI. We included 80 PWH from the National NeuroHIV Tissue Consortium and 80 PWoH from the Wisconsin Registry for Alzheimer’s Prevention. Binary logistic regressions of AD-related CSF biomarker positivity (Aβ 42, Aβ 42 /Aβ 40, t-tau, p-tau 181 , Aβ 42 /t-tau) were conducted with HIV serostatus, aMCI status, HIV x aMCI interaction, and demographic covariates. Among PWH, we examined how HIV-disease characteristics relate to AD biomarker positivity. No HIV x aMCI interactions were detected. Regardless of aMCI status, having HIV was associated with higher odds of CSF Aβ 42 (OR = 7.97) and Aβ 42 /Aβ 40 (OR = 6.06) positivity, suggesting increased cerebral Aβ plaque burden. Regardless of HIV serostatus, having aMCI was associated with higher odds of CSF p-tau 181 positivity (OR = 3.64). Neither HIV nor aMCI status related to Aβ 42 /t-tau positivity. No HIV-disease characteristics related to AD biomarker positivity. Higher CSF Aβ positivity in PWH versus PWoH, regardless of aMCI status, suggests that HIV disease promotes amyloidosis; however, whether positive CSF biomarkers in PWH raises risk for future cognitive impairment and AD remains to be explored longitudinally. Like PWoH, elevated CSF p-tau 181 among PWH may indicate increased risk for AD-related memory impairment.

Consumers show flexible refuge use but more rigid foraging under plant invasion - Nathalie R. Sommer; Catherine B. Moore; Oswald J. Schmitz; Julia D. Monk (Biological Invasions, 2026)

Success of restoration strategies in preventing extirpation of 2 critically endangered coral species - Erinn M. Muller; Mark C. Ladd; Richard Karp; Phanor H. Montoya‐Maya; Ilsa B. Kuffner; Andrew C. Baker; Erich Bartels; Amanda Bourque; Abigail S. Clark; Nikkie Cox; Martine D'Alessandro; Ben Daughtry; et al. (Conservation Biology, 2026)
An unprecedented marine heatwave in 2023 caused widespread coral bleaching and mortality throughout the Caribbean. In the Florida Keys (USA), 2 foundation species, elkhorn coral ( Acropora palmata ) and staghorn coral ( Acropora cervicornis ), were severely affected. These species have been the primary focus of reef restoration in Florida for decades. Substantial losses of these species occurred in outplanted populations, in ocean‐based nurseries, and among remnant wild colonies, leading to uncertainty over their future in the Florida Keys, given recent observed trends in climate conditions. However, the past 2 decades of restoration activity created a community of experts, a network of ocean‐based and land‐based coral‐rearing infrastructure, and 2 independent land‐based coral gene banks that prevented regional extirpation and preserved much of the genetic richness of these critically endangered coral species. Without the past decades of effort and the emergency response associated with the 2023 bleaching event, Florida acroporids would largely have been lost. This outcome afforded by the restoration network in Florida demonstrates the value of proactively establishing resources prior to major disturbances. We identified several critical strategies that, in the context of existing climate change, are preventing the extirpation of coral species in Florida, including extending collaborative restoration efforts to solidify a network of trained experts; establishing trust‐focused relationships among management agencies and restoration groups; testing direct interventions to reduce light and temperature stress early during thermal anomalies; developing redundant ocean‐based and land‐based nurseries; and establishing living coral gene banks prior to major threats to prevent the extirpation of coral species.

Informing spatial conservation prioritization with species’ traits - Liam A. Trethowan; Laura Jennings; Haerul Arifin; Renata Borosova; Gemma L. C. Bramley; Marie Briggs; Osanna Chu; Ruth P. Clark; Sally Dawson; Kiran L. Dhanjal‐Adams; Yance de Freitas; James Hartup; et al. (Conservation Biology, 2026)
New Guinea, the most botanically diverse island on the planet, is the location for one of the boldest conservation initiatives. The Manokwari Declaration aims to achieve 70% conservation designation for the Bird's Head Peninsula. This is 40% higher than the 2022 Global Biodiversity Framework target. However, there is a lack of species occurrence data to support evidence of where biodiversity can be best protected. To address this, we integrated plant trait data from taxonomic descriptions in species occurrence models that can inform conservation planning. Inclusion of traits improved the performance of co‐occurrence models of ∼800 plant species across the 100,000‐km 2 landscape. Traits generally improved model performance, but not all traits contributed equally (e.g., leaf size and red flower color most improved accuracy of occurrence prediction). Likewise, trait‐parameterized models tended to be most useful with rare species occurrence prediction, but this was inconsistent among traits. Under 70% protection, three‐quarters of the areas selected conserved trait diversity. Critically, trait diversity also increased the chances that areas at high risk of deforestation were selected as conservation priorities. Overall, we found that plant species’ traits, often key parameters of ecosystem function and resilience, improved spatial conservation planning.

Food Substitution and Waste Reduction Can Reduce the Environmental Impacts and Food Costs of School Meal Programs in the United States: An 2011-2018 NHANES Analysis - David C. Love; Zach Conrad; Daphene Altema-Johnson; Rebecca Ramsing; Karen Bassarab; Andrew L. Thorne-Lyman; D’Ann L. Williams; E.R.H. Moore; Elizabeth M. Nussbaumer; Patti Truant Anderson (Journal of the Academy of Nutrition and Dietetics, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Linking stand age and straw management to carbon stocks and microbial communities in tall fescue seed fields - Martina Gonzalez Mateu; Amber D. Moore; Nicole Anderson; Elizabeth Verhoeven; Jennifer M. Moore; Kristin M. Trippe (Plant and Soil, 2026)
Background and aims Perennial grass seed systems may promote soil organic carbon (SOC) storage through continuous plant cover, reduced tillage, and straw residue retention, yet few studies have explored the effects of field management practices on SOC stocks. Methods We measured SOC stocks (0–30 and 30–100 cm depth), particulate and mineral-associated organic carbon (POM and MAOM), microbial community structure, and plant biomass across 24 tall fescue seed fields of varying stand ages (2–20 years) and straw management practices (straw retention vs removal) in Oregon, USA. Results While SOC stocks did not differ among treatments at either depth, stand age and straw retention altered plant and biomass, and SOC partitioning. Specifically, older stands exhibited higher total field-level C (SOC + plant biomass) due to greater root inputs, while straw retention increased the proportion of POM in the topsoil. Together, stand age and straw retention shifted community composition and increased microbial biomass. Total PLFAs were positively correlated with %POM and soil respiration, indicating that straw retention can drive rapid C turnover. When compared to nearby land uses, tall fescue seed fields had lower topsoil C stocks than natural grasslands but higher than arable crops, underscoring the C storage potential of these systems. Conclusions Our results indicate that stand age and straw management altered SOC dynamics primarily through changes in microbial biomass and labile SOC inputs. Maintaining older perennial stands with straw retention can support higher belowground inputs and foster a larger microbial community, potentially enhancing aspects of soil health beyond SOC accumulation.

Identification of Dolly Varden (Salvelinus malma) in the Canadian Arctic east of the Mackenzie River - Spencer Y. Weinstein; Amanda Dumond; Tracey N. Loewen; James D. Reist; Matthew C. Hale; Colin P. Gallagher; Jean-Sébastien Moore; Les N. Harris; Ross F. Tallman; Robert Bajno; Zoya A. Martin; Paul M. Craig; et al. (Environmental Biology of Fishes, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Signal characteristics of potential airbursts in Titan’s atmosphere - Elisa Dong; Catherine D. Neish; John E. Moores; Shigeru Wakita; Gareth S. Collins; Peter G. Brown; Ralph D. Lorenz; Benjamin Fernando; Mark P. Panning (Icarus, 2026)

Hillslope-induced environmental gradients regulate potential soil respiration in temperate peatlands - Yanfei Li; Pengzhi Zhao; Maud Henrion; Patrick Gerin; Matthieu Leclercq; Angus Moore; Eléonore du bois d'Aische; Sébastien Lambot; Sophie Opfergelt; Veerle Vanacker; François Jonard; Kristof Van Oost (CATENA, 2026)

Volatilized Metabolites Produced by Soilborne Aspergillus flavus Regulate Fungal Conidiation, and Production of Secondary Metabolites - Lina Castano-Duque; Imtiaz Ahmad; Steven W. Lloyd; Matthew D. Lebar; Carol Carter-Wientjes; Nathaniel B. McCartney; Jared G. Ali; Geromy G. Moore (Journal of Chemical Ecology, 2026)
Corn plants are susceptible to infection by fungi such as Aspergillus flavus that have the potential to produce several types of mycotoxins, one of the most potent ones known to exist is aflatoxin. Since aflatoxin contaminated corn must be destroyed, causing annual monetary losses in billions of dollars, it would be helpful to detect the presence of aflatoxin producing fungi at pre-harvest and pre-planting stages. To this end, it may be possible to capture volatile organic compounds these fungi produce while overwintering in the soil or while infecting corn plants. In this study, we acquired A. flavus VOCs from conidia and sclerotia, while residing in the soil environment. We concluded that soilborne conidia and sclerotia have specific VOC signatures, and sclerotia tend to emit specific VOCs at greater abundance compared to soilborne conidia or fungus-free soil. These sclerotium-specific VOCs include geranyl acetone, caryophyllene compounds, and methanone. Bioassays using toxin producing and non-producing fungi showed that β-caryophyllene increased spore concentration, and both β-caryophyllene and caryophyllene oxide were able to modulate aerial hyphae, sclerotia production and decrease aflatoxin, cyclopiazonic acid and ditryptophenaline production in A. flavus strains. Our results show insights into the ecological roles that β-caryophyllene and caryophyllene oxide have over A. flavus’ development and metabolism, although their effect on multitrophic interactions among corn, fungi and other potential organisms are still not fully understood. These VOCs could serve as an agricultural surveillance management system that enables early mitigation of aflatoxin producing fungi outbreaks in the field.

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Meal Preparation Strategies and Lack of Food Security Among Unaccompanied Latino Migrant Farmworker Youth in Georgia and Florida: A Mixed-Methods Approach - Fiorella L. Carlos Chavez; Kaleea R. Lewis; Bethany A. Moore; Tracy Tang; Edward D. Vargas; Joan M. Hermsen; Rebecca E. Lee; Youngbin Lee; Irma A. Arteaga; Khushi Bypan; J. Sanford Rikoon; Thomas A. Arcury (Journal of Agromedicine, 2026)

A statistical representation of oil spill fate in the Salish Sea (Part 1) - Rachael D. Mueller; Susan E. Allen; Stephanie Chang; Haibo Niu; Douglas J. Latornell; Shihan Li; Ryah Bagshaw; Ashutosh Bhudia; Vicky Do; Krista Forysinski; Ben Moore-Maley; Cameron Power (Marine Pollution Bulletin, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Evaluation of proinsulin(F25D) as a targeting ligand for insulin-binding B cells in autoimmune diabetes - Kyle D. Apley; Lindsay E. Bass; Jaylyn King; Grant Downes; Kristen Wang; Mason V. Forchetti; Daniel J. Moore; Peggy Kendall; Rachel H. Bonami; Cory J. Berkland (Drug Delivery and Translational Research, 2026)

Biomechanical Analysis of the Effects of Knee Savers on Knee Joint Loading During High Knee-Flexion Tasks - Liying Zheng; John Z. Wu; Kevin D. Moore; Ashley L. Hawke; Robert E. Carey; Christopher M. Warren; Scott P. Breloff (Annals of Biomedical Engineering, 2026)

Spatiotemporal Patterns and Drivers of Fish Biodiversity on a Remote Freshwater Archipelago - David J. Gallagher; Mark C. Romanski; Jay D. Glase; Seth A. Moore; Courtney E. Larson; Donn K. Branstrator; Thomas R. Hrabik (Journal of Biogeography, 2026)
Aim Fish communities are shaped by environmental filters operating across different spatiotemporal scales. While many recent studies focus on anthropogenic gradients, few can isolate the role of natural drivers in community assembly. Isle Royale's inland lakes offer a rare opportunity to explore long‐term fish biodiversity dynamics with minimal confounding influences. We analysed fish communities in 23 lakes surveyed in the 1920s, 1990s, and 2020s to 1) assess temporal changes in richness and composition 2) identify lakes and species experiencing the greatest change, and 3) evaluate environmental drivers of community structure. Location Isle Royale National Park, USA. Taxon Freshwater fish. Methods We analysed historical and contemporary fish survey data using species‐area curves, PERMANOVA, and multivariate dispersion tests to quantify changes in richness and composition, temporal beta diversity indices and similarity percentages (SIMPER) to identify lakes and species changing most, and non‐metric multidimensional scaling (NMDS) to examine relationships with environmental factors. Results Mean richness and species‐area curve slopes declined slightly but non‐significantly over time. Community composition remained largely stable with no homogenization, although subtle shifts from cold‐water to cool‐water species were observed in larger lakes. Species gains and losses were associated with isostatic rebound rate. Fast‐rebounding lakes tended to gain species, while slower‐rebounding lakes tended to lose species. Richness and predator presence were structured along lake area and elevation gradients, respectively. Main Conclusions Fish biodiversity of Isle Royale's lakes has remained remarkably stable over the past century, reflecting minimal anthropogenic influence. Subtle shifts suggest continuous filtering by geological and environmental processes, however, and spatial gradients in composition highlight interactions between large‐ and small‐scale filters. This study provides a valuable baseline reference for understanding the processes of community assembly and environmental change in more impacted ecosystems.

A statistical representation of oil spill fate in the Salish Sea (Part 2) - Rachael D. Mueller; Susan E. Allen; Stephanie Chang; Haibo Niu; Douglas J. Latornell; Shihan Li; Ryah Bagshaw; Ashutosh Bhudia; Vicky Do; Krista Forysinski; Ben Moore-Maley; Cameron Power (Marine Pollution Bulletin, 2025)

The slow rejection of mercury in Yukon’s small-scale gold mining industry - C.L. Johnson; K.R. Moore; D. Johnson (The Extractive Industries and Society, 2025)

Environmental drivers of foraging by deep-diving cetaceans: Roles of mesoscale oceanography and light-driven cycles - Thomas A. Clay; Gemma Carroll; Megan A. Cimino; Jennifer L. Miksis-Olds; Katie A. Kowarski; Anthony P. Lyons; Peter I. Miller; Timothy S. Moore; Joseph D. Warren; Elliott L. Hazen (Progress in Oceanography, 2025)

The effects of cadmium and high fructose diet on metabolic and reproductive health in female CD-1 mice - Victoria R. Adams; Janice A. Dye; Micheal G. Narotsky; Makala L. Moore; Helen H. Nguyen; Aubrey L. Sasser; Kaberi P. Das; Lillian F. Strader; Joseph P. Pancras; Donna Hill; Chloe Davis; Wanda C. Williams; et al. (Food and Chemical Toxicology, 2025)

Evolution of the Narooma Accretionary Complex, southeastern Australia: structure and regional significance - C. J. L. Wilson; D. H. Moore (Australian Journal of Earth Sciences, 2025)

BMP9 knockout impairs pulmonary vessel muscularisation and confers aberrant tamoxifen sensitivity - Benjamin J. Dunmore; Stephen Moore; Rowena J. Jones; Joshua Hodgson; Kathryn Auckland; Mark Southwood; Nichola Figg; Nobuhiro Kikuchi; Martin Bennett; Allan Lawrie; Christopher J. Rhodes; Mark R. Toshner; et al. (Angiogenesis, 2025)
Deleterious mutations in the GDF2 gene, encoding BMP9, are causative of pulmonary arterial hypertension and hereditary haemorrhagic telangiectasia. Paradoxically, BMP9 germ-line knockout ( Gdf2 −/− ; Bmp9 KO) and double Bmp9 KO / conditional Bmp10 cKO (dKO) mice exhibit an attenuated response to PAH-inducing stimuli. We asked whether this contradiction is due to the pathological, physiological, or genetic consequences of BMP9 knockout. In Bmp9 KO mice we observed reduced pulmonary vascular smooth muscle cell (SMC) coverage and using RNA-seq analysis of Bmp9 KO mouse lungs identified two novel genes, COLQ and ITGA6 , which were differentially regulated in a human PAH RNA-seq dataset. In order to study BMP10 loss, postnatal tamoxifen treatment was required to induce Bmp10 cKO. As previously reported, in dKO mice we observed cardiomegaly and splenomegaly, as well as hyperplasia and hemosiderosis in the pulmonary vasculature. Surprisingly, tamoxifen treated Bmp9 KO control mice phenocopied these pathological changes in dKO mice and downregulated SMC marker gene transcription. Loss of BMP10 is not critical for severe tissue remodelling in the lung, heart, and spleen, rather Bmp9 KO mice appear sensitive to tamoxifen and BMP9 loss is the primary cause of mild vessel remodelling due to a basal reduction of smooth muscle cell coverage. This study suggests that interaction of the BMP pathway with tamoxifen needs to be carefully considered when studying Bmp9 KO mice and urges caution in the context of tamoxifen use when studying cardiovascular and pulmonary disease models.

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

A CNN Autoencoder for Learning Latent Disc Geometry from Segmented Lumbar Spine MRI - Mattia Perrone; D’Mar M. Moore; Daisuke Ukeba; John T. Martin (Annals of Biomedical Engineering, 2025)

Serum Biomarkers in Atlantic Salmon for Differential Diagnosis of Cardiomyopathy Syndrome and Pancreas Disease: Proteomic Identification of Serum Fibrinogen to Enhance Troponin Immunoassay as Optimal Diagnostic Approach - Francesca Riva; Lauren Elaine Black; Kim D. Thompson; Philippe Sourd; Andrei Bordeianu; Christopher C. Chadwick; Hooman Moghadam; Jorge Del‐Pozo; Janina Costa; Richard Burchmore; Nicola Brady; Lewis Moore; et al. (Journal of Fish Diseases, 2025)
Cardiac viral diseases are among the major causes of economic losses in Atlantic salmon ( Salmo salar L.) aquaculture. These include cardiomyopathy syndrome (CMS) caused by piscine myocarditis virus (PMCV) and pancreas disease (PD) caused by Atlantic salmonid alphavirus (SAV). The resulting cardiomyopathies impact fish stock in terms of mortality, quality, growth performance and economic loss. Diagnosis of these diseases is currently based on clinical signs, histopathology and RT‐qPCR. To identify putative biomarkers for use in the health assessment of Atlantic salmon, a quantitative proteomics investigation was undertaken with the aim of differentiating fish with CMS from healthy fish and fish with PD. Serum samples ( n = 9/group) were collected during health assessment from pens where clinical CMS or PD were present and compared to serum from healthy Atlantic salmon. There were 34 differentially abundant proteins (DAPs) in CMS compared to healthy, 66 comparing CMS to PD, and 81 comparing PD to healthy. In relation to healthy samples, most DAPs were shared between CMS and PD, with higher relative abundances observed in PD. An exception to this was serum fibrinogen, which was identified as a putative biomarker for CMS, whereas differentiation of Atlantic salmon with CMS from those with PD was enhanced by the calculation of the ratio of fibrinogen to skeletal troponin C.

The sicker sex is plastic: Thermal plasticity determines sex biases in pathogen transmission - Nathan J. Butterworth; Jared Lush; Kerri J. Moore; Matthew D. Hall (Ecology, 2025)
Sex differences are predicted to play an important role in the spread and evolution of pathogens. However, attempts to generalize the “sicker” sex have been challenged by intraspecific variability of sex biases across the infection process. Sex‐specific plasticity provides a framework to resolve this by elucidating how infection is shaped at the sex‐pathogen‐environment interface. Using the Daphnia magna and Pasteuria ramosa system, we measure infection outcomes for males and females across three temperatures and seven pathogen densities to quantify how sex‐specific plasticity shapes susceptibility, pathogen loads, and ultimately transmission. We find unique forms of plasticity at each stage of infection – including equivalent, sex‐specific, and divergent plasticity. Integrating these into a single estimate of transmission reveals a clear pattern—male‐biased transmission at cold temperatures, and female‐biased transmission at warm temperatures. Sex‐specific thermal plasticity can thus determine the “sicker” sex, with implications for pathogen spread and evolution in a warming world.

Temporal cluster of feline tuberculosis in the UK caused by Mycobacterium caprae, Associated with raw meat-based diet consumption - A. Schlachter; E. Bruno-McClung; C. Pritchard; J. Wheeler; I. Miteva; C. O'Halloran; R. Ellis; D. Jorge; D. Gunn-Moore; R. Rua-Domenech; A. Nunez (Journal of Comparative Pathology, 2025)

Understanding the motivations of small-scale miners in Yukon, Canada through a human-nature connection (HNC) framework and meaningful rural work - C.L. Johnson; K.R Moore; D Johnson (The Extractive Industries and Society, 2025)

Connections between roots and soil health across agriculture management practices - E. Britt Moore; Mriganka De; Marcio R. Nunes; Debasish Saha; Virginia Jin; Lidong Li; Jane M. F. Johnson; Douglas L. Karlen; Marshall D. McDaniel (Plant and Soil, 2025)

Dual-strain detection of norovirus GI.1 and GII.4 in food samples using epitope-imprinted polymers - Amy Dann; Pankaj Singla; Jake McClements; Minji Kim; Sloane Stoufer; Robert D. Crapnell; Craig E. Banks; Shayan Seyedin; Mark Geoghegan; Christopher F. Blanford; Matthew D. Moore; Marloes Peeters (Analytica Chimica Acta, 2025)

Enhancement of 3-hydroxyvalerate fraction in poly(3-hydroxybutyrate-co-3-hydroxyvalerate) produced by Haloferax mediterranei fed with food waste pretreated via arrested anaerobic digestion integrated with microbial electrolysis cells - Xueyao Zhang; Naresh Kumar Amradi; Martin Moore; Amro Hassanein; Rebecca L. Mickol; Emily L. McCoy; Brian J. Eddie; Jamia S. Shepard; Jiefu Wang; Stephanie Lansing; Matthew D. Yates; Young-Teck Kim; et al. (Bioresource Technology, 2025)

Optimizing automated photo identification for population assessments - Philip T. Patton; Krishna Pacifici; Robin W. Baird; Erin M. Oleson; Jason B. Allen; Erin Ashe; Aline Athayde; Charla J. Basran; Elsa Cabrera; John Calambokidis; Júlio Cardoso; Emma L. Carroll; et al. (Conservation Biology, 2025)
Several legal acts mandate that management agencies regularly assess biological populations. For species with distinct markings, these assessments can be conducted noninvasively via capture‐recapture and photographic identification (photo‐ID), which involves processing considerable quantities of photographic data. To ease this burden, agencies increasingly rely on automated identification (ID) algorithms. Identification algorithms present agencies with an opportunity—reducing the cost of population assessments—and a challenge—propagating misidentifications into abundance estimates at a large scale. We explored several strategies for generating capture histories with an ID algorithm, evaluating trade‐offs between labor costs and estimation error in a hypothetical population assessment. To that end, we conducted a simulation study informed by 39 photo‐ID datasets representing 24 cetacean species. We fed the results into a custom optimization tool to discern the optimal strategy for each dataset. Our strategies included choosing between truly and partially automated photo‐ID and, in the case of the latter, choosing the number of suggested matches to inspect. True automation was optimal for datasets for which the algorithm identified individuals well. As identification performance declined, the optimization recommended that users inspect more suggested matches from the ID algorithm, particularly for small datasets. False negatives (i.e., individual was resighted but erroneously marked as a first capture) strongly predicted estimation error. A 2% increase in the false negative rate translated to a 5% increase in the relative bias in abundance estimates. Our framework can be used to estimate expected error of the abundance estimate, project labor effort, and find the optimal strategy for a dataset and algorithm. We recommend estimating a strategy's false negative rate before implementing the strategy in a population assessment. Our framework provides organizations with insights into the conservation benefits and consequences of automation as conservation enters a new era of artificial intelligence for population assessments.

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Marine Mammal Stranding Networks in the 21st Century: Whence and Whither? - Frances M. D. Gulland; Regina Asmutis‐Silvia; Jeff Boehm; Robert A. DiGiovanni; Caroline E. C. Goertz; Jessica L. Huggins; Gretchen N. Lovewell; Kathleen M. Moore; Kristi West (Marine Mammal Science, 2025)

Nutrient limitation dampens the response of a harmful algae to a marine heatwave in an upwelling system - Alexis D. Fischer; Emilie Houliez; Brian D. Bill; Maria T. Kavanaugh; Simone R. Alin; Andrew U. Collins; Raphael M. Kudela; Stephanie K. Moore (Limnology and Oceanography, 2025)
Harmful algal blooms caused by toxin‐producing species of the diatom genus Pseudo‐nitzschia have been linked to anomalously warm ocean conditions in the Northern California Current System. This study compares summertime concentrations of Pseudo‐nitzschia spp. and the toxin they produce, domoic acid, during a marine heatwave year (2019) and a climatologically neutral year (2021). An Imaging FlowCytobot was installed on a fishery survey vessel alongside environmental sensors to continuously sample phytoplankton and oceanographic parameters. This was paired with targeted manual sample collections for nutrients, chlorophyll, and domoic acid. Accumulations of Pseudo‐nitzschia spp. were associated with upwelling zones and established hotspot regions: the Juan de Fuca Eddy, Heceta Bank, and Trinidad Head. Overall, however, Pseudo‐nitzschia spp. and domoic acid concentrations were low during both summers and appear to have been limited by nitrate. Nutrient availability may therefore modulate the response of Pseudo‐nitzschia spp. to warm anomalies. Comparison of these results with 2015, another marine heatwave year but one that produced record concentrations of Pseudo‐nitzschia spp. and domoic acid, suggests that the timing of marine heatwave conditions in the nearshore relative to seasonal upwelling plays a key role in determining whether a Pseudo‐nitzschia spp. harmful algal bloom will occur.

The Seaward Migration of European Eel at a Continental Scale: A Europe‐Wide Biotelemetry Meta‐Analysis - Pieterjan Verhelst; David Righton; Kim Aarestrup; Pedro R. Almeida; Tea Bašić; Jonathan D. Bolland; Liam Carter; Johan Coeck; José Lino Costa; Justas Dainys; Jan Grimsrud Davidsen; Isabel Domingos; et al. (Fish and Fisheries, 2025)
The European eel ( Anguilla anguilla L.) has a catadromous life cycle, with a single panmictic population that colonises continental Europe and northern Africa yet migrates 5000 to 9000 km to spawn in the Atlantic Ocean. It is unknown how this continental migration is organised so individual eels arrive in time for spawning with conspecifics. This meta‐analysis combined tracking data from 18 water bodies in freshwater and transitional systems distributed along the southwest‐northeast axis of Europe, resulting in a dataset of 2306 eels, making it the most comprehensive in terms of geographical coverage and number of eels tagged. The eels were tracked using acoustic telemetry and the Nedap Trail System and allowed us to study the eel's migration phenology at a continental scale. The findings reveal that the day when eels arrive at sea varies significantly with latitude, with northern eels arriving earlier. Migration speed differs between tidal and non‐tidal habitats, suggesting that tidal currents facilitate faster movement. However, despite these patterns, we observed substantial variability in arrival at sea time and migration speed within water bodies, suggesting that the eel's migration phenology is considerably plastic. The presence of water regulating structures such as weirs, pumping stations and hydropower plants can impact migration timing and speed, potentially delaying eels, but is likely dependent on local hydrological conditions which can be water body specific.

Global Change Asymmetrically Rewires Ecosystems - Charlotte A. Ward; Tyler D. Tunney; Ian Donohue; Carling Bieg; Kayla R. S. Hale; Bailey C. McMeans; John C. Moore; Kevin S. McCann (Ecology Letters, 2025)
Global change is complex and multidimensional, making it challenging to understand how human activities affect ecosystem processes. A critical gap in this understanding is how drivers of global change broadly affect food webs. While an industry of studies documents shifts in food webs in response to anthropogenic pressures, a general synthesis is lacking. To address this, we review studies across diverse ecosystems that use stable isotope analysis, energetic food web modelling and gut content analysis to reveal the prevalence of asymmetric rewiring—a phenomenon whereby anthropogenic pressures differentially impact habitats across space, altering some energy pathways within food webs relative to others. We then highlight several examples from the literature to illustrate how this process unfolds. To explore its broader consequences, we use a simple food web model to demonstrate how asymmetric rewiring alters resilience and key ecosystem functions, such as primary and secondary production. Our synthesis uncovers a remarkably general response in food web structure to global change that needs to be better understood to protect nature and the services that human societies rely on in a rapidly changing world.

Economic and environmental performance of biomass gasification for renewable natural gas production in the context of the U.S. natural gas supply - O.A. Oyedeji; A.M. Moore; D. Kamath; I.K. Busch; S.J. Curran; M. Henriksen; M. Jamieson; T.E. Fout; E.G. Webb; M.H. Langholtz; T.J. Theiss (Biomass and Bioenergy, 2025)

From Depletion to Restoration: Lessons From Long‐Term Monitoring of Carbon Gains and Losses in Cropping Systems - Caitlin E. Moore; Bethany Blakely; Taylor L. Pederson; Nuria Gomez‐Casanovas; Christy D. Gibson; Anya M. Knecht; Guler Aslan‐Sungur; Evan H. DeLucia; Emily A. Heaton; Andy VanLoocke; Tilden Meyers; Carl J. Bernacchi (Global Change Biology, 2025)
As global atmospheric CO 2 rapidly approaches a key tipping point, there is an urgent need to implement strategies to reverse this pattern. A generally accepted understanding of carbon (C) in agricultural fields includes: (H1) substantial C loss occurs when natural vegetation is converted to crops, (H2) soils typically reach a steady‐state C concentration under contemporary practices, and (H3) improved management or crop selection can enhance soil C stocks over time. Significant variability exists, but studies consistently show large C losses from agricultural ecosystems, supporting H1. Although steady‐state C levels (H2) are commonly assumed, measuring C gains or losses in mature agroecosystems is challenging. Efforts to increase soil C storage (H3) have limited data due to the diversity of potential practices, compounded by substantial variability in soil C measurements. Here, long‐term (7–17 year) ecosystem C flux data from diverse cropping systems revealed that conventionally tilled annual row crops (maize and soybean) act as significant long‐term atmospheric C sources, challenging H2. Furthermore, conservation tillage practices reduced C losses compared with conventional tillage but showed minimal evidence for long‐term ecosystem C storage, even after 20+ years. This indicates that no‐till practices reduce C losses but imply that no soil C is added, challenging H3. By contrast, perennial Miscanthus × giganteus , Panicum virgatum , and restored tallgrass prairie systems store C at the ecosystem scale more effectively than minimally tilled annual row crops. Analysis over multiple years demonstrates significant ecosystem C storage with perennial crops, varying by species, starting in the first year of transition. These findings, although focused on one region, suggest that the assumptions of steady‐state C levels and increased storage from conservation practices do not universally apply and that significant changes to agroecosystems are required to increase C storage.

Discussion of Clemens, J. D. (2025). Regional tectonics, crustal deformation and contrasting batholith orientations in southeastern Australia: why is Late Devonian central Victoria different? Australian Journal of Earth Sciences, 72 (3), 297–315. https://doi.org/10.1080/08120099.2025.2505030 - D. H. Moore (Australian Journal of Earth Sciences, 2025)

Quantifying the Relative Importance of Sand Deposition and Dune Grasses to Carbon Storage in US Central Atlantic Coast Dunes - Katya R. Jay; Sally D. Hacker; Cedric J. Hagen; John Stepanek; Laura J. Moore; Peter Ruggiero (Estuaries and Coasts, 2025)
Coastal ecosystems such as mangroves, salt marshes, and seagrasses sequester large amounts of carbon per unit area due to their high productivity and sediment accumulation rates. However, only a handful of studies have examined carbon sequestration in coastal dunes, which are shaped by biophysical feedback between aeolian sediment transport and burial-tolerant vegetation. The goal of this study was to measure carbon storage and identify the factors that influence its variability along the foredunes of the US Outer Banks barrier islands of North Carolina. Specifically, differences in carbon stocks (above- and belowground biomass and sand), dune grass abundance, and sand supply were measured among islands, cross-shore dune profile locations, and dune grass species. Carbon varied among aboveground grass biomass (0.1 ± 0.1 kg C m −2 ), belowground grass biomass (1.1 ± 1.6 kg C m −3 ), and sand (0.9 ± 0.6 kg C m −3 ), with the largest amount in belowground grass stocks. Aboveground grass carbon stocks were comparable to those in eelgrass beds and salt marshes on a per-area basis, while sediment carbon values in our study system were lower than those in other coastal systems, including other dune locations. Additionally, sand carbon density was positively related to patterns in dune sand supply and grass abundance, reflecting a self-reinforcing vegetation-sediment feedback at both high and low sand accumulation rates.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Addressing decarbonization strategies through a game theory perspective - Elizabeth A. Moore; Karan Bhuwalka; Andy Zhu; Yijia Chen; Panya Tang; Jennifer D. Russell; Randolph Kirchain; Richard Roth (Resources, Conservation and Recycling, 2025)

Enhanced microplastic fragmentation along human built structures in an urban waterway - E. K. Moore; L. Pittman; M. Heminghaus; D. Heintzelman; A. Hatter (International Journal of Environmental Science and Technology, 2025)

Triangulating habitat suitability for the locally extirpated California grizzly bear - Alex McInturff; Peter S. Alagona; Scott D. Cooper; Kaitlyn M. Gaynor; Sarah E. Anderson; Elizabeth S. Forbes; Robert Heilmayr; Elizabeth H.T. Hiroyasu; Bruce E. Kendall; Alexis M. Mychajliw; Molly Hardesty-Moore (Biological Conservation, 2025)

Groundwater flowpath characteristics drive variability in per- and polyfluoroalkyl substances (PFAS) loading across a stream-wetland system - David M. Rey; Martin A. Briggs; Andrea K. Tokranov; Hayley G. Lind; Patrick T. Scordato; Ramona Darlington Iery; Henry E. Moore; Lee D. Slater; Denis R. LeBlanc (Science of The Total Environment, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Synthesis of encapsulated nanofertilizer from biogas plant digestate - Edward D. Nasser; Joel Kenneth M. Ngojo; Ramiro Emerson C. Amon; Jayvee Moore S. Dy; Julius J. Rosalia; Chosel P. Lawagon (Bioresource Technology Reports, 2025)

Labile Soil Carbon Heterogeneity Driven by Consumer Engineering of Aboveground Structure in a Kenyan Savanna - Elizabeth S. Forbes; Dana D. Moore; John Naisikie Mantas; Joshua Schimel; Truman P. Young; Hillary S. Young (Ecosystems, 2025)
Aboveground ecosystem structure moderates and even confers essential ecosystem functions. This includes an ecosystem’s carbon dynamics, which are strongly influenced by its structure: for example, tropical savannas like those in central Kenya store substantial amounts of carbon in soil. Savannas’ belowground allocation of carbon makes them important for global carbon sequestration, but difficult to monitor. However, the labile soil carbon pool is responsive to changes in ecosystem structure and is thus a good indicator of overall soil organic carbon dynamics. Kenya’s savanna structure is controlled by belowground ecosystem engineers (termites), ambient weather conditions, and the aboveground engineering influences of large-bodied, mammalian consumers. As a result, climate change and biodiversity loss are likely to change savannas’ aboveground structure. To predict likely outcomes of these threats on savanna soil carbon, it is critical to explore the relationships between labile soil carbon and ecosystem structure, local climate, and mammalian consumer community composition. In a large-scale, long-term herbivore exclosure experiment in central Kenya, we sampled labile carbon from surface soils at three distinct savanna structural elements: termite mounds, beneath tree canopies, and the grassland matrix. In one sampling year, we measured total extractable organic carbon (TEOC), total extractable nitrogen (TEN), and extractable microbial biomass for each sample. Across three sampling years with varying weather conditions, we measured rate of labile soil carbon mineralization. We quantified areal coverage of each structural element across herbivore community treatments to estimate pool sizes and mineralization dynamics at the plot scale. Concentrations and stocks of soil TEOC, TEN, and microbial biomass were driven by the structural element from which they were sampled (soils collected under tree canopies generally had the highest of each). Large-bodied herbivore community composition interacted variably with concentrations, stocks, and carbon mineralization, resulting in apparently compensatory effects of herbivore treatment and structural element with no net effects of large herbivore community composition on plot-scale labile carbon dynamics. We confirmed engineering of structural heterogeneity by consumers and identified distinct labile carbon dynamics in each structural element. However, carbon and nitrogen were also influenced by consumer community composition, indicating potentially compensatory interacting effects of herbivore treatment and structural element. These results suggest that one pathway by which consumers influence savanna carbon is by altering its structural heterogeneity and thus the heterogeneity of its plot-scale labile carbon.

5-HT2C agonism as a neurotherapeutic for sarcopenia: preclinical proof of concept - Nathan R. Kerr; Anna R. Dashtmian; Fereshteh B. Darvishi; Charles D. Brennan; Sindhuja N. Ayyagari; Peter J. Moore; Jose A. Viteri; Meifang Wang; Mark M. Rich; Brian C. Clark; W. David Arnold (GeroScience, 2025)

Establishing the limitations on using archived marine mammal samples for stable isotope analysis: an examination of differing preservation methods on tissues of harbor porpoise ( Phocoena phocoena ) and gray seal ( Halichoerus grypus ) - Daniel M. Moore; Emily G. Cunningham; Kayla D. Crowder; Darren R. Gröcke (Marine Mammal Science, 2025)
The use of biological samples from museum and/or archive collections is common in stable isotope research, particularly for marine mammals. Yet, the temporal stability of isotopic values across various tissue types and the influence of different preservatives on these values are not fully understood, posing significant challenges for accurate data interpretation. Here we examine the impact of three different tissue preservation methods (DMSO, ethanol, freezing), on seven different tissues (blubber, heart, kidney, lung, liver, muscle, and skin) from both a harbor porpoise ( Phocoena phocoena ) and a gray seal ( Halichoerus grypus ) for stable isotope analysis in a 1‐year period. Our results demonstrate that storage in DMSO generates greater temporal variability in δ 13 C and δ 15 N for all tissue types, particularly in the first six months of storage. Furthermore, tissues stored in DMSO often exhibited lower δ13C and δ15N values compared to those stored frozen or in ethanol. This finding highlights a significant issue for studies utilizing tissues stored in DMSO, regardless of the storage duration. These results underscore the critical need for careful consideration of preservation methods in studies involving stored tissues, providing valuable insights for experimental design and management of tissue archives.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Revealing continuity and sustainability through isotope analysis on the A14 project, Cambridgeshire, UK - M. Wallace; J. Montgomery; B. Rogers; J. Moore; G. Nowell; D. Bowsher; A. Smith (Quaternary Science Reviews, 2024)

Mechanical study and equations for gravity flow pipe liners stretching across ring fractures or joints under shear action - Kejie Zhai; Ian D. Moore (Ocean Engineering, 2024)

Characterisation of dissolved organic matter in two contrasting arsenic-prone sites in Kandal Province, Cambodia - Oliver C. Moore; Amy D. Holt; Laura A. Richards; Amy M. McKenna; Robert G.M. Spencer; Dan J. Lapworth; David A. Polya; Jonathan R. Lloyd; Bart E. van Dongen (Organic Geochemistry, 2024)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Mn-porphyrins in a four-helix bundle participate in photo-induced electron transfer with a bacterial reaction center - J. C. Williams; M. S. Faillace; E. J. Gonzalez; R. E. Dominguez; K. Knappenberger; D. A. Heredia; T. A. Moore; A. L. Moore; J. P. Allen (Photosynthesis Research, 2024)

Promoting best practices in ocean forecasting through an Operational Readiness Level - E. Alvarez Fanjul; S. Ciliberti; J. Pearlman; K. Wilmer-Becker; P. Bahurel; F. Ardhuin; A. Arnaud; K. Azizzadenesheli; R. Aznar; M. Bell; L. Bertino; S. Behera; et al. (Frontiers in Marine Science, 2024)
Predicting the ocean state in a reliable and interoperable way, while ensuring high-quality products, requires forecasting systems that synergistically combine science-based methodologies with advanced technologies for timely, user-oriented solutions. Achieving this objective necessitates the adoption of best practices when implementing ocean forecasting services, resulting in the proper design of system components and the capacity to evolve through different levels of complexity. The vision of OceanPrediction Decade Collaborative Center, endorsed by the UN Decade of Ocean Science for Sustainable Development 2021-2030, is to support this challenge by developing a “predicted ocean based on a shared and coordinated global effort” and by working within a collaborative framework that encompasses worldwide expertise in ocean science and technology. To measure the capacity of ocean forecasting systems, the OceanPrediction Decade Collaborative Center proposes a novel approach based on the definition of an Operational Readiness Level (ORL). This approach is designed to guide and promote the adoption of best practices by qualifying and quantifying the overall operational status. Considering three identified operational categories - production, validation, and data dissemination - the proposed ORL is computed through a cumulative scoring system. This method is determined by fulfilling specific criteria, starting from a given base level and progressively advancing to higher levels. The goal of ORL and the computed scores per operational category is to support ocean forecasters in using and producing ocean data, information, and knowledge. This is achieved through systems that attain progressively higher levels of readiness, accessibility, and interoperability by adopting best practices that will be linked to the future design of standards and tools. This paper discusses examples of the application of this methodology, concluding on the advantages of its adoption as a reference tool to encourage and endorse services in joining common frameworks.

Acute exercise might not affect subsequent appetite responses to a fixed meal in adolescents with obesity: The SMASH exploratory study - J. Siroux; H. Moore; L. Isacco; A. Couvert; B. Pereira; V. Julian; M. Duclos; M. Miyashita; G. Finlayson; Y. Boirie; D. Thivel (Appetite, 2024)

Multi-decadal aspen dynamics show recruitment bottleneck across complex mountain community - Michael T. Stoddard; Kyle C. Rodman; Connor D. Crouch; David W. Huffman; Peter Z. Fulé; Kristen M. Waring; Margaret M. Moore (Forest Ecology and Management, 2024)

Results from the InSight atmospheric imaging campaign - M.T. Lemmon; C.L. Campbell; C.A. Wolfe; D. Viúdez-Moreiras; R.D. Lorenz; J.N. Maki; J. Moores; A. Spiga; D. Banfield (Icarus, 2024)

Episodic ozone exposure in Long-Evans rats has limited effects on cauda sperm motility and non-coding RNA populations - Brian N. Chorley; Gary R. Klinefelter; Gail M. Nelson; Lillian F. Strader; Helen H. Nguyen; Mette C. Schladweiler; Grant Palmer; Makala L. Moore; Rachel D. Grindstaff; William T. Padgett; Gleta K. Carswell; Anna A. Fisher; et al. (Reproductive Toxicology, 2024)

Glacial sculpting of a martian cratered landscape on the northeastern flank of the Hellas basin - Anna Grau Galofre; Alan D. Howard; Alexander M. Morgan; Sharon A. Wilson; Jeffrey M. Moore (Icarus, 2024)

Suitability of false codling moth eggs from different sterile to fertile moth ratios in the sterile insect technique programme, to parasitism by Trichogrammatoidea cryptophlebiae - Michael M. Githae; Candice A. Coombes; Reyard Mutamiswa; Sean D. Moore; Martin P. Hill (Crop Protection, 2024)

Integrating animals, pasture, and crops within AusFarm for modelling mixed farming - Neville I. Herrmann; Andrew D. Moore; Eric Zurcher (Environmental Modelling & Software, 2024)

Indications of preferential groundwater seepage feeding northern peatland pools - Henry E. Moore; Xavier Comas; Martin A. Briggs; Andrew S. Reeve; Lee D. Slater (Journal of Hydrology, 2024)

Physicochemical compatibility of caffeine citrate and caffeine base injections with parenteral medications used in neonatal intensive care settings - D. Thisuri N. De Silva; Michael Petrovski; Tobias Strunk; Nabeelah Mukadam; Madhu Page-Sharp; Brioni R. Moore; Kevin T. Batty (European Journal of Clinical Pharmacology, 2024)
Purpose To investigate the physicochemical compatibility of caffeine citrate and caffeine base injections with 43 secondary intravenous (IV) drugs used in Neonatal Intensive Care Unit (NICU) settings. Methods Caffeine citrate (20 mg/mL or 10 mg/mL) or caffeine base injection (10 mg/mL) were mixed in a volume ratio of 1:1 with the secondary drug solution to simulate Y-site co-administration procedures in NICUs. Physical compatibility was evaluated based on visual observation for 2 h, against a black and white background and under polarised light, for changes in colour, precipitation, haze and evolution of gas. Chemical compatibility was determined from caffeine concentration measurements, using a validated high-performance liquid chromatography assay. Results Six of the 43 secondary drugs tested (aciclovir, amphotericin (liposomal), furosemide, hydrocortisone, ibuprofen and ibuprofen lysine) were physically incompatible with caffeine citrate undiluted injection (20 mg/mL), at their high-end, clinically relevant concentrations for NICU settings. However, when tested at lower concentrations, hydrocortisone (1 mg/mL) was physicochemically compatible, whereas furosemide (0.2 mg/mL) was physically incompatible with caffeine citrate. The six drugs which showed physical incompatibility with caffeine citrate 20 mg/mL injection were also physically incompatible with caffeine citrate 10 mg/mL solution. All 43 secondary drugs tested were physicochemically compatible with caffeine base injection. Conclusions Most secondary test drugs, except aciclovir, amphotericin (liposomal), furosemide, hydrocortisone, ibuprofen and ibuprofen lysine, were physicochemically compatible with caffeine citrate injection. Caffeine base injection was physicochemically compatible with all 43 test drugs tested.

Undergraduate Students’ Engineering Systems Thinking in Synthetic Biology Design: A Qualitative Descriptive Study - Ruben D. Lopez-Parra; Tamara J. Moore (Biomedical Engineering Education, 2024)

Impacts of irregularly-distributed acidified brine flow on geo-chemo-mechanical alteration in an artificial shale fracture under differential stress - Samantha J. Fuchs; Dustin Crandall; Johnathan E. Moore; Mayandi Sivaguru; Bruce W. Fouke; D. Nicolas Espinoza; Ange-Therese Akono; Charles J. Werth (International Journal of Greenhouse Gas Control, 2024)

Human‐modified habitats imperil ornamented dragonflies less than their non‐ornamented counterparts at local, regional, and continental scales - Michael P. Moore; Noah T. Leith; Kasey D. Fowler‐Finn; Kim A. Medley (Ecology Letters, 2024)
Biologists have long wondered how sexual ornamentation influences a species' risk of extinction. Because the evolution of condition‐dependent ornamentation can reduce intersexual conflict and accelerate the fixation of advantageous alleles, some theory predicts that ornamented taxa can be buffered against extinction in novel and/or stressful environments. Nevertheless, evidence from the wild remains limited. Here, we show that ornamented dragonflies are less vulnerable to extinction across multiple spatial scales. Population‐occupancy models across the Western United States reveal that ornamented species have become more common relative to non‐ornamented species over >100 years. Phylogenetic analyses indicate that ornamented species exhibit lower continent‐wide extinction risk than non‐ornamented species. Finally, spatial analyses of local dragonfly assemblages suggest that ornamented species possess advantages over non‐ornamented taxa at living in habitats that have been converted to farms and cities. Together, these findings suggest that ornamented taxa are buffered against contemporary extinction at local, regional, and continental scales.

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Field-scale efficacy of entomopathogenic nematodes to control false codling moth, Thaumatotibia leucotreta (Lepidoptera: Tortricidae), in citrus orchards in South Africa - Sean D. Moore; Ralf-Udo Ehlers; Aruna Manrakhan; Martin Gilbert; Wayne Kirkman; John-Henry Daneel; Jeanne Y. De Waal; Rynhardt Nel; Guy Sutton; Antoinette P. Malan (Crop Protection, 2024)

Impact of storm events on disinfection byproduct precursors in a drinking water source in the Northeastern United States - Mohammad (Kiron) Shakhawat; Rakesh K. Gelda; Karen E. Moore; Rajith Mukundan; Mariana Lanzarini-Lopes; Sean T. McBeath; Christian D. Guzman; Dave Reckhow (Water Research, 2024)

Maturing the concept of small-scale mining (SSM) in the Global North using concept evaluation criteria on the placer mining industry in Yukon, Canada - C. Johnson; K.R. Moore; D. Johnson (Resources Policy, 2024)

Identification of Regulatory Elements in Primary Sensory Neurons Involved in Trauma-Induced Neuropathic Pain - Kimberly E. Stephens; Cedric Moore; David A. Vinson; Bryan E. White; Zachary Renfro; Weiqiang Zhou; Zhicheng Ji; Hongkai Ji; Heng Zhu; Yun Guan; Sean D. Taverna (Molecular Neurobiology, 2024)
Chronic pain is a significant public health issue that is often refractory to existing therapies. Here we use a multiomic approach to identify cis-regulatory elements that show differential chromatin accessibility and reveal transcription factor (TF) binding motifs with functional regulation in the rat dorsal root ganglion (DRG), which contain cell bodies of primary sensory neurons, after nerve injury. We integrated RNA-seq to understand how differential chromatin accessibility after nerve injury may influence gene expression. Using TF protein arrays and chromatin immunoprecipitation-qPCR, we confirmed C/EBPγ binding to a differentially accessible sequence and used RNA-seq to identify processes in which C/EBPγ plays an important role. Our findings offer insights into TF motifs that are associated with chronic pain. These data show how interactions between chromatin landscapes and TF expression patterns may work together to determine gene expression programs in rat DRG neurons after nerve injury.

David versus Goliath: Early career researchers in an unethical publishing system - Aurore Receveur; Jonathan Bonfanti; Stephanie D'Agata; Andrew J. Helmstetter; Nikki A. Moore; Brunno F. Oliveira; Cathleen Petit‐Cailleux; Erica Rievrs Borges; Marieke Schultz; Aaron N. Sexton; Devi Veytia (Ecology Letters, 2024)
The publish‐or‐perish culture in academia has catalysed the development of an unethical publishing system. This system is characterised by the proliferation of journals and publishers—unaffiliated with learned societies or universities—that maintain extremely large revenues and profit margins diverting funds away from the academic community. Early career researchers (ECRs) are particularly vulnerable to the consequences of this publishing system because of intersecting factors, including pressure to pursue high impact publications, rising publication costs and job insecurity. Moving towards a more ethical system requires that scientists advocate for structural change by making career choices that come with risks, many of which disproportionately impact ECRs. We illuminate major issues facing ECRs in Ecology and Evolution under the current publishing system, and propose a portfolio of actions to promote systemic change that can be implemented by ECRs and established researchers.

Mud infiltration and travel paths during mud loss experiments on horizontal borehole stability - Haitao Lan; Xuefeng Yan; Ian D. Moore (Tunnelling and Underground Space Technology, 2024)

Detection of human enteric viruses in fresh produce of markets, farms and surface water used for irrigation in the Tehran, Iran - Maedeh Rafieepoor; Seyed Reza Mohebbi; Seyed Masoud Hosseini; Mohammad Tanhaei; Mahsa Saeedi Niasar; Shabnam Kazemian; Matthew D. Moore; Mohammad Reza Zali (Science of The Total Environment, 2024)

Constraints from lamprophyre petrogenesis on the timing of Eocene lithospheric thinning and associated rifting of Borneo and Sulawesi - David Murphy; Tim A. Moore; D. Hendra Amijaya; Ferian Anggara; Mike Friederich; Carmen Gaina; Jessica Trofimovs; Hayden Dalton; Edafe Ominigbo (Journal of Asian Earth Sciences, 2024)

Parasites alter food-web topology of a subarctic lake food web and its pelagic and benthic compartments - Shannon E. Moore; Anna Siwertsson; Kevin D. Lafferty; Armand M. Kuris; Miroslava Soldánová; Dana Morton; Raul Primicerio; Per-Arne Amundsen (Oecologia, 2024)
We compared three sets of highly resolved food webs with and without parasites for a subarctic lake system corresponding to its pelagic and benthic compartments and the whole-lake food web. Key topological food-web metrics were calculated for each set of compartments to explore the role parasites play in food-web topology in these highly contrasting webs. After controlling for effects from differences in web size, we observed similar responses to the addition of parasites in both the pelagic and benthic compartments demonstrated by increases in trophic levels, linkage density, connectance, generality, and vulnerability despite the contrasting composition of free-living and parasitic species between the two compartments. Similar effects on food-web topology can be expected with the inclusion of parasites, regardless of the physical characteristics and taxonomic community compositions of contrasting environments. Additionally, similar increases in key topological metrics were found in the whole-lake food web that combines the pelagic and benthic webs, effects that are comparable to parasite food-web analyses from other systems. These changes in topological metrics are a result of the unique properties of parasites as infectious agents and the links they participate in. Trematodes were key contributors to these results, as these parasites have distinct characteristics in aquatic systems that introduce new link types and increase the food web’s generality and vulnerability disproportionate to other parasites. Our analysis highlights the importance of incorporating parasites, especially trophically transmitted parasites, into food webs as they significantly alter key topological metrics and are thus essential for understanding an ecosystem’s structure and functioning.

How thick is the Strathbogie Complex? - D. H. Moore; R. J. Armit (Australian Journal of Earth Sciences, 2024)

Catch per unit effort modelling for stock assessment: A summary of good practices - Simon D. Hoyle; Robert A. Campbell; Nicholas D. Ducharme-Barth; Arnaud Grüss; Bradley R. Moore; James T. Thorson; Laura Tremblay-Boyer; Henning Winker; Shijie Zhou; Mark N. Maunder (Fisheries Research, 2024)

Long-term ozone exposure and lung function in middle childhood - Marnie F. Hazlehurst; Logan C. Dearborn; Allison R. Sherris; Christine T. Loftus; Margaret A. Adgent; Adam A. Szpiro; Yu Ni; Drew B. Day; Joel D. Kaufman; Neeta Thakur; Rosalind J. Wright; Sheela Sathyanarayana; et al. (Environmental Research, 2024)

Habitat modulates population‐level responses of freshwater salmon growth to a century of change in climate and competition - Michael H. H. Price; Jonathan W. Moore; Skip McKinnell; Brendan M. Connors; John D. Reynolds (Global Change Biology, 2024)
The impacts of climate change are widespread and threaten natural systems globally. Yet, within regions, heterogeneous physical landscapes can differentially filter climate, leading to local response diversity. For example, it is possible that while freshwater lakes are sensitive to climate change, they may exhibit a diversity of thermal responses owing to their unique morphology, which in turn can differentially affect the growth and survival of vulnerable biota such as fishes. In particular, salmonids are cold‐water fishes with complex life histories shaped by diverse freshwater habitats that are sensitive to warming temperatures. Here we examine the influence of habitat on the growth of sockeye salmon ( Oncorhynchus nerka ) in nursery lakes of Canada's Skeena River watershed over a century of change in regional temperature and intraspecific competition. We found that freshwater growth has generally increased over the last century. While growth tended to be higher in years with relatively higher summer air temperatures (a proxy for lake temperature), long‐term increases in growth appear largely influenced by reduced competition. However, habitat played an important role in modulating the effect of high temperature. Specifically, growth was positively associated with rising temperatures in relatively deep (>50 m) nursery lakes, whereas warmer temperatures were not associated with a change in growth for fish among shallow lakes. The influence of temperature on growth also was modulated by glacier extent whereby the growth of fish from lakes situated in watersheds with little (i.e.,

Validating assumptions in calculating carbon dioxide removal by enhanced rock weathering in Kantola et al., 2023 - Adam Wolf; Elliot Chang; Ilsa B. Kantola; Elena Blanc‐Betes; Michael D. Masters; Alison Marklein; Caitlin E. Moore; Carl J. Bernacchi; Evan H. DeLucia (Global Change Biology, 2024)

Electrostatic precipitator collection efficiency studies using atmospheric radon progeny as aerosol analogs for nuclear explosion radionuclides - Michael E. Moore; Martin E. Keillor; Dustin M. Kasparek; Anthony R. Day; Brian D. Glasgow (Journal of Environmental Radioactivity, 2023)

Does prey availability influence the detection of Dinophysis spp. by the imaging FlowCytobot? - Emilie Houliez; Alexis D. Fischer; Brian D. Bill; Stephanie K. Moore (Harmful Algae, 2023)

Improved net carbon budgets in the US Midwest through direct measured impacts of enhanced weathering - Ilsa B. Kantola; Elena Blanc‐Betes; Michael D. Masters; Elliot Chang; Alison Marklein; Caitlin E. Moore; Adam von Haden; Carl J. Bernacchi; Adam Wolf; Dimitar Z. Epihov; David J. Beerling; Evan H. DeLucia (Global Change Biology, 2023)
Terrestrial enhanced weathering (EW) through the application of Mg‐ or Ca‐rich rock dust to soil is a negative emission technology with the potential to address impacts of climate change. The effectiveness of EW was tested over 4 years by spreading ground basalt (50 t ha −1 year −1 ) on maize/soybean and miscanthus cropping systems in the Midwest US. The major elements of the carbon budget were quantified through measurements of eddy covariance, soil carbon flux, and biomass. The movement of Mg and Ca to deep soil, released by weathering, balanced by a corresponding alkalinity flux, was used to measure the drawdown of CO 2 , where the release of cations from basalt was measured as the ratio of rare earth elements to base cations in the applied rock dust and in the surface soil. Basalt application stimulated peak biomass and net primary production in both cropping systems and caused a small but significant stimulation of soil respiration. Net ecosystem carbon balance (NECB) was strongly negative for maize/soybean (−199 to −453 g C m −2 year −1 ) indicating this system was losing carbon to the atmosphere. Average EW (102 g C m −2 year −1 ) offset carbon loss in the maize/soybean by 23%–42%. NECB of miscanthus was positive (63–129 g C m −2 year −1 ), indicating carbon gain in the system, and EW greatly increased inorganic carbon storage by an additional 234 g C m −2 year −1 . Our analysis indicates a co‐deployment of a perennial biofuel crop (miscanthus) with EW leads to major wins—increased harvested yields of 29%–42% with additional carbon dioxide removal (CDR) of 8.6 t CO 2 ha −1 year −1 . EW applied to maize/soybean drives a CDR of 3.7 t CO 2 ha −1 year −1 , which partially offsets well‐established carbon losses from soil from this crop rotation. EW applied in the US Midwest creates measurable improvements to the carbon budgets perennial bioenergy crops and conventional row crops.

Are the surface textures of Pluto's Wright Mons and its surroundings exogenic? - Alan D. Howard; Jeffrey M. Moore; Orkan M. Umurhan; Oliver L. White; Kelsi N. Singer; Paul M. Schenk (Icarus, 2023)

Drought conditioning of rhizosphere microbiome influences maize water use traits - Kelsey R. Carter; Abigael C. Nachtsheim; L. Turin Dickman; Eric R. Moore; Sangeeta Negi; John P. Heneghan; Anthony J. Sabella; Christina R. Steadman; Michaeline B. N. Albright; Christine M. Anderson-Cook; Louise H. Comas; Rose J. Harris; et al. (Plant and Soil, 2023)
Background and Aims Beneficial plant–microbe interactions can improve plant performance under drought; however, we know less about how drought-induced shifts in microbial communities affect plant traits. Methods We cultivated Zea mays in fritted clay with soil microbiomes originating from contrasting environments (agriculture or forest) under two irrigation treatments (well-watered or water limited). Using this design, we investigated whether water conditioning was carried forward through the microbiome to affect a subsequent plant cohort that was subjected to either a well-watered or water limited treatment. Results Regardless of the microbiome-origin, plants inoculated with a microbiome from a water limited legacy had traits that allowed them to avoid stress but conserve water. They produced longer roots to explore soil, generated greater soil dissolved organic carbon, potentially stimulating the microbiome, and slower soil water content loss during drought. A well-watered legacy resulted in plants that delayed permanent stomatal closure and higher photosynthetic nitrogen use efficiency. In plants with a forest-originated microbiome, a well-watered legacy and water treatment also resulted in higher rates of photosynthesis and stomatal conductance. Conclusion These results demonstrate that soil microbiomes can be developed to influence plant drought performance, impacting crop resilience, using short-term microbial conditioning.

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Effort-related effects of chronic administration of the DA D2 receptor antagonist haloperidol via subcutaneous programmable minipumps: Reversal by co-administration of the adenosine A2A antagonist istradefylline - Renee A. Rotolo; Alev Ecevitoglu; Rose E. Presby; Hanna Lindgren; Cedric Mombereau; Cyrene Nicholas; Alana Moore; Gayle A. Edelstein; Merce Correa; John D. Salamone (Psychopharmacology, 2023)

Bycatch in northeast Atlantic lobster and crab pot fisheries (Irish Sea, Celtic Sea and Bristol Channel) - Alec B.M. Moore; Charlotte Heney; Harriet Lincoln; Charlotte Colvin; Hadley Newell; Rebecca Turner; Ian D. McCarthy; Natalie Hold (Fisheries Research, 2023)

Impact of a Digital Health Coaching Program on Individuals with T2DM Experiencing Food Insecurity in Rural Areas - J. Moore; V. Tran; C. Harrison; M. McMorris; M. Johnson; S. Spradlin; J. King; L. Campbell; I. Washington; D. Bivens (Journal of the Academy of Nutrition and Dietetics, 2023)

Urban heat and desert wildlife: rodent body condition across a gradient of surface temperatures - H. L. Bateman; B. D. Allen; M. S. Moore; D. M. Hondula (Urban Ecosystems, 2023)

TAAR1 Regulates Purinergic-induced TNF Secretion from Peripheral, But Not CNS-resident, Macrophages - David A. Barnes; Marius C. Hoener; Craig S. Moore; Mark D. Berry (Journal of Neuroimmune Pharmacology, 2023)

Building Ecosystem Resilience and Adaptive Capacity: a Systematic Review of Aspen Ecology and Management in the Southwest - Connor D Crouch; Paul C Rogers; Margaret M Moore; Kristen M Waring (Forest Science, 2023)
Quaking aspen (Populus tremuloides Michx.) has high conservation value on the southwestern edge of its range, which extends from the southwestern United States (i.e., Arizona, New Mexico, and Texas) to central Mexico. This value is driven by aspen’s ecological importance, positive impact on local economies, and aesthetic and cultural values. Generally, the scant aspen populations that remain in the Southwest lack resilience and adaptive capacity, and managers are unsure how best to maintain the species in an uncertain future. This systematic review seeks to address that need by reviewing existing literature from the Southwest on which biotic and abiotic factors influence aspen forest dynamics and by synthesizing that literature with a discussion of how management can promote aspen ecosystem resilience and adaptive capacity. We found that fire and silvicultural treatments promote aspen regeneration, but chronic ungulate browse inhibits recruitment. Moreover, drought is a driver of overstory mortality and has a negative influence on recruitment. In the second half of this review, we propose three management objectives for increasing aspen resilience and adaptive capacity: (1) promote diversity in age structure, (2) mitigate ungulate impacts, and (3) enhance complexity. We consider how various management strategies could meet these objectives and highlight potential threats to aspen forest health and resilience.

Growing and non-growing season nitrous oxide emissions from a manured semiarid cropland soil under irrigation - Robert S. Dungan; April B. Leytem; Amber D. Moore; David L. Bjorneberg; Peter R. Grace; Christian Brunk; David W. Rowlings (Agriculture, Ecosystems & Environment, 2023)

Biomass Quality Responses to Selection for Increased Biomass Yield in Perennial Energy Grasses - Michael D. Casler; DoKyoung Lee; Robert B. Mitchell; Kenneth J. Moore; Paul R. Adler; R. Mark Sulc; Keith D. Johnson; Robert L. Kallenbach; Arvid R. Boe; Russell D. Mathison; Kim A. Cassida; Doohong Min; et al. (BioEnergy Research, 2023)

Drivers of the microbial metabolic quotient across global grasslands - A. C. Risch; S. Zimmermann; M. Schütz; E. T. Borer; A. A. D. Broadbent; M. C. Caldeira; K. F. Davies; N. Eisenhauer; A. Eskelinen; P. A. Fay; F. Hagedorn; J. M. H. Knops; et al. (Global Ecology and Biogeography, 2023)
Aim The microbial metabolic quotient (MMQ; mg CO 2 ‐C/mg MBC/h), defined as the amount of microbial CO 2 respired (MR; mg CO 2 ‐C/kg soil/h) per unit of microbial biomass C (MBC; mg C/kg soil), is a key parameter for understanding the microbial regulation of the carbon (C) cycle, including soil C sequestration. Here, we experimentally tested hypotheses about the individual and interactive effects of multiple nutrient addition (nitrogen + phosphorus + potassium + micronutrients) and herbivore exclusion on MR, MBC and MMQ across 23 sites (five continents). Our sites encompassed a wide range of edaphoclimatic conditions; thus, we assessed which edaphoclimatic variables affected MMQ the most and how they interacted with our treatments. Location Australia, Asia, Europe, North/South America. Time period 2015–2016. Major taxa Soil microbes. Methods Soils were collected from plots with established experimental treatments. MR was assessed in a 5‐week laboratory incubation without glucose addition, MBC via substrate‐induced respiration. MMQ was calculated as MR/MBC and corrected for soil temperatures (MMQsoil). Using linear mixed effects models (LMMs) and structural equation models (SEMs), we analysed how edaphoclimatic characteristics and treatments interactively affected MMQsoil. Results MMQsoil was higher in locations with higher mean annual temperature, lower water holding capacity and lower soil organic C concentration, but did not respond to our treatments across sites as neither MR nor MBC changed. We attributed this relative homeostasis to our treatments to the modulating influence of edaphoclimatic variables. For example, herbivore exclusion, regardless of fertilization, led to greater MMQsoil only at sites with lower soil organic C ( Main conclusions Our results pinpoint the main variables related to MMQsoil across grasslands and emphasize the importance of the local edaphoclimatic conditions in controlling the response of the C cycle to anthropogenic stressors. By testing hypotheses about MMQsoil across global edaphoclimatic gradients, this work also helps to align the conflicting results of prior studies.

Championing inclusive terminology in ecology and evolution - Susan J. Cheng; Kaitlyn M. Gaynor; Alex C. Moore; Kathy Darragh; Cesar O. Estien; J.W. Hammond; Christopher Lawrence; Kirby L. Mills; Marcella D. Baiz; Danielle Ignace; Lily Khadempour; Matthew A. McCary; et al. (Trends in Ecology & Evolution, 2023)

Diet effects on longevity, heat tolerance, lipid peroxidation and mitochondrial membrane potential in Daphnia - Taraysha D. Moore; Dominik Martin-Creuzburg; Lev Y. Yampolsky (Oecologia, 2023)

Eddy and tidal driven basal melting of the Totten and Moscow University ice shelves - Yuwei Xia; David E. Gwyther; Ben Galton-Fenzi; Eva A. Cougnon; Alexander D. Fraser; John C. Moore (Frontiers in Marine Science, 2023)
The mass loss from the neighboring Totten and Moscow University ice shelves is accelerating and may raise global sea levels in coming centuries. Totten Glacier is mostly based on bedrock below sea level, and so is vulnerable to warm water intrusion reducing its ice shelf buttressing. The mechanisms driving the ocean forced sub-ice-shelf melting remains to be further explored. In this study, we simulate oceanic-driven ice shelf melting of the Totten (TIS) and Moscow University ice shelves (MUIS) using a high spatiotemporal resolution model that resolves both eddy and tidal processes. We selected the year 2014 as representative of the period 1992 to 2017 to investigate how basal melting varies on spatial and temporal scales. We apply the wavelet coherence method to investigate the interactions between the two ice shelves in time-frequency space and hence estimate the contributions from tidal (<1.5 days) and eddy (2-35 days) components of the ocean heat transport to the basal melting of each ice shelf. In our simulation, the 2014 mean basal melt rate for TIS is 6.7 m yr -1 (42 Gt yr -1 ) and 9.7 m yr -1 (52 Gt yr -1 ) for MUIS. We find high wavelet coherence in the eddy dominated frequency band between the two ice shelves over almost the whole year. The wavelet coherence along five transects across the ice shelves suggests that TIS basal melting is dominated by eddy processes, while MUIS basal melting is dominated by tidal processes. The eddy-dominated basal melt for TIS is probably due to the large and convoluted bathymetric gradients beneath the ice shelf, weakening higher frequency tidal mode transport. This illustrates the key role of accurate bathymetric data plays in simulating on-going and future evolution of these important ice shelves.

Quantifying the relative influence of coastal foredune growth factors on the U.S. Mid-Atlantic Coast using field observations and the process-based numerical model Windsurf - Paige A. Hovenga; Peter Ruggiero; Michael Itzkin; Katya R. Jay; Laura Moore; Sally D. Hacker (Coastal Engineering, 2023)

Exposure and behavioral responses of tagged beluga whales ( Delphinapterus leucas ) to ships in the Pacific Arctic - Morgan J. Martin; William D. Halliday; Luke Storrie; John J. Citta; Jackie Dawson; Nigel E. Hussey; Francis Juanes; Lisa L. Loseto; Shannon A. MacPhee; Lisa Moore; Adrian Nicoll; Gregory O'Corry‐Crowe; et al. (Marine Mammal Science, 2023)
Arctic marine mammals face a multitude of challenges linked to climate change, including increasing anthropogenic noise from ship traffic. The beluga whale ( Delphinapterus leucas ), a predominately Arctic endemic cetacean, relies heavily on acoustic communication, with documented overlap between their vocalizations and hearing range and ship noise. Some belugas migrate through areas with the highest levels of ship traffic in the Pacific Arctic and exposure to ship noise is highly probable. Here, we document the responses of nine satellite‐tagged Eastern Beaufort Sea belugas to encounters with ships in the Beaufort, Chukchi, and Bering Seas during July–December 2018. We report 177 occasions when ships were within 125 km of tagged belugas and quantified changes in lateral and vertical movements to investigate individual behavioral responses to ship approaches within 50 km ( n = 23). Belugas' swim speed was negatively correlated with ship distance, showing possible changes in swim speed up to 79 km away. Changes in lateral and vertical movements, indicating disruption of behavior, were observed when some ships passed within 50 km. These findings corroborate previous studies that have shown behavioral responses of belugas to ships at distances far beyond visual range, implying belugas react to low‐amplitude ship noise near ambient levels.

Residual correlation and ensemble modelling to improve crop and grassland models - Renáta Sándor; Fiona Ehrhardt; Peter Grace; Sylvie Recous; Pete Smith; Val Snow; Jean-François Soussana; Bruno Basso; Arti Bhatia; Lorenzo Brilli; Jordi Doltra; Christopher D. Dorich; et al. (Environmental Modelling & Software, 2023)

Aqueous sulfate contributions in terrestrial basaltic catchments: Implications for understanding sulfate sources and transport in Meridiani Planum, Mars - Rhianna D. Moore; Anna Szynkiewicz (Icarus, 2023)

Health Literacy Correlates to HPV Vaccination Among US Adults Ages 27–45 - Annalynn M. Galvin; Ashvita Garg; Stacey B. Griner; Jonathan D. Moore; Erika L. Thompson (Journal of Cancer Education, 2023)

The National Conference on Health Disparities Student Research Forum - Marvella E. Ford; Angela M. Malek; Erica Martino; Latecia Abraham-Hilaire; Oluwole Ariyo; Dana Burshell; Gloria Callwood; Laura Campbell; Kimberly Cannady; Courtney Chavis; Brittney Crawford; Andie Edwards; et al. (Journal of Cancer Education, 2023)
The annual National Conference on Health Disparities (NCHD) was launched in 2000. It unites health professionals, researchers, community leaders, and government officials, and is a catalyzing force in developing policies, research interventions, and programs that address prevention, social determinants, health disparities, and health equity. The NCHD Student Research Forum (SRF) was established in 2011 at the Medical University of South Carolina to build high-quality biomedical research presentation capacity in primarily underrepresented undergraduate and graduate/professional students. This paper describes the unique research training and professional development aspects of the NCHD SRF. These include guidance in abstract development, a webinar on presentation techniques and methods, a vibrant student-centric conference, and professional development workshops on finding a mentor and locating scholarship/fellowship funding, networking, and strategies for handling ethical issues in research with mentors. Between 2011 and 2018, 400 undergraduate and graduate/professional students participated in the NCHD SRF. Most students were women (80.5%). Approximately half were African American or black (52.3%), 18.0% were white, and 21.3% were of Hispanic/Latinx ethnicity. The NCHD SRF is unique in several ways. First, it provides detailed instructions on developing a scientific abstract, including content area examples. Second, it establishes a mandatory pre-conference training webinar demonstrating how to prepare a scientific poster. Third, it works with the research mentors, faculty advisors, department chairs, and deans to help identify potential sources of travel funding for students with accepted abstracts. These features make the NCHD SRF different from many other conferences focused on students’ scientific presentations.

Long‐distance migration is a major factor driving local adaptation at continental scale in Coho salmon - Quentin Rougemont; Amanda Xuereb; Xavier Dallaire; Jean‐Sébastien Moore; Eric Normandeau; Alysse Perreault‐Payette; Bérénice Bougas; Eric B. Rondeau; Ruth E. Withler; Donald M. Van Doornik; Penelope A. Crane; Kerry A. Naish; et al. (Molecular Ecology, 2023)
Inferring the genomic basis of local adaptation is a long‐standing goal of evolutionary biology. Beyond its fundamental evolutionary implications, such knowledge can guide conservation decisions for populations of conservation and management concern. Here, we investigated the genomic basis of local adaptation in the Coho salmon ( Oncorhynchus kisutch ) across its entire North American range. We hypothesized that extensive spatial variation in environmental conditions and the species’ homing behaviour may promote the establishment of local adaptation. We genotyped 7829 individuals representing 217 sampling locations at more than 100,000 high‐quality RADseq loci to investigate how recombination might affect the detection of loci putatively under selection and took advantage of the precise description of the demographic history of the species from our previous work to draw accurate population genomic inferences about local adaptation. The results indicated that genetic differentiation scans and genetic–environment association analyses were both significantly affected by variation in recombination rate as low recombination regions displayed an increased number of outliers. By taking these confounding factors into consideration, we revealed that migration distance was the primary selective factor driving local adaptation and partial parallel divergence among distant populations. Moreover, we identified several candidate single nucleotide polymorphisms associated with long‐distance migration and altitude including a gene known to be involved in adaptation to altitude in other species. The evolutionary implications of our findings are discussed along with conservation applications.

Carbon as a key driver of super-reduced explosive volcanism on Mercury: Evidence from graphite-melt smelting experiments - Kayla Iacovino; Francis M. McCubbin; Kathleen E. Vander Kaaden; Joanna Clark; Axel Wittmann; Ryan S. Jakubek; Gordon M. Moore; Marc D. Fries; Doug Archer; Jeremy W. Boyce (Earth and Planetary Science Letters, 2023)

Dementia in Convolutional Neural Networks: Using Deep Learning Models to Simulate Neurodegeneration of the Visual System - Jasmine A. Moore; Anup Tuladhar; Zahinoor Ismail; Pauline Mouches; Matthias Wilms; Nils D. Forkert (Neuroinformatics, 2023)

Silicon fertilisation affects morphological and immune defences of an insect pest and enhances plant compensatory growth - Tarikul Islam; Ben D. Moore; Scott N. Johnson (Journal of Pest Science, 2023)
Herbivorous insects have evolved various anti-predator defences, including morphological, behavioural, and immune defences, which can make biocontrol of herbivorous pests challenging. Silicon (Si) accumulation in plants is a potent physical defence against mandibulate insects. However, it remains uncertain how Si affects the anti-predator defences of insect herbivores and plant defences following herbivory. We grew the model grass, Brachypodium distachyon , hydroponically with (+Si) or without (–Si) Si and investigated the plant-mediated effects of Si on the anti-predator defences of the cotton bollworm, Helicoverpa armigera , integrating morphological (i.e. integument resistance and thickness), behavioural, and immune defences. We also examined the effects of Si on plant compensatory growth and leaf trichome production. Larval growth, leaf consumption, and integument resistance were lower when feeding on +Si plants compared to when feeding on –Si plants. Larval integument thickness, defensive behaviours, haemocyte density, and lysozyme-like activity in the haemolymph were unaffected by Si. Larvae fed on +Si plants had higher haemolymph phenoloxidase (PO) and total-PO activities than larvae fed on –Si plants, although this did not enhance the melanisation response of larvae. Furthermore, Si supplies increased plant compensation for herbivory and constitutive trichome production, whereas herbivory induced trichome production only on –Si plants. We provide the first evidence for plant-mediated effects of Si on anti-predator defences of an insect herbivore. We suggest that the lower integument resistance of larvae when feeding on Si-supplemented plants could contribute to their vulnerability to natural enemies and that high PO activity may impose fitness costs (e.g. delayed development).

Intrinsic and extrinsic factors interact during development to influence telomere length in a long‐lived reptile - Junsoo Bae; Emily M. Bertucci; Samantha L. Bock; Matthew D. Hale; Jameel Moore; Phil M. Wilkinson; Thomas R. Rainwater; John A. Bowden; Therese Koal; Hai PhamTuan; Benjamin B. Parrott (Molecular Ecology, 2022)
The mechanisms connecting environmental conditions to plasticity in biological aging trajectories are fundamental to understanding individual variation in functional traits and life history. Recent findings suggest that telomere biology is especially dynamic during early life stages and has long‐term consequences for subsequent reproduction and survival. However, our current understanding is mostly derived from studies investigating ecological and anthropogenic factors separately, leaving the effects of complex environmental interactions unresolved. American alligators ( Alligator mississippiensis ) are long‐lived apex predators that rely on incubation temperature during a discrete period during development and endocrine cues to determine sex, making them especially vulnerable to current climatic variability and exposure to anthropogenic contaminants interfering with hormone function. Here, we combine field studies with a factorial design to understand how the developmental environment, along with intrinsic biological variation contribute to persistent telomere variation. We found that exposure to a common endocrine disrupting contaminant, DDE, affects telomere length, but that the directionality is highly dependent upon incubation temperature. Variation in hatchling growth, underlies a strong clutch effect. We also assess concentrations of a panel of glucocorticoid hormones and find that contaminant exposure elicits an increase in circulating glucocorticoids. Consistent with emerging evidence linking stress and aging trajectories, GC levels also appear to trend with shorter telomere length. Thus, we add support for a mechanistic link between contaminants and glucocorticoid signalling, which interacts with ecological aspects of the developmental environment to alter telomere dynamics.

Hyporthodus griseofasciatus (Perciformes: Epinephelidae), a new species of deep‐water grouper from the west coast of Australia - Glenn I. Moore; Corey B. Wakefield; Joseph D. DiBattista; Stephen J. Newman (Journal of Fish Biology, 2022)
A new species of deep‐water epinephelid fish is described from the west coast of Australia based on 14 specimens, 99–595 mm standard length. Hyporthodus griseofasciatus sp. nov. is endemic to Western Australia from Barrow Island to Two Peoples Bay in depths of 76–470 m. It has a series of eight grey bands alternating with eight brown bands along the body and the soft dorsal, soft anal and caudal fin margins are pale cream to white. It is distinguished from its nearest congener, H. ergastularius , by the presence of a star‐like pattern of radiating lines on the head versus an overall brownish colour in the latter as well as significant differences in the quantitative analyses of 25 morphological characters. The two species have allopatric distributions on either side of the Australian continent. H. griseofasciatus is distinguished from H. octofasciatus by several grey bands being distinctly narrower than other grey bands ( vs. all grey bands subequal in the latter) and the presence of broad white margins on the dorsal, caudal and anal fins ( vs. narrow or absent in the latter). Some scale counts appear to also differ. Analyses of mitochondrial cytochrome oxidase subunit 1 sequences revealed reciprocally monophyletic clades with fixed differences and genetic distances typical of recently diverged species of fishes.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Amplifying actions for food system transformation: insights from the Stockholm region - David P. M. Lam; Amanda Jiménez-Aceituno; Leonie Guerrero Lara; My M. Sellberg; Albert V. Norström; Michele-Lee Moore; Garry D. Peterson; Per Olsson (Sustainability Science, 2022)
Food is essential to people and is one of the main ways in which people are connected to the world’s ecosystems. However, food systems often cause ecosystem degradation and produce ill-health, which has generated increasing calls to transform food systems to be more sustainable. The Swedish food system is currently undergoing substantial change. A varied set of local actors have created alternative sustainability initiatives that enact new ways of doing, thinking, and organizing. These actors can increase the transformative impact of their initiatives through multiple actions and a variety of amplification processes. We analyzed the actions adopted by 29 food initiatives active in the Stockholm region using information available online. We conducted 11 interviews to better understand the amplification processes of speeding up (i.e., accelerating impact) , scaling up (i.e., influencing higher institutional levels), and scaling deep (i.e., changing values and mind-sets). Our results indicated that the initiatives mainly seek to stabilize and grow their impact while changing the awareness, values, and mind-sets of people concerning the food they consume ( scaling deep ). However, these approaches raise new questions about whether these actions subvert or reinforce current unsustainable and inequitable system dynamics. We suggest there are distinct steps that local and regional governments could take to support these local actors via collaborations with coordinated forms of initiatives, and fostering changes at the municipality level, but these steps require ongoing, adaptive approaches given the highly complex nature of transformative change and the risks of reinforcing current system dynamics.

Characterizing Exposure to Head Acceleration Events in Youth Football Using an Instrumented Mouthpiece - Madison E. Marks; Ty D. Holcomb; N. Stewart Pritchard; Logan E. Miller; Mark A. Espeland; Christopher M. Miles; Justin B. Moore; Kristie L. Foley; Joel D. Stitzel; Jillian E. Urban (Annals of Biomedical Engineering, 2022)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Acute tryptophan depletion alters affective touch perception - Paula D. Trotter; Sharon A. Smith; David J. Moore; Noreen O’Sullivan; Martyn M. McFarquhar; Francis P. McGlone; Susannah C. Walker (Psychopharmacology, 2022)
Rationale Affiliative tactile interactions help regulate physiological arousal and confer resilience to acute and chronic stress. C-tactile afferents (CTs) are a population of unmyelinated, low threshold mechanosensitive cutaneous nerve fibres which respond optimally to a low force stimulus, moving at between 1 and 10 cm/s. As CT firing frequencies correlate positively with subjective ratings of touch pleasantness, they are hypothesised to form the first stage of encoding affiliative tactile interactions. Serotonin is a key modulator of social responses with known effects on bonding. Objectives The aim of the present study was to determine the effect of acutely lowering central serotonin levels on perceptions of CT-targeted affective touch. Methods In a double blind, placebo-controlled design, the effect of acute tryptophan depletion (ATD) on 25 female participants’ ratings of directly and vicariously experienced touch was investigated. Psychophysical techniques were used to deliver dynamic tactile stimuli; some velocities were targeted to optimally activate CTs (1–10 cm/s), whereas other, faster and slower strokes fell outside the CT optimal range. Discriminative tactile function, cold pain threshold and tolerance were also measured. Results ATD significantly increased pleasantness ratings of both directly and vicariously experienced affective touch, increasing discrimination of the specific hedonic value of CT targeted velocities. While ATD had no effect on either tactile or cold pain thresholds, there was a trend for reduced tolerance to cold pain. Conclusions These findings are consistent with previous reports that depletion of central serotonin levels modulates neural and behavioural responsiveness to appetitive sensory signals.

The promise of automated machine learning for the genetic analysis of complex traits - Elisabetta Manduchi; Joseph D. Romano; Jason H. Moore (Human Genetics, 2022)
The genetic analysis of complex traits has been dominated by parametric statistical methods due to their theoretical properties, ease of use, computational efficiency, and intuitive interpretation. However, there are likely to be patterns arising from complex genetic architectures which are more easily detected and modeled using machine learning methods. Unfortunately, selecting the right machine learning algorithm and tuning its hyperparameters can be daunting for experts and non-experts alike. The goal of automated machine learning (AutoML) is to let a computer algorithm identify the right algorithms and hyperparameters thus taking the guesswork out of the optimization process. We review the promises and challenges of AutoML for the genetic analysis of complex traits and give an overview of several approaches and some example applications to omics data. It is our hope that this review will motivate studies to develop and evaluate novel AutoML methods and software in the genetics and genomics space. The promise of AutoML is to enable anyone, regardless of training or expertise, to apply machine learning as part of their genetic analysis strategy.

Characterization of the juvenile koala gut microbiome across wild populations - Michaela D. J. Blyton; Rochelle M. Soo; Philip Hugenholtz; Ben D. Moore (Environmental Microbiology, 2022)
Summary In this study we compared the faecal microbiomes of wild joey koalas ( Phascolarctos cinereus ) to those of adults, including their mothers, to establish whether gut microbiome maturation and inheritance in the wild is comparable to that seen in captivity. Our findings suggest that joey koala microbiomes slowly shift towards an adult assemblage between 6 and 12 months of age, as the microbiomes of 9‐month‐old joeys were more similar to those of adults than those of 7‐month‐olds, but still distinct. At the phylum level, differences between joeys and adults were broadly consistent with those in captivity, with Firmicutes increasing in relative abundance over the joeys' development and Proteobacteria decreasing. Of the fibre‐degrading genes that increased in abundance over the development of captive joeys, those involved in hemicellulose and cellulose degradation, but not pectin degradation, were also generally found in higher abundance in adult wild koalas compared to 7‐month‐olds. Greater maternal inheritance of the faecal microbiome was seen in wild than in captive koalas, presumably due to the more solitary nature of wild koalas. This strong maternal inheritance of the gut microbiome could contribute to the development of localized differences in microbiome composition, population health and diet through spatial clustering of relatives.

Evolutionary interactions between thermal ecology and sexual selection - Noah T. Leith; Kasey D. Fowler‐Finn; Michael P. Moore (Ecology Letters, 2022)
Thermal ecology and mate competition are both pervasive features of ecological adaptation. A surge of recent work has uncovered the diversity of ways in which temperature affects mating interactions and sexual selection. However, the potential for thermal biology and reproductive ecology to evolve together as organisms adapt to their thermal environment has been underappreciated. Here, we develop a series of hypotheses regarding (1) not only how thermal ecology affects mating system dynamics, but also how mating dynamics can generate selection on thermal traits; and (2) how the thermal consequences of mate competition favour the reciprocal co‐adaptation of thermal biology and sexual traits. We discuss our hypotheses in the context of both pre‐copulatory and post‐copulatory processes. We also call for future work integrating experimental and phylogenetic comparative approaches to understand evolutionary feedbacks between thermal ecology and sexual selection. Overall, studying reciprocal feedbacks between thermal ecology and sexual selection may be necessary to understand how organisms have adapted to the environments of the past and could persist in the environments of the future.

Predicting wetland occurrence, main hydrogeomorphic type and vulnerability in the predominantly arid to semi-arid interior of the Western Cape, South Africa - D. C. Kotze; N. A. Rivers-Moore; N. Job; M. Grenfell (Wetlands Ecology and Management, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Rastogi; Sunny Nguyen; et al. (GeroScience, 2022)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

High-temperature oxidation of proximal basaltic pyroclasts, 1886 Tarawera, New Zealand - Hannah C. Moore; Rebecca J. Carey; Bruce F. Houghton; Martin Jutzeler; James D. L. White (Bulletin of Volcanology, 2022)
Microlite crystallization in erupting basalt can occur in the conduit, in flight, or in situ after deposition. Distinguishing the products of primary versus secondary (post-fragmentation) crystallization can be challenging in near-vent environments, but is vital for interpreting shallow conduit conditions from pyroclast textures. Here, we examine pyroclasts of the 1886 basaltic Plinian eruption of Tarawera volcano, New Zealand, to assess the roles of primary versus secondary crystallization of microlites. Lapilli and ash were selected from (a) an ultra-proximal section (T47), < 100 m from vent, which is dominated by pyroclasts derived from the Plinian jet and column margin, and (b) a medial fall deposit section (T43), 2.5 km from the fissure, which contains products from the umbrella cloud. Strong contrasts in pyroclast groundmass crystallinities exist between sections, from near-holocrystalline (90–97% void-free corrected; VFC) in T47 pyroclasts to highly crystalline (77–83% VFC) in T43 pyroclasts. Subhedral-euhedral Fe–Ti microlites (< 3 μm) are ubiquitous and abundant in T47 pyroclasts, whereas they are virtually absent in T43 pyroclasts. Olivine is present in both T47 and T43 pyroclasts but evidence of its subsolidus transformation is only seen in T47 clasts, whereas in T43 clasts olivine is fresh. Near-complete crystallization of the groundmass and subsolidus transformation of olivine in the ultraproximal T47 clasts are evidence that post-depositional modification of primary pyroclast textures occurred in ultra-proximal environments at Tarawera as a response to high residual temperatures and oxidizing conditions, aided by short transport times of relatively coarse ejecta at high accumulation rates, likely supplemented by intense vent-derived heat. Ultra-proximal basaltic eruption products can continue to crystallize after deposition and are thus unlikely to be faithful indictors of shallow conduit magmatic processes; we recommend the use of medial and distal products instead.

Cover and density of southwestern ponderosa pine understory plants in permanent chart quadrats (2002–2020) - Margaret M. Moore; Jeffrey S. Jenness; Daniel C. Laughlin; Robert T. Strahan; Jonathan D. Bakker; Helen E. Dowling; Judith D. Springer (Ecology, 2022)
This data set consists of 101 permanent 1 m × 1 m (1‐m 2 ) quadrats located within southwestern ponderosa pine ecosystems near Flagstaff, Arizona, USA. Individual plants in these quadrats were identified and mapped annually for 19 years (2002–2020). The original chart quadrats were established between 1912 and 1927 to determine the effects of domestic livestock grazing on herbaceous plants and pine seedlings. Today these data provide opportunities to examine the effects of climate and land‐use change on plant demography, population dynamics, and community processes. We provide the following data and data formats: (1) digitized maps of all plant locations in shapefile and geodatabase format, (2) shapefiles showing annual locations of each individual plant species, (3) annual maps of each quadrat in TIFF and PDF format, (4) annual basal area of each species per quadrat for species mapped as polygons, (5) tabular representation of polygon areas and centroid locations for plant species mapped as polygons, (6) tabular representation of point locations for plant species mapped as points, (7) plot‐scale 20 m × 20 m overstory tree canopy cover, tree basal area, parent material, and elevation, (8) quadrat‐scale information (e.g., quadrat site and number, coordinates in UTM Zone 12 and latitude/longitude, and descriptive comments for each quadrat), (9) plant species list, (10) summary of plant species observed in each quadrat, (11) summary of quadrats mapped by site and year, and (12) data formatted for use in Integral Projection Models (IPM) and plant population analyses. There are no copyright restrictions; please cite this paper and the associated data set when data are used in publications.

A pathogenic deletion in Forkhead Box L1 (FOXL1) identifies the first otosclerosis (OTSC) gene - Nelly Abdelfatah; Ahmed A. Mostafa; Curtis R. French; Lance P. Doucette; Cindy Penney; Matthew B. Lucas; Anne Griffin; Valerie Booth; Christopher Rowley; Jessica E. Besaw; Lisbeth Tranebjærg; Nanna Dahl Rendtorff; et al. (Human Genetics, 2022)
Otosclerosis is a bone disorder of the otic capsule and common form of late-onset hearing impairment. Considered a complex disease, little is known about its pathogenesis. Over the past 20 years, ten autosomal dominant loci ( OTSC1-10 ) have been mapped but no genes identified. Herein, we map a new OTSC locus to a 9.96 Mb region within the FOX gene cluster on 16q24.1 and identify a 15 bp coding deletion in Forkhead Box L1 co-segregating with otosclerosis in a Caucasian family. Pre-operative phenotype ranges from moderate to severe hearing loss to profound sensorineural loss requiring a cochlear implant. Mutant FOXL1 is both transcribed and translated and correctly locates to the cell nucleus. However, the deletion of 5 residues in the C-terminus of mutant FOXL1 causes a complete loss of transcriptional activity due to loss of secondary (alpha helix) structure. FOXL1 (rs764026385) was identified in a second unrelated case on a shared background. We conclude that FOXL1 (rs764026385) is pathogenic and causes autosomal dominant otosclerosis and propose a key inhibitory role for wildtype Foxl1 in bone remodelling in the otic capsule. New insights into the molecular pathology of otosclerosis from this study provide molecular targets for non-invasive therapeutic interventions.

Nutrient identity modifies the destabilising effects of eutrophication in grasslands - Oliver Carroll; Evan Batzer; Siddharth Bharath; Elizabeth T. Borer; Sofía Campana; Ellen Esch; Yann Hautier; Timothy Ohlert; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Lori Biederman; et al. (Ecology Letters, 2022)
Nutrient enrichment can simultaneously increase and destabilise plant biomass production, with co‐limitation by multiple nutrients potentially intensifying these effects. Here, we test how factorial additions of nitrogen (N), phosphorus (P) and potassium with essential nutrients (K+) affect the stability (mean/standard deviation) of aboveground biomass in 34 grasslands over 7 years. Destabilisation with fertilisation was prevalent but was driven by single nutrients, not synergistic nutrient interactions. On average, N‐based treatments increased mean biomass production by 21–51% but increased its standard deviation by 40–68% and so consistently reduced stability. Adding P increased interannual variability and reduced stability without altering mean biomass, while K+ had no general effects. Declines in stability were largest in the most nutrient‐limited grasslands, or where nutrients reduced species richness or intensified species synchrony. We show that nutrients can differentially impact the stability of biomass production, with N and P in particular disproportionately increasing its interannual variability.

Correction to: Plant invasion impacts on fungal community structure and function depend on soil warming and nitrogen enrichment - M. A. Anthony; K. A. Stinson; J. A. M. Moore; S. D. Frey (Oecologia, 2022)

Fate of thiamethoxam from treated seeds in mesocosms and response of aquatic invertebrate communities - A. K. Vanderpont; C. Lobson; Z. Lu; K. Luong; M. Arentsen; T. Vera; D. Moore; M. S. White; R. S. Prosser; C. S. Wong; M. L. Hanson (Ecotoxicology, 2022)

CSF markers of AD-related pathology relate specifically to memory impairment in older people with HIV: a pilot study - Judith D. Lobo; David J. Moore; Mark W. Bondi; Virawudh Soontornniyomkij; Benchawanna Soontornniyomkij; Ben Gouaux; Cristian L. Achim; Ronald J. Ellis; Erin E. Sundermann (Journal of NeuroVirology, 2022)

Birds of a Feather Eat Plastic Together: High Levels of Plastic Ingestion in Great Shearwater Adults and Juveniles Across Their Annual Migratory Cycle - Anna R. Robuck; Christine A. Hudak; Lindsay Agvent; Gwenyth Emery; Peter G. Ryan; Vonica Perold; Kevin D. Powers; Johanna Pedersen; Michael A. Thompson; Justin J. Suca; Michael J. Moore; Craig A. Harms; et al. (Frontiers in Marine Science, 2022)
Limited work to date has examined plastic ingestion in highly migratory seabirds like Great Shearwaters ( Ardenna gravis ) across their entire migratory range. We examined 217 Great Shearwaters obtained from 2008–2019 at multiple locations spanning their yearly migration cycle across the Northwest and South Atlantic to assess accumulation of ingested plastic as well as trends over time and between locations. A total of 2328 plastic fragments were documented in the ventriculus portion of the gastrointestinal tract, with an average of 9 plastic fragments per bird. The mass, count, and frequency of plastic occurrence (FO) varied by location, with higher plastic burdens but lower FO in South Atlantic adults and chicks from the breeding colonies. No fragments of the same size or morphology were found in the primary forage fish prey, the Sand Lance ( Ammodytes spp., n = 202) that supports Great Shearwaters in Massachusetts Bay, United States, suggesting the birds directly ingest the bulk of their plastic loads rather than accumulating via trophic transfer. Fourier-transform infrared spectroscopy indicated that low- and high-density polyethylene were the most common polymers ingested, within all years and locations. Individuals from the South Atlantic contained a higher proportion of larger plastic items and fragments compared to analogous life stages in the NW Atlantic, possibly due to increased use of remote, pelagic areas subject to reduced inputs of smaller, more diverse, and potentially less buoyant plastics found adjacent to coastal margins. Different signatures of polymer type, size, and category between similar life stages at different locations suggests rapid turnover of ingested plastics commensurate with migratory stage and location, though more empirical evidence is needed to ground-truth this hypothesis. This work is the first to comprehensively measure the accumulation of ingested plastics by Great Shearwaters over the last decade and across multiple locations spanning their yearly trans-equatorial migration cycle and underscores their utility as sentinels of plastic pollution in Atlantic ecosystems.

Aflatoxin B 1 in imported cinnamon consumed in the Yazd province of Iran - Vahid Safavizadeh; Carlos Augusto Fernandes de Oliveira; Zahra Nekoukar; Masoud Aman Mohammadi; Gianluca Tognon; Matthew D. Moore (Food Additives & Contaminants Part B-Surveillance, 2022)

Silicon suppresses a ubiquitous mite herbivore and promotes natural enemy attraction by altering plant volatile blends - Tarikul Islam; Ben D. Moore; Scott N. Johnson (Journal of Pest Science, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Passive-Sampler-Based Bioavailability Assessment of PCB Congeners Associated with Aroclor-Containing Paint Chips in the Presence of Sediment - Guilherme R. Lotufo; Philip T. Gidley; Andrew D. McQueen; David W. Moore; Deborah A. Edwards; Jeffery Hardenstine; Allen D. Uhler (Archives of Environmental Contamination and Toxicology, 2022)
This is the first investigation of the bioavailability of PCBs associated with paint chips (PC) dispersed in sediment. Bioavailability of PCB-containing PC in sediment was measured using ex situ polyethylene passive samplers (PS) and compared to that of PCBs from field-collected sediments. PC were mixed in freshwater sediment from a relatively uncontaminated site with no known PCB contamination sources and from a contaminated site with non-paint PCB sources. PC

Marine and freshwater regime changes impact a community of migratory Pacific salmonids in decline - Kyle L. Wilson; Colin J. Bailey; Trevor D. Davies; Jonathan W. Moore (Global Change Biology, 2022)
Marine and freshwater ecosystems are increasingly at risk of large and cascading changes from multiple human activities (termed “regime shifts”), which can impact population productivity, resilience, and ecosystem structure. Pacific salmon exhibit persistent and large fluctuations in their population dynamics driven by combinations of intrinsic (e.g., density dependence) and extrinsic factors (e.g., ecosystem changes, species interactions). In recent years, many Pacific salmon have declined due to regime shifts but clear understanding of the processes driving these changes remains elusive. Here, we unpacked the role of density dependence, ecosystem trends, and stochasticity on productivity regimes for a community of five anadromous Pacific salmonids (Steelhead, Coho Salmon, Pink Salmon, Dolly Varden, and Coastal Cutthroat Trout) across a rich 40‐year time‐series. We used a Bayesian multivariate state‐space model to examine whether productivity shifts had similarly occurred across the community and explored marine or freshwater changes associated with those shifts. Overall, we identified three productivity regimes: an early regime (1976–1990), a compensatory regime (1991–2009), and a declining regime (since 2010) where large declines were observed for Steelhead, Dolly Varden, and Cutthroat Trout, intermediate declines in Coho and no change in Pink Salmon. These regime changes were associated with multiple cumulative effects across the salmon life cycle. For example, increased seal densities and ocean competition were associated with lower adult marine survival in Steelhead. Watershed logging also intensified over the past 40 years and was associated with (all else equal) ≥97% declines in freshwater productivity for Steelhead, Cutthroat, and Coho. For Steelhead, marine and freshwater dynamics played approximately equal roles in explaining trends in total productivity. Collectively, these changing environments limited juvenile production and lowered future adult returns. These results reveal how changes in freshwater and marine environments can jointly shape population dynamics among ecological communities, like Pacific salmon, with cascading consequences to their resilience.

Maternal inheritance of the koala gut microbiome and its compositional and functional maturation during juvenile development - Michaela D.J. Blyton; Rochelle M. Soo; Philip Hugenholtz; Ben D. Moore (Environmental Microbiology, 2022)
Summary The acquisition and maturation of the gastrointestinal microbiome is a crucial aspect of mammalian development, particularly for specialist herbivores such as the koala ( Phascolarctos cinereus ). Joey koalas are thought to be inoculated with microorganisms by feeding on specialized maternal faeces (pap). We found that compared to faeces, pap has higher microbial density, higher microbial evenness and a higher proportion of rare taxa, which may facilitate the establishment of those taxa in joey koalas. We show that the microbiomes of captive joey koalas were on average more similar to those of their mothers than to other koalas, indicating strong maternal inheritance of the faecal microbiome, which can lead to intergenerational gut dysbiosis when the mother is ill. Directly after pap feeding, the joey koalas' microbiomes were enriched for milk‐associated bacteria including Bacteroides fragilis , suggesting a conserved role for this species across mammalian taxa. The joeys' microbiomes then changed slowly over 5 months to resemble those of adults by 1 year of age. The relative abundance of fibrolytic bacteria and genes involved in the degradation of plant cell walls also increased in the infants over this time, likely in response to an increased proportion of Eucalyptus leaves in their diets.

A first genetic assessment of the newly introduced Isle Royale gray wolves (Canis lupus) - Samuel D. Hervey; Linda Y. Rutledge; Brent R. Patterson; Mark C. Romanski; John A. Vucetich; Jerrold L. Belant; Dean E. Beyer; Seth A. Moore; Kristin E. Brzeski (Conservation Genetics, 2021)

Temporal rarity is a better predictor of local extinction risk than spatial rarity - Peter A. Wilfahrt; Ashley L. Asmus; Eric W. Seabloom; Jeremiah A. Henning; Peter Adler; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Lars A. Brudvig; Marc Cadotte; Pedro Daleo; Anu Eskelinen; et al. (Ecology, 2021)
Spatial rarity is often used to predict extinction risk, but rarity can also occur temporally. Perhaps more relevant in the context of global change is whether a species is core to a community (persistent) or transient (intermittently present), with transient species often susceptible to human activities that reduce niche space. Using 5–12 yr of data on 1,447 plant species from 49 grasslands on five continents, we show that local abundance and species persistence under ambient conditions are both effective predictors of local extinction risk following experimental exclusion of grazers or addition of nutrients; persistence was a more powerful predictor than local abundance. While perturbations increased the risk of exclusion for low persistence and abundance species, transient but abundant species were also highly likely to be excluded from a perturbed plot relative to ambient conditions. Moreover, low persistence and low abundance species that were not excluded from perturbed plots tended to have a modest increase in abundance following perturbance. Last, even core species with high abundances had large decreases in persistence and increased losses in perturbed plots, threatening the long‐term stability of these grasslands. Our results demonstrate that expanding the concept of rarity to include temporal dynamics, in addition to local abundance, more effectively predicts extinction risk in response to environmental change than either rarity axis predicts alone.

Anticipating and Adapting to the Future Impacts of Climate Change on the Health, Security and Welfare of Low Elevation Coastal Zone (LECZ) Communities in Southeastern USA - Thomas Allen; Joshua Behr; Anamaria Bukvic; Ryan S. D. Calder; Kiki Caruson; Charles Connor; Christopher D’Elia; David Dismukes; Robin Ersing; Rima Franklin; Jesse Goldstein; Jonathon Goodall; et al. (Journal of Marine Science and Engineering, 2021)
Low elevation coastal zones (LECZ) are extensive throughout the southeastern United States. LECZ communities are threatened by inundation from sea level rise, storm surge, wetland degradation, land subsidence, and hydrological flooding. Communication among scientists, stakeholders, policy makers and minority and poor residents must improve. We must predict processes spanning the ecological, physical, social, and health sciences. Communities need to address linkages of (1) human and socioeconomic vulnerabilities; (2) public health and safety; (3) economic concerns; (4) land loss; (5) wetland threats; and (6) coastal inundation. Essential capabilities must include a network to assemble and distribute data and model code to assess risk and its causes, support adaptive management, and improve the resiliency of communities. Better communication of information and understanding among residents and officials is essential. Here we review recent background literature on these matters and offer recommendations for integrating natural and social sciences. We advocate for a cyber-network of scientists, modelers, engineers, educators, and stakeholders from academia, federal state and local agencies, non-governmental organizations, residents, and the private sector. Our vision is to enhance future resilience of LECZ communities by offering approaches to mitigate hazards to human health, safety and welfare and reduce impacts to coastal residents and industries.

Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Ragosti; Sunny Nguyen; et al. (GeroScience, 2021)

Species loss due to nutrient addition increases with spatial scale in global grasslands - Eric W. Seabloom; Evan Batzer; Jonathan M. Chase; W. Stanley Harpole; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Isabel C. Barrio; Lori Biederman; Elizabeth H. Boughton; Miguel N. Bugalho; Maria C. Caldeira; et al. (Ecology Letters, 2021)
The effects of altered nutrient supplies and herbivore density on species diversity vary with spatial scale, because coexistence mechanisms are scale dependent. This scale dependence may alter the shape of the species–area relationship (SAR), which can be described by changes in species richness ( S ) as a power function of the sample area ( A ): S = cA z , where c and z are constants. We analysed the effects of experimental manipulations of nutrient supply and herbivore density on species richness across a range of scales (0.01–75 m 2 ) at 30 grasslands in 10 countries. We found that nutrient addition reduced the number of species that could co‐occur locally, indicated by the SAR intercepts (log c ), but did not affect the SAR slopes ( z ). As a result, proportional species loss due to nutrient enrichment was largely unchanged across sampling scales, whereas total species loss increased over threefold across our range of sampling scales.

Fine root dynamics across pantropical rainforest ecosystems - Walter Huaraca Huasco; Terhi Riutta; Cécile A. J. Girardin; Fernando Hancco Pacha; Beisit L. Puma Vilca; Sam Moore; Sami W. Rifai; Jhon del Aguila‐Pasquel; Alejandro Araujo Murakami; Renata Freitag; Alexandra C. Morel; Sheleme Demissie; et al. (Global Change Biology, 2021)
Fine roots constitute a significant component of the net primary productivity (NPP) of forest ecosystems but are much less studied than aboveground NPP. Comparisons across sites and regions are also hampered by inconsistent methodologies, especially in tropical areas. Here, we present a novel dataset of fine root biomass, productivity, residence time, and allocation in tropical old‐growth rainforest sites worldwide, measured using consistent methods, and examine how these variables are related to consistently determined soil and climatic characteristics. Our pantropical dataset spans intensive monitoring plots in lowland (wet, semi‐deciduous, and deciduous) and montane tropical forests in South America, Africa, and Southeast Asia ( n = 47). Large spatial variation in fine root dynamics was observed across montane and lowland forest types. In lowland forests, we found a strong positive linear relationship between fine root productivity and sand content, this relationship was even stronger when we considered the fractional allocation of total NPP to fine roots, demonstrating that understanding allocation adds explanatory power to understanding fine root productivity and total NPP. Fine root residence time was a function of multiple factors: soil sand content, soil pH, and maximum water deficit, with longest residence times in acidic, sandy, and water‐stressed soils. In tropical montane forests, on the other hand, a different set of relationships prevailed, highlighting the very different nature of montane and lowland forest biomes. Root productivity was a strong positive linear function of mean annual temperature, root residence time was a strong positive function of soil nitrogen content in montane forests, and lastly decreasing soil P content increased allocation of productivity to fine roots. In contrast to the lowlands, environmental conditions were a better predictor for fine root productivity than for fractional allocation of total NPP to fine roots, suggesting that root productivity is a particularly strong driver of NPP allocation in tropical mountain regions.

Single-Turnover Variable Chlorophyll Fluorescence as a Tool for Assessing Phytoplankton Photosynthesis and Primary Productivity: Opportunities, Caveats and Recommendations - Nina Schuback; Philippe D. Tortell; Ilana Berman-Frank; Douglas A. Campbell; Aurea Ciotti; Emilie Courtecuisse; Zachary K. Erickson; Tetsuichi Fujiki; Kimberly Halsey; Anna E. Hickman; Yannick Huot; Maxime Y. Gorbunov; et al. (Frontiers in Marine Science, 2021)
Phytoplankton photosynthetic physiology can be investigated through single-turnover variable chlorophyll fluorescence (ST-ChlF) approaches, which carry unique potential to autonomously collect data at high spatial and temporal resolution. Over the past decades, significant progress has been made in the development and application of ST-ChlF methods in aquatic ecosystems, and in the interpretation of the resulting observations. At the same time, however, an increasing number of sensor types, sampling protocols, and data processing algorithms have created confusion and uncertainty among potential users, with a growing divergence of practice among different research groups. In this review, we assist the existing and upcoming user community by providing an overview of current approaches and consensus recommendations for the use of ST-ChlF measurements to examine in-situ phytoplankton productivity and photo-physiology. We argue that a consistency of practice and adherence to basic operational and quality control standards is critical to ensuring data inter-comparability. Large datasets of inter-comparable and globally coherent ST-ChlF observations hold the potential to reveal large-scale patterns and trends in phytoplankton photo-physiology, photosynthetic rates and bottom-up controls on primary productivity. As such, they hold great potential to provide invaluable physiological observations on the scales relevant for the development and validation of ecosystem models and remote sensing algorithms.

Fundamental dietary specialisation explains differential use of resources within a koala population - Karen J. Marsh; Michaela D. J. Blyton; William J. Foley; Ben D. Moore (Oecologia, 2021)

Association between sexually selected traits and allelic distance in two unlinked MHC II loci in white-tailed deer (Odocoileus virginianus) - Natascha M. D. Ivy-Israel; Carolyn E. Moore; Tonia S. Schwartz; Todd D. Steury; Sarah Zohdy; Chad H. Newbolt; Stephen S. Ditchkoff (Evolutionary Ecology, 2021)

Fungal community structure and function shifts with atmospheric nitrogen deposition - Jessica A. M. Moore; Mark A. Anthony; Gregory J. Pec; Lidia K. Trocha; Artur Trzebny; Kevin M. Geyer; Linda T. A. van Diepen; Serita D. Frey (Global Change Biology, 2021)
Fungal decomposition of soil organic matter depends on soil nitrogen (N) availability. This ecosystem process is being jeopardized by changes in N inputs that have resulted from a tripling of atmospheric N deposition in the last century. Soil fungi are impacted by atmospheric N deposition due to higher N availability, as soils are acidified, or as micronutrients become increasingly limiting. Fungal communities that persist with chronic N deposition may be enriched with traits that enable them to tolerate environmental stress, which may trade‐off with traits enabling organic matter decomposition. We hypothesized that fungal communities would respond to N deposition by shifting community composition and functional gene abundances toward those that tolerate stress but are weak decomposers. We sampled soils at seven eastern US hardwood forests where ambient N deposition varied from 3.2 to 12.6 kg N ha −1 year −1 , five of which also have experimental plots where atmospheric N deposition was simulated through fertilizer application treatments (25–50 kg N ha −1 year −1 ). Fungal community and functional responses to fertilizer varied across the ambient N deposition gradient. Fungal biomass and richness increased with simulated N deposition at sites with low ambient deposition and decreased at sites with high ambient deposition. Fungal functional genes involved in hydrolysis of organic matter increased with ambient N deposition while genes involved in oxidation of organic matter decreased. One of four genes involved in generalized abiotic stress tolerance increased with ambient N deposition. In summary, we found that the divergent response to simulated N deposition depended on ambient N deposition levels. Fungal biomass, richness, and oxidative enzyme potential were reduced by N deposition where ambient N deposition was high suggesting fungal communities were pushed beyond an environmental stress threshold. Fungal community structure and function responses to N enrichment depended on ambient N deposition at a regional scale.

Vascular plant extinction in the continental United States and Canada - Wesley M. Knapp; Anne Frances; Reed Noss; Robert F. C. Naczi; Alan Weakley; George D. Gann; Bruce G. Baldwin; James Miller; Patrick McIntyre; Brent D. Mishler; Gerry Moore; Richard G. Olmstead; et al. (Conservation Biology, 2021)
Extinction rates are expected to increase during the Anthropocene. Current extinction rates of plants and many animals remain unknown. We quantified extinctions among the vascular flora of the continental United States and Canada since European settlement. We compiled data on apparently extinct species by querying plant conservation databases, searching the literature, and vetting the resulting list with botanical experts. Because taxonomic opinion varies widely, we developed an index of taxonomic uncertainty (ITU). The ITU ranges from A to F, with A indicating unanimous taxonomic recognition and F indicating taxonomic recognition by only a single author. The ITU allowed us to rigorously evaluate extinction rates. Our data suggest that 51 species and 14 infraspecific taxa, representing 33 families and 49 genera of vascular plants, have become extinct in our study area since European settlement. Seven of these taxa exist in cultivation but are extinct in the wild. Most extinctions occurred in the west, but this outcome may reflect the timing of botanical exploration relative to settlement. Sixty‐four percent of extinct plants were single‐site endemics, and many occurred outside recognized biodiversity hotspots. Given the paucity of plant surveys in many areas, particularly prior to European settlement, the actual extinction rate of vascular plants is undoubtedly much higher than indicated here.

Role of Sea Surface Microlayer Properties in Cloud Formation - Brianna N. Hendrickson; Sarah D. Brooks; Daniel C. O. Thornton; Richard H. Moore; Ewan Crosbie; Luke D. Ziemba; Craig A. Carlson; Nicholas Baetge; Jessica A. Mirrielees; Alyssa N. Alsante (Frontiers in Marine Science, 2021)
To date, the relative contribution of primary marine organic matter to the subset of atmospheric particles that nucleate cloud droplets is highly uncertain. Here, cloud condensation nuclei (CCN) measurements were conducted on aerosolized sea surface microlayer (SML) samples collected from the North Atlantic Ocean during the NASA North Atlantic Aerosols and Marine Ecosystems Study (NAAMES), κ values were predicted for three representative high molecular weight (HMW) organic components of marine aerosol: 6-glucose, humic acid, and ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO). The predicted κ values for pure organic aerosols varied by only ±0.01 across all of the organics chosen. For the desalted SML samples, calculations assuming an organic composition of entirely RuBisCO provided the closest predicted κ values for the desalted SML samples with a mean κ value of 0.53 ± 0.10. These results indicate that it is the sea salt in the SML which drives the cloud formation potential of marine aerosols. While the presence of organic material from the ocean surface waters may increase aerosol mass due to enrichment processes, cloud formation potential of mixed organic/salt primary marine aerosols will be slightly weakened or unchanged compared to sea spray aerosol.

Using search-constrained inverse distance weight modeling for near real-time riverine flood modeling: Harris County, Texas, USA before, during, and after Hurricane Harvey - Andrew S. Berens; Tess Palmer; Nina D. Dutton; Amy Lavery; Mark Moore (Natural Hazards, 2021)

Characterization of a bovine intestinal myofibroblast cell line and stimulation using phytoglycogen-based nanoparticles bound to inosine monophosphate - K. Jenik; T. N. Alkie; E. Moore; J. D. Dejong; L. E. J. Lee; S. J. DeWitte-Orr (In Vitro Cellular & Developmental Biology - Animal, 2021)

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

Spatial Heterogeneity of Surface Topography in Peatlands: Assessing Overwintering Habitat Availability for the Eastern Massasauga Rattlesnake - Chantel E. Markle; Taylor D. North; Lorna I. Harris; Paul A. Moore; James M. Waddington (Wetlands, 2020)

Plant invasion impacts on fungal community structure and function depend on soil warming and nitrogen enrichment - M. A. Anthony; K. A. Stinson; J. A. M. Moore; S. D. Frey (Oecologia, 2020)
The impacts of invasive species on biodiversity may be mitigated or exacerbated by abiotic environmental changes. Invasive plants can restructure soil fungal communities with important implications for native biodiversity and nutrient cycling, yet fungal responses to invasion may depend on numerous anthropogenic stressors. In this study, we experimentally invaded a long-term soil warming and simulated nitrogen deposition experiment with the widespread invasive plant Alliaria petiolata (garlic mustard) and tested the responses of soil fungal communities to invasion, abiotic factors, and their interaction. We focused on the phytotoxic garlic mustard because it suppresses native mycorrhizae across forests of North America. We found that invasion in combination with warming, but not under ambient conditions or elevated nitrogen, significantly reduced soil fungal biomass and ectomycorrhizal relative abundances and increased relative abundances of general soil saprotrophs and fungal genes encoding for hydrolytic enzymes. These results suggest that warming potentially exacerbates fungal responses to plant invasion. Soils collected from uninvaded and invaded plots across eight forests spanning a 4 °C temperature gradient further demonstrated that the magnitude of fungal responses to invasion was positively correlated with mean annual temperature. Our study is one of the first empirical tests to show that the impacts of invasion on fungal communities depends on additional anthropogenic pressures and were greater in concert with warming than under elevated nitrogen or ambient conditions.

Predicting biodiversity richness in rapidly changing landscapes: climate, low human pressure or protection as salvation? - David W. Macdonald; Luca Chiaverini; Helen M. Bothwell; Żaneta Kaszta; Eric Ash; Gilmoore Bolongon; Özgün Emre Can; Ahimsa Campos-Arceiz; Phan Channa; Gopalasamy Reuben Clements; Andrew J. Hearn; Laurie Hedges; et al. (Biodiversity and Conservation, 2020)
Rates of biodiversity loss in Southeast Asia are among the highest in the world, and the Indo-Burma and South-Central China Biodiversity Hotspots rank among the world’s most threatened. Developing robust multi-species conservation models is critical for stemming biodiversity loss both here and globally. We used a large and geographically extensive remote-camera survey and multi-scale, multivariate optimization species distribution modelling to investigate the factors driving biodiversity across these two adjoining biodiversity hotspots. Four major findings emerged from the work. (i) We identified clear spatial patterns of species richness, with two main biodiverse centres in the Thai-Malay Peninsula and in the mountainous region of Southwest China. (ii) Carnivores in particular, and large ungulates to a lesser degree, were the strongest indicators of species richness. (iii) Climate had the largest effect on biodiversity, followed by protected status and human footprint. (iv) Gap analysis between the biodiversity model and the current system of protected areas revealed that the majority of areas supporting the highest predicted biodiversity are not protected. Our results highlighted several key locations that should be prioritized for expanding the protected area network to maximize conservation effectiveness. We demonstrated the importance of switching from single-species to multi-species approaches to highlight areas of high priority for biodiversity conservation. In addition, since these areas mostly occur over multiple countries, we also advocate for a paradigmatic focus on transboundary conservation planning.

Global impacts of fertilization and herbivore removal on soil net nitrogen mineralization are modulated by local climate and soil properties - Anita C. Risch; Stefan Zimmermann; Barbara Moser; Martin Schütz; Frank Hagedorn; Jennifer Firn; Philip A. Fay; Peter B. Adler; Lori A. Biederman; John M. Blair; Elizabeth T. Borer; Arthur A. D. Broadbent; et al. (Global Change Biology, 2020)
Soil nitrogen (N) availability is critical for grassland functioning. However, human activities have increased the supply of biologically limiting nutrients, and changed the density and identity of mammalian herbivores. These anthropogenic changes may alter net soil N mineralization (soil net N min ), that is, the net balance between N mineralization and immobilization, which could severely impact grassland structure and functioning. Yet, to date, little is known about how fertilization and herbivore removal individually, or jointly, affect soil net N min across a wide range of grasslands that vary in soil and climatic properties. Here we collected data from 22 grasslands on five continents, all part of a globally replicated experiment, to assess how fertilization and herbivore removal affected potential (laboratory‐based) and realized (field‐based) soil net N min . Herbivore removal in the absence of fertilization did not alter potential and realized soil net N min . However, fertilization alone and in combination with herbivore removal consistently increased potential soil net N min. Realized soil net N min , in contrast, significantly decreased in fertilized plots where herbivores were removed. Treatment effects on potential and realized soil net N min were contingent on site‐specific soil and climatic properties. Fertilization effects on potential soil net N min were larger at sites with higher mean annual precipitation (MAP) and temperature of the wettest quarter (T.q.wet). Reciprocally, realized soil net N min declined most strongly with fertilization and herbivore removal at sites with lower MAP and higher T.q.wet. In summary, our findings show that anthropogenic nutrient enrichment, herbivore exclusion and alterations in future climatic conditions can negatively impact soil net N min across global grasslands under realistic field conditions. This is an important context‐dependent knowledge for grassland management worldwide.

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Multiple sources of internal calcium stores mediate ethanol-induced presynaptic inhibitory GABA release in the central nucleus of the amygdala in mice - Qiang Li; Rebecca C. Klein; Scott D. Moore (Psychopharmacology, 2020)

Utility of Kinetic and Kinematic Jumping and Landing Variables as Predictors of Injury Risk: A Systematic Review - Jason S. Pedley; Rhodri S. Lloyd; Paul J. Read; Isabel S. Moore; Mark De Ste Croix; Gregory D. Myer; Jon L. Oliver (Journal of Science in Sport and Exercise, 2020)
Purpose Jump-landing assessments provide a means to quantify an individual’s ability to attenuate ground reaction forces, generate lower limb explosive power and maintain joint alignment. In order to identify risk factors that can be targeted through appropriate training interventions, it is necessary to establish which (scalar) objective kinetic, kinematic, and performance measures are most associated with lower-extremity injury. Methods Online searches of MEDLINE, SCOPUS, EBSCOHost, SPORTDiscus and PubMed databases were completed for all articles published before March 2020 in accordance with PRISMA guidelines. Results 40 articles investigating nine jump-landing assessments were included in this review. The 79% of studies using drop jump ( n = 14) observed an association with future injury, while only 8% of countermovement jump studies ( n = 13) observed an association with injury risk. The 57% of studies using unilateral assessments found associations with risk of injury ( n = 14). Studies using performance measures (jump height/distance) as outcome measure were only associated with injury risk in 30% of cases. However, those using kinetic and/or kinematic analyses (knee abduction moment, knee valgus angle, knee separation distance, peak ground reaction force) found associations with injury in 89% of studies. Conclusion The landing element of jump-landing assessments appears to be superior for identifying individuals at greater risk of injury; likely due to a closer representation of the injury mechanism. Consequently, jump-landing assessments that involve attenuation of impact forces such as the drop jump appear most suited for this purpose but should involve assessment of frontal plane knee motion and ground reaction forces.

The Influence of Biological Maturity on Dynamic Force–Time Variables and Vaulting Performance in Young Female Gymnasts - Sylvia Moeskops; Jon L. Oliver; Paul J. Read; John B. Cronin; Gregory D. Myer; G. Gregory Haff; Isabel S. Moore; Rhodri S. Lloyd (Journal of Science in Sport and Exercise, 2020)
Purpose This cross-sectional study investigated dynamic force–time variables and vaulting performance in young female gymnasts of different maturity status. Methods 120 gymnasts aged 5–14 years were sub-divided into maturity groupings using percent of predicted adult height (%PAH) attained. Participants performed three jumping protocols, the squat jump (SJ), countermovement jump (CMJ) and drop jump (DJ), before completing straight jump vaults that were recorded using two-dimensional video. Results Jumping performance improved with biological maturity evidenced by the most mature gymnasts’ producing significantly more absolute force ( P < 0.05; all d > 0.78), impulse ( P < 0.05; all d > 0.75) and power ( P < 0.05; all d > 0.91) than the least mature group, resulting in the greater jump heights ( P < 0.05; all d > 0.70). While, no significant differences were observed in relative peak force across multiple tests, measures of relative peak power did significantly increase with maturity. Based upon regression analyses, maturation was found to influence vertical take-off velocity during vaulting, explaining 41% of the variance in each jumping protocol. Across all tests, the DJ was found to have the highest predictive ability of vaulting vertical take-off velocity, explaining 55% of the total variance. Conclusion Biological maturation impacts jump height and underpinning mechanical variables in young female gymnasts. Vaulting vertical take-off velocity appears to be influenced by maturation and various dynamic force–time variables, particularly those during DJ, which had the highest explained total variance.

Using structured eradication feasibility assessment to prioritize the management of new and emerging invasive alien species in Europe - Olaf Booy; Pete A. Robertson; Niall Moore; Jess Ward; Helen E. Roy; Tim Adriaens; Richard Shaw; Johan Van Valkenburg; Gabrielle Wyn; Sandro Bertolino; Olivier Blight; Etienne Branquart; et al. (Global Change Biology, 2020)
Prioritizing the management of invasive alien species (IAS) is of global importance and within Europe integral to the EU IAS regulation. To prioritize management effectively, the risks posed by IAS need to be assessed, but so too does the feasibility of their management. While the risk of IAS to the EU has been assessed, the feasibility of management has not. We assessed the feasibility of eradicating 60 new (not yet established) and 35 emerging (established with limited distribution) species that pose a threat to the EU, as identified by horizon scanning. The assessment was carried out by 34 experts in invasion management from across Europe, applying the Non‐Native Risk Management scheme to defined invasion scenarios and eradication strategies for each species, assessing the feasibility of eradication using seven key risk management criteria. Management priorities were identified by combining scores for risk (derived from horizon scanning) and feasibility of eradication. The results show eradication feasibility score and risk score were not correlated, indicating that risk management criteria evaluate different information than risk assessment. In all, 17 new species were identified as particularly high priorities for eradication should they establish in the future, whereas 14 emerging species were identified as priorities for eradication now. A number of species considered highest priority for eradication were terrestrial vertebrates, a group that has been the focus of a number of eradication attempts in Europe. However, eradication priorities also included a diverse range of other taxa (plants, invertebrates and fish) suggesting there is scope to broaden the taxonomic range of attempted eradication in Europe. We demonstrate that broad scale structured assessments of management feasibility can help prioritize IAS for management. Such frameworks are needed to support evidence‐based decision‐making.

Fear expression is reduced after acute and repeated nociceptin/orphanin FQ (NOP) receptor antagonism in rats: therapeutic implications for traumatic stress exposure - Rachel M. Taylor; Isaac H. Jeong; Matthew D. May; Elizabeth M. Bergman; Vincent F. Capaldi; Nicole L.T. Moore; Liana M. Matson; Emily G. Lowery-Gionta (Psychopharmacology, 2020)

The environmental impact of rearing crickets for live pet food in the UK, and implications of a transition to a hybrid business model combining production for live pet food with production for human consumption - J. Suckling; A. Druckman; C. D. Moore; D. Driscoll (The International Journal of Life Cycle Assessment, 2020)
Purpose Rearing crickets in the UK for the live pet food market is already a well-established industry. However, there is interest in also producing food for human consumption. This paper presents a life cycle assessment (LCA) of a current live pet food business. Using results from this LCA, the papers explores how current business practices could be improved to reduce environmental impacts, and discusses the potential benefits of a hybrid live pet food/human consumption business model. Methods An attributional, cradle-to-farm-gate life cycle assessment was conducted on rearing crickets for the live pet food market, with data collected on-site at a case study business. Results are reported in multiple impact categories from the ILCD 2011 Midpoint+ method. Comparison is made to the only other similar study: an LCA of rearing crickets in Thailand for human consumption (Halloran et al. J Clean Prod 156:83–94, 2017). The sources of the different environmental impacts between the two studies are explored and inefficiencies in the live pet food rearing process identified. Subsequently, scenarios are used to explore how the inefficiencies may be mitigated, and environmental impact of the live pet food production process reduced through adoption of a hybrid live pet food/human food production model. Results and discussions The environmental impact was found to be larger across all impact categories than the only known comparable study, which is for rearing crickets in Thailand for human consumption (Halloran et al. J Clean Prod 156:83–94, 2017). Some of this difference is due to the heating required for rearing crickets in a climate such as the UK, and some is due to the requirements of the live pet food market being much more demanding on resources than the human food model. The current study identifies improvements in practices that would make this contrast less stark, such as optimizing feeding practices, and the benefits of moving to a hybrid live pet food/human consumption business model. Conclusions This is the first LCA of crickets reared in the UK. The results highlight inefficiencies in the rearing process that are now being addressed by the case study business. The study also shows the potential co-benefits of a hybrid business model, in which crickets for human consumption are produced alongside crickets for the live pet food market.

Detection of the rare Australian endemic blind cave eel (Ophisternon candidum) with environmental DNA: implications for threatened species management in subterranean environments - Nicole E. White; Michelle T. Guzik; Andrew D. Austin; Glenn I. Moore; William F. Humphreys; Jason Alexander; Michael Bunce (Hydrobiologia, 2020)

‘Sub-Prime’ Water, Low-Security Entitlements and Policy Challenges in Over-Allocated River Basins: the Case of the Murray–Darling Basin - Harriet Elizabeth Moore; Ian D. Rutherfurd; Murray C. Peel; Avril Horne (Environmental Management, 2020)
Environmental policy is often implemented using market instruments. In some cases, including carbon taxing, the links between financial products and the environmental objectives, are transparent. In other cases, including water markets, the links are less transparent. In Australia’s Murray–Darling Basin (MDB), financial water products are known as ‘entitlements’, and are similar to traditional financial products, such as shares. The Australian water market includes ‘Low Security’ entitlements, which are similar to ‘sub-prime’ mortgage bonds because they are unlikely to yield an amount equal to their financial worth. Nearly half the water purchased under the Murray–Darling Basin Plan for environmental purposes is ‘Low Security’. We suggest that the current portfolio of water held by the Australian Government for environmental purposes reflects the mortgage market in the lead-up to the global financial crisis. Banks assumed that the future value of the mortgage market would reflect past trends. Similarly, it is assumed that the future value of water products will reflect past trends, without considering climate change. Historic records of allocations to ‘Low Security’ entitlements in the MDB suggest that, in the context of climate change, the Basin Plan water portfolio may fall short of the target annual average yield of 2075 GL by 511 GL. We recommend adopting finance sector methods including ‘hedging’ ‘Low Security’ entitlements by purchasing an additional 322–2755 GL of ‘Low Security’, or 160–511 GL of ‘High Security’ entitlements. Securing reliable environmental water is a global problem. Finance economics present opportunities for increasing the reliability of environmental flows.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Effects of Hurricane Harvey on the Trophic Status of Juvenile Sport Fishes (Cynoscion nebulosus, Sciaenops ocellatus) in an Estuarine Nursery - Philip Matich; Kaya B. Moore; Jeffrey D. Plumlee (Estuaries and Coasts, 2020)

Dominant native and non‐native graminoids differ in key leaf traits irrespective of nutrient availability - Arthur A. D. Broadbent; Jennifer Firn; James M. McGree; Elizabeth T. Borer; Yvonne M. Buckley; W. Stanley Harpole; Kimberly J. Komatsu; Andrew S. MacDougall; Kate H. Orwin; Nicholas J. Ostle; Eric W. Seabloom; Jonathan D. Bakker; et al. (Global Ecology and Biogeography, 2020)
Aim Nutrient enrichment is associated with plant invasions and biodiversity loss. Functional trait advantages may predict the ascendancy of invasive plants following nutrient enrichment but this is rarely tested. Here, we investigate (a) whether dominant native and non‐native plants differ in important morphological and physiological leaf traits, (b) how their traits respond to nutrient addition, and (c) whether responses are consistent across functional groups. Location Australia, Europe, North America and South Africa. Time period 2007–2014. Major taxa studied Graminoids and forbs. Methods We focused on two types of leaf traits connected to resource acquisition: morphological features relating to light‐foraging surfaces and investment in tissue (specific leaf area, SLA) and physiological features relating to internal leaf chemistry as the basis for producing and utilizing photosynthate. We measured these traits on 503 leaves from 151 dominant species across 27 grasslands on four continents. We used an identical nutrient addition treatment of nitrogen (N), phosphorus (P) and potassium (K) at all sites. Sites represented a broad range of grasslands that varied widely in climatic and edaphic conditions. Results We found evidence that non‐native graminoids invest in leaves with higher nutrient concentrations than native graminoids, particularly at sites where native and non‐native species both dominate. We found little evidence that native and non‐native forbs differed in the measured leaf traits. These results were consistent in natural soil fertility levels and nutrient‐enriched conditions, with dominant species responding similarly to nutrient addition regardless of whether they were native or non‐native. Main conclusions Our work identifies the inherent physiological trait advantages that can be used to predict non‐native graminoid establishment, potentially because of higher efficiency at taking up crucial nutrients into their leaves. Most importantly, these inherent advantages are already present at natural soil fertility levels and are maintained following nutrient enrichment.

Adequate supply of dietary taurine stimulates expression of molecular markers of growth and protein turnover in juvenile barramundi (Lates calcarifer) - David A. Poppi; Stephen S. Moore; Nicholas M. Wade; Brett D. Glencross (Fish Physiology and Biochemistry, 2020)

Evaluation of dredged sediment for aquatic placement: interpreting contaminant bioaccumulation - Andrew D. McQueen; Guilherme R. Lotufo; Scott W. Pickard; Andrew M. Lenox; David W. Moore; Katherine von Stackelberg; Burton C. Suedel (Environmental Monitoring and Assessment, 2020)

A comparison of cancer stage at diagnosis and treatment initiation between enrollees in an urban HIV clinic and SEER - Keri L. Calkins; Geetanjali Chander; Corinne E. Joshu; Kala Visvanathan; Anthony T. Fojo; Catherine R. Lesko; Richard D. Moore; Bryan Lau (Cancer Causes & Control, 2020)

Nutrient availability controls the impact of mammalian herbivores on soil carbon and nitrogen pools in grasslands - Judith Sitters; E. R. Jasper Wubs; Elisabeth S. Bakker; Thomas W. Crowther; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Lori Biederman; Elizabeth T. Borer; Elsa E. Cleland; Nico Eisenhauer; Jennifer Firn; et al. (Global Change Biology, 2020)
Grasslands are subject to considerable alteration due to human activities globally, including widespread changes in populations and composition of large mammalian herbivores and elevated supply of nutrients. Grassland soils remain important reservoirs of carbon (C) and nitrogen (N). Herbivores may affect both C and N pools and these changes likely interact with increases in soil nutrient availability. Given the scale of grassland soil fluxes, such changes can have striking consequences for atmospheric C concentrations and the climate. Here, we use the Nutrient Network experiment to examine the responses of soil C and N pools to mammalian herbivore exclusion across 22 grasslands, under ambient and elevated nutrient availabilities (fertilized with NPK + micronutrients). We show that the impact of herbivore exclusion on soil C and N pools depends on fertilization. Under ambient nutrient conditions, we observed no effect of herbivore exclusion, but under elevated nutrient supply, pools are smaller upon herbivore exclusion. The highest mean soil C and N pools were found in grazed and fertilized plots. The decrease in soil C and N upon herbivore exclusion in combination with fertilization correlated with a decrease in aboveground plant biomass and microbial activity, indicating a reduced storage of organic matter and microbial residues as soil C and N. The response of soil C and N pools to herbivore exclusion was contingent on temperature – herbivores likely cause losses of C and N in colder sites and increases in warmer sites. Additionally, grasslands that contain mammalian herbivores have the potential to sequester more N under increased temperature variability and nutrient enrichment than ungrazed grasslands. Our study highlights the importance of conserving mammalian herbivore populations in grasslands worldwide. We need to incorporate local‐scale herbivory, and its interaction with nutrient enrichment and climate, within global‐scale models to better predict land–atmosphere interactions under future climate change.

RAD-Seq Analysis and in situ Monitoring of Nassau Grouper Reveal Fine-Scale Population Structure and Origins of Aggregating Fish - Krista D. Sherman; Josephine R. Paris; Robert Andrew King; Karen A. Moore; Craig P. Dahlgren; Lindy C. Knowles; Kristine Stump; Charles R. Tyler; Jamie R. Stevens (Frontiers in Marine Science, 2020)

Multiple factors contribute to the spatially variable and dramatic decline of an invasive snail in an estuary where it was long-established and phenomenally abundant - Kerstin Wasson; Rachel A. Fabian; Susanne Fork; Julia Stanganelli; Zachary Mize; Kathryn Beheshti; Rikke Jeppesen; Isabel J. Jones; Chela J. Zabin; Sally Walker; Sarah C. Lummis; Mason Emery; et al. (Biological Invasions, 2020)

Nitrogen Demand Associated with Increased Biomass Yield of Switchgrass and Big Bluestem: Implications for Future Breeding Strategies - Michael D. Casler; DoKyoung Lee; Robert B. Mitchell; Paul R. Adler; R. Mark Sulc; Keith D. Johnson; Robert L. Kallenbach; Arvid R. Boe; Russell D. Mathison; Kim A. Cassida; Doohong Min; Kenneth J. Moore (BioEnergy Research, 2020)

Elevated atmospheric carbon dioxide concentrations alter root morphology and reduce the effectiveness of entomopathogenic nematodes - Ivan Hiltpold; Ben D. Moore; Scott N. Johnson (Plant and Soil, 2020)

Orchid fleck virus associated with the first case of citrus leprosis-N in South Africa - Glynnis Cook; Wayne Kirkman; Rochelle Clase; Chanel Steyn; Elaine Basson; Paul H. Fourie; Sean D. Moore; Tim G. Grout; Elma Carstens; Vaughan Hattingh (European Journal of Plant Pathology, 2019)

Belowground Biomass Response to Nutrient Enrichment Depends on Light Limitation Across Globally Distributed Grasslands - Elsa E. Cleland; Eric M. Lind; Nicole M. DeCrappeo; Elizabeth DeLorenze; Rachel Abbott Wilkins; Peter B. Adler; Jonathan D. Bakker; Cynthia S. Brown; Kendi F. Davies; Ellen Esch; Jennifer Firn; Scott Gressard; et al. (Ecosystems, 2019)

Moving Towards Gender Equality in Medical Toxicology - Meghan B. Spyres; Elizabeth C. Moore; Anne-Michelle Ruha; Ayrn D. O’Connor (Journal of Medical Toxicology, 2019)

Ingestion and Absorption of Eucalypt Monoterpenes in the Specialist Feeder, the Koala (Phascolarctos cinereus) - Caroline Marschner; Mark B. Krockenberger; Damien P. Higgins; Christopher Mitchell; Ben D. Moore (Journal of Chemical Ecology, 2019)

Current Status and Future Challenges of Weather Radar Polarimetry: Bridging the Gap between Radar Meteorology/Hydrology/Engineering and Numerical Weather Prediction - Guifu Zhang; Vivek N. Mahale; Bryan J. Putnam; Youcun Qi; Qing Cao; Andrew D. Byrd; Petar Bukovcic; Dusan S. Zrnic; Jidong Gao; Ming Xue; Youngsun Jung; Heather D. Reeves; et al. (Advances in Atmospheric Sciences, 2019)

Correction to: Are soils beneath coniferous tree stands more acidic than soils beneath deciduous tree stands? - Jason R. Burgess-Conforti; Philip A. Moore; Phillip R. Owens; David M. Miller; Amanda J. Ashworth; Phillip D. Hays; Michelle A. Evans-White; Kelsey R. Anderson (Environmental Science and Pollution Research, 2019)

Are soils beneath coniferous tree stands more acidic than soils beneath deciduous tree stands? - Jason R. Burgess-Conforti; Philip A. Moore; Phillip R. Owens; David M. Miller; Amanda J. Ashworth; Phillip D. Hays; Michelle A. Evans-White; Kelsey R. Anderson (Environmental Science and Pollution Research, 2019)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Establishing Patient Centric Specifications for Drug Substance and Drug Product Impurities - J. Bercu; S. C. Berlam; J. Berridge; B. Cherney; D. Cowley; H. W. Laughton; D. McLoughlin; M. McMahon; C. M. V. Moore; C. Murti; J. O’Neill; R. Parsons; et al. (Journal of Pharmaceutical Innovation, 2019)

Spatial autocorrelation inflates niche breadth–range size relationships - Timothy E. Moore; Robert Bagchi; Matthew E. Aiello‐Lammens; Carl D. Schlichting (Global Ecology and Biogeography, 2018)
Aim Species with broader environmental tolerances are expected to be more widely distributed than specialist species, implying a positive correlation between niche breadth and geographic range size. When this relationship is evaluated using data derived from broad‐scale geographic distributions of species, spatial autocorrelation of species distribution data and environments may inflate niche breadth–range size relationships, bringing into question the causal relationship between environmental tolerance and range size. Using null models, we quantify the contribution of spatial autocorrelation to the frequently reported relationship between species’ range size and niche breadth. Location South Africa. Time period Current. Major taxa studied Eighty species in the genus Pelargonium. Methods Using phylogenetic least squares regression, we examined the extent to which variation in range size of Pelargonium species is related to temperature and precipitation niche breadths. We developed null models that randomized the spatial distribution of the climatic variables, but retained their broad spatial autocorrelation structure. We tested whether observed niche breadth–range size relationships were stronger than expected, given spatial autocorrelation of climatic variables. Results We found the expected positive relationships between measures of niche breadth and range size, but these were no stronger than expected based on our spatial null models. Including spatial structure in simulations reduced expected niche breadths compared to simulations based on fully randomized environmental variables, resulting in steeper slopes for the simulated niche breadth–range size relationships. Main conclusion Our results indicate that spatial autocorrelation may positively bias niche breadth–range size relationships. This bias suggests that previously reported relationships between range size and niche breadth based on broad‐scale distributional data may be, at least in part, artefactual. Future studies need to explicitly account for spatial autocorrelation, and inferences on the role of environmental tolerance in driving patterns of species range size variation should be derived in conjunction with laboratory and field‐based experiments.

Comparative genomics and physiology of the genus Methanohalophilus , a prevalent methanogen in hydraulically fractured shale - Mikayla A. Borton; Rebecca A. Daly; Bridget O'Banion; David W. Hoyt; Daniel N. Marcus; Susan Welch; Sybille S. Hastings; Tea Meulia; Richard A. Wolfe; Anne E. Booker; Shikha Sharma; David R. Cole; et al. (Environmental Microbiology, 2018)
Summary About 60% of natural gas production in the United States comes from hydraulic fracturing of unconventional reservoirs, such as shales or organic‐rich micrites. This process inoculates and enriches for halotolerant microorganisms in these reservoirs over time, resulting in a saline ecosystem that includes methane producing archaea. Here, we survey the biogeography of methanogens across unconventional reservoirs, and report that members of genus Methanohalophilus are recovered from every hydraulically fractured unconventional reservoir sampled by metagenomics. We provide the first genomic sequencing of three isolate genomes, as well as two metagenome assembled genomes (MAGs). Utilizing six other previously sequenced isolate genomes and MAGs, we perform comparative analysis of the 11 genomes representing this genus. This genomic investigation revealed distinctions between surface and subsurface derived genomes that are consistent with constraints encountered in each environment. Genotypic differences were also uncovered between isolate genomes recovered from the same well, suggesting niche partitioning among closely related strains. These genomic substrate utilization predictions were then confirmed by physiological investigation. Fine‐scale microdiversity was observed in CRISPR‐Cas systems of Methanohalophilus , with genomes from geographically distinct unconventional reservoirs sharing spacers targeting the same viral population. These findings have implications for augmentation strategies resulting in enhanced biogenic methane production in hydraulically fractured unconventional reservoirs.

Effect of 1-week betalain-rich beetroot concentrate supplementation on cycling performance and select physiological parameters - Petey W. Mumford; Wesley C. Kephart; Matthew A. Romero; Cody T. Haun; C. Brooks Mobley; Shelby C. Osburn; James C. Healy; Angelique N. Moore; David D. Pascoe; William C. Ruffin; Darren T. Beck; Jeffrey S. Martin; et al. (European Journal of Applied Physiology, 2018)

Effects of an Education Intervention about HPV Self-Testing for Healthcare Providers and Staff - Brynne E. Presser; Mira L. Katz; Abigail B. Shoben; Deborah Moore; Mack T. Ruffin; Electra D. Paskett; Paul L. Reiter (Journal of Cancer Education, 2018)

Study of worker’s exposure to Tantalum-bearing particles in a mining and metallurgical plant - K. Moore Dias da Cunha; K. C. Dalia Pereira; J. R. D. Guimarães; C. Lima; J. E. C. Nascimento; R. Lima; A. A. Hecht; J. C. B. Fiel (Environmental Geochemistry and Health, 2018)

Carbon assimilation and transfer through kelp forests in the NE Atlantic is diminished under a warmer ocean climate - Albert Pessarrodona; Pippa J. Moore; Martin D. J. Sayer; Dan A. Smale (Global Change Biology, 2018)
Global climate change is affecting carbon cycling by driving changes in primary productivity and rates of carbon fixation, release and storage within Earth's vegetated systems. There is, however, limited understanding of how carbon flow between donor and recipient habitats will respond to climatic changes. Macroalgal‐dominated habitats, such as kelp forests, are gaining recognition as important carbon donors within coastal carbon cycles, yet rates of carbon assimilation and transfer through these habitats are poorly resolved. Here, we investigated the likely impacts of ocean warming on coastal carbon cycling by quantifying rates of carbon assimilation and transfer in Laminaria hyperborea kelp forests—one of the most extensive coastal vegetated habitat types in the NE Atlantic—along a latitudinal temperature gradient. Kelp forests within warm climatic regimes assimilated, on average, more than three times less carbon and donated less than half the amount of particulate carbon compared to those from cold regimes. These patterns were not related to variability in other environmental parameters. Across their wider geographical distribution, plants exhibited reduced sizes toward their warm‐water equatorward range edge, further suggesting that carbon flow is reduced under warmer climates. Overall, we estimated that Laminaria hyperborea forests stored ~11.49 Tg C in living biomass and released particulate carbon at a rate of ~5.71 Tg C year −1 . This estimated flow of carbon was markedly higher than reported values for most other marine and terrestrial vegetated habitat types in Europe. Together, our observations suggest that continued warming will diminish the amount of carbon that is assimilated and transported through temperate kelp forests in NE Atlantic, with potential consequences for the coastal carbon cycle. Our findings underline the need to consider climate‐driven changes in the capacity of ecosystems to fix and donate carbon when assessing the impacts of climate change on carbon cycling.

Spatial heterogeneity in species composition constrains plant community responses to herbivory and fertilisation - Dorothee Hodapp; Elizabeth T. Borer; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Juan Alberti; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Marc Cadotte; Elsa E. Cleland; et al. (Ecology Letters, 2018)
Environmental change can result in substantial shifts in community composition. The associated immigration and extinction events are likely constrained by the spatial distribution of species. Still, studies on environmental change typically quantify biotic responses at single spatial (time series within a single plot) or temporal (spatial beta diversity at single time points) scales, ignoring their potential interdependence. Here, we use data from a global network of grassland experiments to determine how turnover responses to two major forms of environmental change – fertilisation and herbivore loss – are affected by species pool size and spatial compositional heterogeneity. Fertilisation led to higher rates of local extinction, whereas turnover in herbivore exclusion plots was driven by species replacement. Overall, sites with more spatially heterogeneous composition showed significantly higher rates of annual turnover, independent of species pool size and treatment. Taking into account spatial biodiversity aspects will therefore improve our understanding of consequences of global and anthropogenic change on community dynamics.

Climate research priorities for policy-makers, practitioners, and scientists in Georgia, USA - Murray A. Rudd; Althea F. P. Moore; Daniel Rochberg; Lisa Bianchi-Fossati; Marilyn A. Brown; David D’Onofrio; Carrie A. Furman; Jairo Garcia; Ben Jordan; Jennifer Kline; L. Mark Risse; Patricia L. Yager; et al. (Environmental Management, 2018)

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

The modern pollen–vegetation relationships of a tropical forest–savannah mosaic landscape, Ghana, West Africa - Adele C.M. Julier; Phillip E. Jardine; Stephen Adu-Bredu; Angela L. Coe; Akwasi Duah-Gyamfi; Wesley T. Fraser; Barry H. Lomax; Yadvinder Malhi; Sam Moore; Kennedy Owusu-Afriyie; William D. Gosling (Palynology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Root responses to domestication, precipitation and silicification: weeping meadow grass simplifies and alters toughness - James M. W. Ryalls; Ben D. Moore; Scott N. Johnson; Myles Connor; Ivan Hiltpold (Plant and Soil, 2018)

Neural correlates of verbal memory in youth with heavy prenatal alcohol exposure - Lauren A. Gross; Eileen M. Moore; Jeffrey R. Wozniak; Claire D. Coles; Julie A. Kable; Elizabeth R. Sowell; Kenneth L. Jones; Edward P. Riley; Sarah N. Mattson (Brain Imaging and Behavior, 2018)

Leveraging epigenomics and contactomics data to investigate SNP pairs in GWAS - Elisabetta Manduchi; Scott M. Williams; Alessandra Chesi; Matthew E. Johnson; Andrew D. Wells; Struan F. A. Grant; Jason H. Moore (Human Genetics, 2018)

Pollen-vegetation richness and diversity relationships in the tropics - William D. Gosling; Adele C. M. Julier; Stephen Adu-Bredu; Gloria D. Djagbletey; Wesley T. Fraser; Phillip E. Jardine; Barry H. Lomax; Yadvinder Malhi; Emmanuel A. Manu; Francis E. Mayle; Sam Moore (Vegetation History and Archaeobotany, 2018)

Tracking long-distance atmospheric deposition of trace metal emissions from smelters in the upper Columbia River valley using Pb isotope analysis of lake sediments - Andrew Wright Child; Barry C. Moore; Jeffrey D. Vervoort; Marc W. Beutel (Environmental Science and Pollution Research, 2018)

Exposure to Sublethal Ammonia Concentrations Alters the Duration and Intensity of Agonistic Interactions in the Crayfish, Orconectes rusticus - David D. Edwards; Katie L. Klotz; Paul A. Moore (Bulletin of Environmental Contamination and Toxicology, 2018)

Assessing uncertainties in crop and pasture ensemble model simulations of productivity and N 2 O emissions - Fiona Ehrhardt; Jean‐François Soussana; Gianni Bellocchi; Peter Grace; Russel McAuliffe; Sylvie Recous; Renáta Sándor; Pete Smith; Val Snow; Massimiliano de Antoni Migliorati; Bruno Basso; Arti Bhatia; et al. (Global Change Biology, 2018)
Simulation models are extensively used to predict agricultural productivity and greenhouse gas emissions. However, the uncertainties of (reduced) model ensemble simulations have not been assessed systematically for variables affecting food security and climate change mitigation, within multi‐species agricultural contexts. We report an international model comparison and benchmarking exercise, showing the potential of multi‐model ensembles to predict productivity and nitrous oxide (N 2 O) emissions for wheat, maize, rice and temperate grasslands. Using a multi‐stage modelling protocol, from blind simulations (stage 1) to partial (stages 2–4) and full calibration (stage 5), 24 process‐based biogeochemical models were assessed individually or as an ensemble against long‐term experimental data from four temperate grassland and five arable crop rotation sites spanning four continents. Comparisons were performed by reference to the experimental uncertainties of observed yields and N 2 O emissions. Results showed that across sites and crop/grassland types, 23%–40% of the uncalibrated individual models were within two standard deviations ( SD ) of observed yields, while 42 (rice) to 96% (grasslands) of the models were within 1 SD of observed N 2 O emissions. At stage 1, ensembles formed by the three lowest prediction model errors predicted both yields and N 2 O emissions within experimental uncertainties for 44% and 33% of the crop and grassland growth cycles, respectively. Partial model calibration (stages 2–4) markedly reduced prediction errors of the full model ensemble E‐median for crop grain yields (from 36% at stage 1 down to 4% on average) and grassland productivity (from 44% to 27%) and to a lesser and more variable extent for N 2 O emissions. Yield‐scaled N 2 O emissions (N 2 O emissions divided by crop yields) were ranked accurately by three‐model ensembles across crop species and field sites. The potential of using process‐based model ensembles to predict jointly productivity and N 2 O emissions at field scale is discussed.

Forest biomass, productivity and carbon cycling along a rainfall gradient in West Africa - Sam Moore; Stephen Adu‐Bredu; Akwasi Duah‐Gyamfi; Shalom D. Addo‐Danso; Forzia Ibrahim; Armel T. Mbou; Agnès de Grandcourt; Riccardo Valentini; Giacomo Nicolini; Gloria Djagbletey; Kennedy Owusu‐Afriyie; Agne Gvozdevaite; et al. (Global Change Biology, 2018)
Net Primary Productivity ( NPP ) is one of the most important parameters in describing the functioning of any ecosystem and yet it arguably remains a poorly quantified and understood component of carbon cycling in tropical forests, especially outside of the Americas. We provide the first comprehensive analysis of NPP and its carbon allocation to woody, canopy and root growth components at contrasting lowland West African forests spanning a rainfall gradient. Using a standardized methodology to study evergreen ( EF ), semi‐deciduous ( SDF ), dry forests ( DF ) and woody savanna ( WS ), we find that (i) climate is more closely related with above and belowground C stocks than with NPP (ii) total NPP is highest in the SDF site, then the EF followed by the DF and WS and that (iii) different forest types have distinct carbon allocation patterns whereby SDF allocate in excess of 50% to canopy production and the DF and WS sites allocate 40%–50% to woody production. Furthermore, we find that (iv) compared with canopy and root growth rates the woody growth rate of these forests is a poor proxy for their overall productivity and that (v) residence time is the primary driver in the productivity‐allocation‐turnover chain for the observed spatial differences in woody, leaf and root biomass across the rainfall gradient. Through a systematic assessment of forest productivity we demonstrate the importance of directly measuring the main components of above and belowground NPP and encourage the establishment of more permanent carbon intensive monitoring plots across the tropics.

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Assessment of wound healing of tagged gray ( Eschrichtius robustus ) and blue ( Balaenoptera musculus ) whales in the eastern North Pacific using long‐term series of photographs - Stephanie A. Norman; Kiirsten R. Flynn; Alexandre N. Zerbini; Frances M. D. Gulland; Michael J. Moore; Stephen Raverty; David S. Rotstein; Bruce R. Mate; Craig Hayslip; Diane Gendron; Richard Sears; Annie B. Douglas; et al. (Marine Mammal Science, 2018)
Tags have been used to examine migration routes and habitat use of large whales for >40 yr, however, evaluation of tag wound healing has largely been short‐term, anecdotal or generalized. This study developed methods for systematic photographic assessment of long‐term external consequences of tag placement, to determine potential differences in wound healing between species and tag types and thus advise future tagging efforts to possibly minimize undesirable side effects. Tag site appearance and healing characteristics were evaluated by two reviewers and a time series evaluated by five veterinarians from photographs during 995 postdeployment encounters with 34 gray and 63 blue whales tagged in the North Pacific. Blue whale resightings were less frequent, but spanned a longer time period due to earlier tag deployments than the more frequent gray whale follow‐up observations. Swelling occurred in 74% of reencountered gray whales, with the highest frequency 6 mo postdeployment. Swellings were common in blue whales with early tag designs but rare with current models. Depressions occurred in 82% of gray and 71% of blue whales. This study demonstrates the value of follow‐up studies of tagged animals and systematic scoring of photographs to quantitatively compare tag response.

Concomitant external pneumatic compression treatment with consecutive days of high intensity interval training reduces markers of proteolysis - Cody T. Haun; Michael D. Roberts; Matthew A. Romero; Shelby C. Osburn; James C. Healy; Angelique N. Moore; Christopher B. Mobley; Paul A. Roberson; Wesley C. Kephart; Petey W. Mumford; Michael D. Goodlett; David D. Pascoe; et al. (European Journal of Applied Physiology, 2017)

Seascape genomics reveals fine‐scale patterns of dispersal for a reef fish along the ecologically divergent coast of Northwestern Australia - Joseph D. DiBattista; Michael J. Travers; Glenn I. Moore; Richard D. Evans; Stephen J. Newman; Ming Feng; Samuel D. Moyle; Rebecca J. Gorton; Thor Saunders; Oliver Berry (Molecular Ecology, 2017)
Understanding the drivers of dispersal among populations is a central topic in marine ecology and fundamental for spatially explicit management of marine resources. The extensive coast of Northwestern Australia provides an emerging frontier for implementing new genomic tools to comparatively identify patterns of dispersal across diverse and extreme environmental conditions. Here, we focused on the stripey snapper ( Lutjanus carponotatus ), which is important to recreational, charter‐based and customary fishers throughout the Indo‐West Pacific. We collected 1,016 L. carponotatus samples at 51 locations in the coastal waters of Northwestern Australia ranging from the Northern Territory to Shark Bay and adopted a genotype‐by‐sequencing approach to test whether realized connectivity (via larval dispersal) was related to extreme gradients in coastal hydrodynamics. Hydrodynamic simulations using CONNIE and a more detailed treatment in the Kimberley Bioregion provided null models for comparison. Based on 4,402 polymorphic single nucleotide polymorphism loci shared across all individuals, we demonstrated significant genetic subdivision between the Shark Bay Bioregion in the south and all locations within the remaining, more northern bioregions. More importantly, we identified a zone of admixture spanning a distance of 180 km at the border of the Kimberley and Canning bioregions, including the Buccaneer Archipelago and adjacent waters, which collectively experiences the largest tropical tidal range and some of the fastest tidal currents in the world. Further testing of the generality of this admixture zone in other shallow water species across broader geographic ranges will be critical for our understanding of the population dynamics and genetic structure of marine taxa in our tropical oceans.

Piscirickettsia salmonis infection in cultured lumpfish ( Cyclopterus lumpus L.) - M Marcos‐López; N M Ruane; F Scholz; M Bolton‐Warberg; S O Mitchell; S Murphy O'Sullivan; A Irwin Moore; H D Rodger (Journal of Fish Diseases, 2017)
A Piscirickettsia salmonis infection was diagnosed in lumpfish ( Cyclopterus lumpus L.) juveniles held in a marine research facility on the west coast of Ireland. The main clinical signs and pathology included marked ascites, severe multifocal liver necrosis and severe diffuse inflammation and necrosis of the exocrine pancreas and peri‐pancreatic adipose tissue. Numerous Piscirickettsia ‐like organisms were observed by histopathology in the affected organs, and the bacterial species was characterized by molecular analysis. Sequencing of the partial 16S rDNA gene and internal transcribed spacer region showed the lumpfish sequences to be closely related to previously identified Atlantic salmon ( Salmo salar L.) sequences from Ireland. To the authors’ knowledge, this is the first detection of P. salmonis in lumpfish worldwide. The infection is considered potentially significant in terms of lumpfish health and biosecurity.

Intraspecific haplotype diversity in Cherleria sedoides L. (Caryophyllaceae) is best explained by chloroplast capture from an extinct species - Abigail J. Moore; Francisco J. Valtueña; Markus S. Dillenberger; Joachim W. Kadereit; Chris D. Preston (Alpine Botany, 2017)

Bio-optical Properties of Cyanobacteria Blooms in Western Lake Erie - Timothy S. Moore; Colleen B. Mouw; James M. Sullivan; Michael S. Twardowski; Ashley M. Burtner; Audrey B. Ciochetto; Malcolm N. McFarland; Aditya R. Nayak; Danna Paladino; Nicole D. Stockley; Thomas H. Johengen; Angela W. Yu; et al. (Frontiers in Marine Science, 2017)

A system to identify inhibitors of mTOR signaling using high-resolution growth analysis in Saccharomyces cerevisiae - Mitchell B. Lee; Daniel T. Carr; Michael G. Kiflezghi; Yan Ting Zhao; Deborah B. Kim; Socheata Thon; Margarete D. Moore; Mary Ann K. Li; Matt Kaeberlein (GeroScience, 2017)

Can short-term litter-bag measurements predict long-term decomposition in northern forests? - Tim R. Moore; J. A. Trofymow; C. E. Prescott; B. D. Titus (Plant and Soil, 2017)

Gain-of-function EGLN1 prolyl hydroxylase (PHD2 D4E:C127S) in combination with EPAS1 (HIF-2α) polymorphism lowers hemoglobin concentration in Tibetan highlanders - Tsewang Tashi; N. Scott Reading; Tanna Wuren; Xu Zhang; Lorna G. Moore; Hao Hu; Feng Tang; Anna Shestakova; Felipe Lorenzo; Tatiana Burjanivova; Parvaiz Koul; Prasenjit Guchhait; et al. (Journal of Molecular Medicine, 2017)

Temporal and spatial trends in the abundances of an apex predator, introduced mesopredator and ground-nesting bird are consistent with the mesopredator release hypothesis - Christopher E. Gordon; Ben D. Moore; Mike Letnic (Biodiversity and Conservation, 2017)

An allelic series at pax7a is associated with colour polymorphism diversity in Lake Malawi cichlid fish - Reade B. Roberts; Emily C. Moore; Thomas D. Kocher (Molecular Ecology, 2017)
Despite long‐standing interest in the evolution and maintenance of discrete phenotypic polymorphisms, the molecular genetic basis of such polymorphism in the wild is largely unknown. Female sex‐associated blotched colour polymorphisms found in cichlids of Lake Malawi, East Africa, represent a highly successful polymorphic phenotype, found and maintained in four genera across the geographic expanse of the lake. Previously, we identified an association with an allelic variant of the paired‐box transcription factor gene pax7a and blotched colour morphs in Lake Malawi cichlid fishes. Although a diverse range of blotched phenotypes are present in Lake Malawi cichlid species, they all appeared to result from an allele of pax7a that produces increased levels of transcript. Here, we examine the developmental and genetic basis of variation among blotched morphs. First, we confirm that pax7a ‐associated blotch morphs result primarily from modulation of melanophore development and survival. From laboratory crosses and natural population studies, we identify at least three alleles of pax7a associated with discrete subtypes of blotched morphs, in addition to the ancestral pax7a allele. Genotypes at pax7a support initial evolution of a novel pax7a allele to produce the blotched class of morphs, followed by subsequent evolution of that pax7a blotched allele to produce additional alleles associated with discrete colour morphs. Variant alleles of pax7a produce different levels of pax7a transcript, correlating with pigmentation phenotype at the cellular level. This naturally selected allelic series should serve as a case study for understanding the molecular genetic control of pax7a expression and the evolution of sex‐associated alleles.

Response diversity, nonnative species, and disassembly rules buffer freshwater ecosystem processes from anthropogenic change - Jonathan W. Moore; Julian D. Olden (Global Change Biology, 2017)
Integrating knowledge of environmental degradation, biodiversity change, and ecosystem processes across large spatial scales remains a key challenge to illuminating the resilience of earth's systems. There is now a growing realization that the manner in which communities will respond to anthropogenic impacts will ultimately control the ecosystem consequences. Here, we examine the response of freshwater fishes and their nutrient excretion – a key ecosystem process that can control aquatic productivity – to human land development across the contiguous United States. By linking a continental‐scale dataset of 533 fish species from 8100 stream locations with species functional traits, nutrient excretion, and land remote sensing, we present four key findings. First, we provide the first geographic footprint of nutrient excretion by freshwater fishes across the United States and reveal distinct local‐ and continental‐scale heterogeneity in community excretion rates. Second, fish species exhibited substantial response diversity in their sensitivity to land development; for native species, the more tolerant species were also the species contributing greater ecosystem function in terms of nutrient excretion. Third, by modeling increased land‐use change and resultant shifts in fish community composition, land development is estimated to decrease fish nutrient excretion in the majority (63%) of ecoregions. Fourth, the loss of nutrient excretion would be 28% greater if biodiversity loss was random or 84% greater if there were no nonnative species. Thus, ecosystem processes are sensitive to increased anthropogenic degradation but biotic communities provide multiple pathways for resistance and this resistance varies across space.

Decay of the glycolytic pathway and adaptation to intranuclear parasitism within Enterocytozoonidae microsporidia - Dominic Wiredu Boakye; Pattana Jaroenlak; Anuphap Prachumwat; Tom A. Williams; Kelly S. Bateman; Ornchuma Itsathitphaisarn; Kallaya Sritunyalucksana; Konrad H. Paszkiewicz; Karen A. Moore; Grant D. Stentiford; Bryony A. P. Williams (Environmental Microbiology, 2017)
Summary Glycolysis and oxidative phosphorylation are the fundamental pathways of ATP generation in eukaryotes. Yet in microsporidia, endoparasitic fungi living at the limits of cellular streamlining, oxidative phosphorylation has been lost: energy is obtained directly from the host or, during the dispersive spore stage, via glycolysis. It was therefore surprising when the first sequenced genome from the Enterocytozoonidae – a major family of human and animal‐infecting microsporidians – appeared to have lost genes for glycolysis. Here, we sequence and analyse genomes from additional members of this family, shedding new light on their unusual biology. Our survey includes the genome of Enterocytozoon hepatopenaei , a major aquacultural parasite currently causing substantial economic losses in shrimp farming, and Enterospora canceri , a pathogen that lives exclusively inside epithelial cell nuclei of its crab host. Our analysis of gene content across the clade suggests that Ent. canceri 's adaptation to intranuclear life is underpinned by the expansion of transporter families. We demonstrate that this entire lineage of pathogens has lost glycolysis and, uniquely amongst eukaryotes, lacks any obvious intrinsic means of generating energy. Our study provides an important resource for the investigation of host‐pathogen interactions and reductive evolution in one of the most medically and economically important microsporidian lineages.

Soil greenhouse gas emissions from agroforestry and other land uses under different moisture regimes in lower Missouri River Floodplain soils: a laboratory approach - B. D. Moore; G. Kaur; P. P. Motavalli; B. A. Zurweller; B. M. Svoma (Agroforestry Systems, 2017)

Messages of Hope: Helping Family Members to Overcome Fears and Fatalistic Attitudes Toward Cancer - Jill B. Hamilton; Valarie C. Worthy; Angelo D. Moore; Nakia C. Best; Jennifer M. Stewart; Mi-Kyung Song (Journal of Cancer Education, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Identifying gene–gene interactions that are highly associated with four quantitative lipid traits across multiple cohorts - Rishika De; Shefali S. Verma; Emily Holzinger; Molly Hall; Amber Burt; David S. Carrell; David R. Crosslin; Gail P. Jarvik; Helena Kuivaniemi; Iftikhar J. Kullo; Leslie A. Lange; Matthew B. Lanktree; et al. (Human Genetics, 2017)

Smoking status, usual adult occupation, and risk of recurrent urothelial bladder carcinoma: data from The Cancer Genome Atlas (TCGA) Project - Amber N. Wilcox; Debra T. Silverman; Melissa C. Friesen; Sarah J. Locke; Daniel E. Russ; Noorie Hyun; Joanne S. Colt; Jonine D. Figueroa; Nathaniel Rothman; Lee E. Moore; Stella Koutros (Cancer Causes & Control, 2016)

Entomopathogenic fungi as control agents of Thaumatotibia leucotreta in citrus orchards: field efficacy and persistence - C. A. Coombes; M. P. Hill; S. D. Moore; J. F. Dames (BioControl, 2016)

Can estimates of genetic effective population size contribute to fisheries stock assessments? - J. R. Ovenden; G. M. Leigh; D. C. Blower; A. T. Jones; A. Moore; C. Bustamante; R. C. Buckworth; M. B. Bennett; C. L. Dudgeon (Journal of Fish Biology, 2016)
Sustainable exploitation of fisheries populations is challenging to achieve when the size of the population prior to exploitation and the actual numbers removed over time and across fishing zones are not clearly known. Quantitative fisheries' modeling is able to address this problem, but accurate and reliable model outcomes depend on high quality input data. Much of this information is obtained through the operation of the fishery under consideration, but while this seems appropriate, biases may occur. For example, poorly quantified changes in fishing methods that increase catch rates can erroneously suggest that the overall population size is increasing. Hence, the incorporation of estimates of abundance derived from independent data sources is preferable. We review and evaluate a fisheries‐independent method of indexing population size; inferring adult abundance from estimates of the genetic effective size of a population ( N e ). Recent studies of elasmobranch species have shown correspondence between N e and ecologically determined estimates of the population size ( N ). Simulation studies have flagged the possibility that the range of N e / N ratios across species may be more restricted than previously thought, and also show that declines in N e track declines in the abundance of model fisheries species. These key developments bring this new technology closer to implementation in fisheries science, particularly for data‐poor fisheries or species of conservation interest.

Discovery and complete genome sequence of a novel circovirus-like virus in the endangered rowi kiwi, Apteryx rowi - Daniel J. White; Richard J. Hall; Jing Wang; Nicole E. Moore; Duckchul Park; Kate McInnes; Brett D. Gartrell; Daniel M. Tompkins (Virus Genes, 2016)

The comparative analysis of complete genome sequences from two South African betabaculoviruses: Phthorimaea operculella granulovirus and Plutella xylostella granulovirus - M. D. Jukes; B. M. Motsoeneng; C. M. Knox; M. P. Hill; S. D. Moore (Archives of Virology, 2016)

Comparative genomic, proteomic and exoproteomic analyses of three Pseudomonas strains reveals novel insights into the phosphorus scavenging capabilities of soil bacteria - Ian D. E. A. Lidbury; Andrew R. J. Murphy; David J. Scanlan; Gary D. Bending; Alexandra M. E. Jones; Jonathan D. Moore; Andrew Goodall; John P. Hammond; Elizabeth M. H. Wellington (Environmental Microbiology, 2016)
Summary Bacteria that inhabit the rhizosphere of agricultural crops can have a beneficial effect on crop growth. One such mechanism is the microbial‐driven solubilization and remineralization of complex forms of phosphorus (P). It is known that bacteria secrete various phosphatases in response to low P conditions. However, our understanding of their global proteomic response to P stress is limited. Here, exoproteomic analysis of Pseudomonas putida BIRD‐1 (BIRD‐1), Pseudomonas fluorescens SBW25 and Pseudomonas stutzeri DSM4166 was performed in unison with whole‐cell proteomic analysis of BIRD‐1 grown under phosphate (Pi) replete and Pi deplete conditions. Comparative exoproteomics revealed marked heterogeneity in the exoproteomes of each Pseudomonas strain in response to Pi depletion. In addition to well‐characterized members of the PHO regulon such as alkaline phosphatases, several proteins, previously not associated with the response to Pi depletion, were also identified. These included putative nucleases, phosphotriesterases, putative phosphonate transporters and outer membrane proteins. Moreover, in BIRD‐1, mutagenesis of the master regulator, phoBR , led us to confirm the addition of several novel PHO‐dependent proteins. Our data expands knowledge of the Pseudomonas PHO regulon, including species that are frequently used as bioinoculants, opening up the potential for more efficient and complete use of soil complexed P.

Recent Scientific Publications Cast Doubt on North Atlantic Right Whale Future - Scott D. Kraus; Robert D. Kenney; Charles A. Mayo; William A. McLellan; Michael J. Moore; Douglas P. Nowacek (Frontiers in Marine Science, 2016)

The impact of ethnicity/race on the association between the Veterans Aging Cohort Study (VACS) Index and neurocognitive function among HIV-infected persons - M. J. Marquine; M. Sakamoto; C. Dufour; A. Rooney; P. Fazeli; A. Umlauf; B. Gouaux; D. Franklin; R. Ellis; S. Letendre; M. Cherner; R. K. Heaton; et al. (Journal of NeuroVirology, 2016)

Heterogeneity in virulence relationships between Cryptophlebia leucotreta granulovirus isolates and geographically distinct host populations: lessons from codling moth resistance to CpGV-M - John K. Opoku-Debrah; Martin P. Hill; Caroline Knox; Sean D. Moore (BioControl, 2016)

B-Cell Depletion Reduces the Maturation of Cerebral Cavernous Malformations in Murine Models - Changbin Shi; Robert Shenkar; Hussein A. Zeineddine; Romuald Girard; Maged D. Fam; Cecilia Austin; Thomas Moore; Rhonda Lightle; Lingjiao Zhang; Meijing Wu; Ying Cao; Murat Gunel; et al. (Journal of Neuroimmune Pharmacology, 2016)

Highly heritable resistance to root-lesion nematode (Pratylenchus thornei) in Australian chickpea germplasm observed using an optimised glasshouse method and multi-environment trial analysis - M. S. Rodda; K. B. Hobson; C. R. Forknall; R. P. Daniel; J. P. Fanning; D. D. Pounsett; S. Simpfendorfer; K. J. Moore; K. J. Owen; J. G. Sheedy; J. P. Thompson; G. J. Hollaway; et al. (Australasian Plant Pathology, 2016)

Biological data from a data‐deficient shark: the Arabian smoothhound Mustelus mosis (Carcharhiniformes: Triakidae) - A. B. M. Moore; A. C. Henderson; E. D. Farrell; L. B. Weekes (Journal of Fish Biology, 2016)
The present study provides information on length distribution, reproductive biology and diet of Mustelus mosis based on individuals caught in waters off the eastern Arabian Peninsula. Although ageing of vertebral centra was attempted, band pairs were of low clarity and counts could not be confidently assigned.

The effects of resistance exercise training on arterial stiffness in metabolic syndrome - E. DeVallance; S. Fournier; K. Lemaster; C. Moore; S. Asano; D. Bonner; D. Donley; I. M. Olfert; P. D. Chantler (European Journal of Applied Physiology, 2016)

Antibiotics as CECs: An Overview of the Hazards Posed by Antibiotics and Antibiotic Resistance - Geoffrey I. Scott; Dwayne E. Porter; R. Sean Norman; C. Hart Scott; Miguel I. Uyaguari-Diaz; Keith A. Maruya; Steve B. Weisberg; Michael H. Fulton; Ed F. Wirth; Janet Moore; Paul L. Pennington; Daniel Schlenk; et al. (Frontiers in Marine Science, 2016)

Salt Accumulation and Potato Tuber Yield Response to Historical Dairy Manure Applications in South-Central Idaho - Sara A. Zglobicki; Amber D. Moore; Nora L. Olsen (American Journal of Potato Research, 2016)

$$\dot{V}$$ V ˙ O2 and HR kinetics before and after International Space Station missions - U. Hoffmann; A. D. Moore; J. Koschate; U. Drescher (European Journal of Applied Physiology, 2016)

Precipitation, not CO2 enrichment, drives insect herbivore frass deposition and subsequent nutrient dynamics in a mature Eucalyptus woodland - Andrew N. Gherlenda; Kristine Y. Crous; Ben D. Moore; Anthony M. Haigh; Scott N. Johnson; Markus Riegler (Plant and Soil, 2016)

Quantifying the conservation value of seascape connectivity: a global synthesis - Andrew D. Olds; Rod M. Connolly; Kylie A. Pitt; Simon J. Pittman; Paul S. Maxwell; Chantal M. Huijbers; Brad R. Moore; Simon Albert; David Rissik; Russell C. Babcock; Thomas A. Schlacher (Global Ecology and Biogeography, 2016)
Aim Connectivity structures populations, communities and ecosystems in the sea. The extent of connectivity is, therefore, predicted to also influence the outcomes of conservation initiatives, such as marine reserves. Here we review the published evidence about how important seascape connectivity (i.e. landscape connectivity in the sea) is for marine conservation outcomes. Location Global. Methods We analysed the global literature on the effects of seascape connectivity on reserve performance. Results In the majority of cases, greater seascape connectivity inside reserves translates into better conservation outcomes (i.e. enhanced productivity and diversity). Research on reserve performance is, however, most often conducted separately from research on connectivity, resulting in few studies ( Main conclusions Given that research rarely connects the effects of connectivity and reserves, our thesis is that stronger linkages between landscape ecology and marine spatial planning are likely to improve conservation outcomes in the sea. The key science challenge is to identify the full range of ecological functions that are modulated by connectivity and the spatial scale over which these functions enhance conservation outcomes.

Patterns of movement in the Ventnor landslide complex, Isle of Wight, southern England - J. M. Carey; R. Moore; D. N. Petley (Landslides, 2015)

Strategies African-American Cancer Survivors Use to Overcome Fears and Fatalistic Attitudes - Jill B. Hamilton; Nakia C. Best; Kayoll V. Galbraith; Valarie C. Worthy; LTC Angelo D. Moore (Journal of Cancer Education, 2015)

Hypovolemic men and women regulate blood pressure differently following exposure to artificial gravity - Joyce M. Evans; L. Christine Ribeiro; Fritz B. Moore; Siqi Wang; Qingguang Zhang; Vladimir Kostas; Connor R. Ferguson; Jorge Serrador; Michael Falvo; Michael B. Stenger; Nandu Goswami; Jon C. Rask; et al. (European Journal of Applied Physiology, 2015)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Post‐glacial recolonization of the North American Arctic by Arctic char ( Salvelinus alpinus ): genetic evidence of multiple northern refugia and hybridization between glacial lineages - Jean‐Sébastien Moore; Robert Bajno; James D. Reist; Eric B. Taylor (Journal of Biogeography, 2015)
Aims We investigated post‐glacial recolonization of the North American Arctic by Arctic char ( Salvelinus alpinus ) and examined potential hybridization between different glacial lineages upon secondary contact. Location North American Arctic and adjacent areas. Methods We collected mt DNA sequence data from 1355 individuals from 110 sampling locations and data from nine microsatellite loci from 931 individuals from 37 locations. We assessed the phylogenetic relationships and geographical distribution of mt DNA haplotypes and conducted historical demographic analyses. We used a Bayesian clustering analysis method to detect potential hybridization between glacial lineages. Results Two highly divergent mt DNA lineages were identified in the Arctic region with distinct but overlapping geographic distributions: one in Beringia and the other over the entire Arctic Archipelago and coastal mainland east of Alaska. The microsatellite data also implied the existence of these two lineages. Evidence of hybridization was detected between the Arctic lineage and an Atlantic lineage in eastern North America. Main conclusions Our data suggested survival and recolonization from two northern glacial refugia: one in Beringia and another in a smaller refugium, perhaps in the Arctic Archipelago itself or a separate refugium within Beringia. Patterns of hybridization detected supported the presence of a secondary contact zone between glacial lineages in the eastern Canadian Arctic.

Recreational trampling negatively impacts vegetation structure of an Australian biodiversity hotspot - S. Mason; D. Newsome; S. Moore; R. Admiraal (Biodiversity and Conservation, 2015)

Modernizing Pharmaceutical Manufacturing: from Batch to Continuous Production - Sau L. Lee; Thomas F. O’Connor; Xiaochuan Yang; Celia N. Cruz; Sharmista Chatterjee; Rapti D. Madurawe; Christine M. V. Moore; Lawrence X. Yu; Janet Woodcock (Journal of Pharmaceutical Innovation, 2015)

Agathis bishopi (Hymenoptera: Braconidae) as a Potential Tool for Detecting Oranges Infested with Thaumatotibia leucotreta (Lepidoptera: Tortricidae) - Kennedy Zimba; Martin P. Hill; Sean D. Moore; Unathi Heshula (Journal of Insect Behavior, 2015)

Recent Bayesian approaches for spatial analysis of 2-D images with application to environmental modelling - M. G. Falk; C. L. Alston; C. A. McGrory; S. Clifford; E. A. Heron; D. Leonte; M. Moores; C. D. Walsh; A. N. Pettitt; K. L. Mengersen (Environmental and Ecological Statistics, 2015)

Restoration using Acropora cervicornis at the T/V MARGARA grounding site - S. P. Griffin; M. I. Nemeth; T. D. Moore; B. Gintert (Coral Reefs, 2015)

Genetic and biological characterisation of a novel Plutella xylostella granulovirus, PlxyGV-SA - Fatima Abdulkadir; Caroline Knox; Tamryn Marsberg; Martin P. Hill; Sean D. Moore (BioControl, 2015)

Local Quantification of Wall Thickness and Intraluminal Thrombus Offer Insight into the Mechanical Properties of the Aneurysmal Aorta - Giampaolo Martufi; Alessandro Satriano; Randy D. Moore; David A. Vorp; Elena S. Di Martino (Annals of Biomedical Engineering, 2015)

Acute Methylenedioxypyrovalerone Toxicity - Blake A. Froberg; Michael Levine; Michael C. Beuhler; Bryan S. Judge; Philip W. Moore; Kristin M. Engebretsen; Nathanael J. Mckeown; Christopher D. Rosenbaum; Amy C. Young; Daniel E. Rusyniak (Journal of Medical Toxicology, 2015)

Social Cognition and Brain Morphology: Implications for Developmental Brain Dysfunction - David W. Evans; Steven M. Lazar; K. B. Boomer; Aaron D. Mitchel; Andrew M. Michael; Gregory J. Moore (Brain Imaging and Behavior, 2015)

Erratum to: Strategies African-American Cancer Survivors Use to Overcome Fears and Fatalistic Attitudes - Jill B. Hamilton; Nakia C. Best; Kayoll V. Galbraith; Valarie C. Worthy; Angelo D. Moore (Journal of Cancer Education, 2015)

Responses of leaf beetle larvae to elevated [CO2] and temperature depend on Eucalyptus species - Andrew N. Gherlenda; Anthony M. Haigh; Ben D. Moore; Scott N. Johnson; Markus Riegler (Oecologia, 2015)

Association of mitochondrial DNA levels with frailty and all-cause mortality - Foram N. Ashar; Anna Moes; Ann Z. Moore; Megan L. Grove; Paulo H. M. Chaves; Josef Coresh; Anne B. Newman; Amy M. Matteini; Karen Bandeen-Roche; Eric Boerwinkle; Jeremy D. Walston; Dan E. Arking (Journal of Molecular Medicine, 2015)

Emergent stability in a large, free‐flowing watershed - Jonathan W. Moore; Michael P. Beakes; Holly K. Nesbitt; Justin D. Yeakel; David A. Patterson; Lisa A. Thompson; Corey C. Phillis; Douglas C. Braun; Corinna Favaro; David Scott; Charmaine Carr-Harris; William I. Atlas (Ecology, 2015)
While it is widely recognized that financial stock portfolios can be stabilized through diverse investments, it is also possible that certain habitats can function as natural portfolios that stabilize ecosystem processes. Here we propose and examine the hypothesis that free‐flowing river networks act as such portfolios and confer stability through their integration of upstream geological, hydrological, and biological diversity. We compiled a spatially (142 sites) and temporally (1980–present) extensive data set on fisheries, water flows, and temperatures, from sites within one of the largest watersheds in the world that remains without dams on its mainstem, the Fraser River, British Columbia, Canada. We found that larger catchments had more stable fisheries catches, water flows, and water temperatures than smaller catchments. These data provide evidence that free‐flowing river networks function as hierarchically nested portfolios with stability as an emergent property. Thus, free‐flowing river networks can represent a natural system for buffering variation and extreme events.

Fragmented Tasmania: the transition from Rodinia to Gondwana - D. H. Moore; P. G. Betts; M. Hall (Australian Journal of Earth Sciences, 2015)

Consequential cradle-to-gate carbon footprint of water treatment chemicals using simple and complex marginal technologies for electricity supply - Juan Pablo Alvarez-Gaitan; Michael D. Short; Gregory M. Peters; Iain MacGill; Stephen Moore (The International Journal of Life Cycle Assessment, 2014)

Stability and Broad-Sense Heritability of Mineral Content in Potato: Copper and Sulfur - C. R. Brown; K. G. Haynes; M. Moore; M. J. Pavek; D. C. Hane; S. L. Love; R. G. Novy; J. C. Miller (American Journal of Potato Research, 2014)

Overcoming skepticism with education: interacting influences of worldview and climate change knowledge on perceived climate change risk among adolescents - Kathryn T. Stevenson; M. Nils Peterson; Howard D. Bondell; Susan E. Moore; Sarah J. Carrier (Climatic Change, 2014)

The Effects of Bt Corn on Rusty Crayfish (Orconectes Rusticus) Growth and Survival - Matthew D. Linn; Paul A. Moore (Archives of Environmental Contamination and Toxicology, 2014)

Real Exposure: Field Measurement of Chemical Plumes in Headwater Streams - David D. Edwards; Paul A. Moore (Archives of Environmental Contamination and Toxicology, 2014)

How much does a swimming, underweight, entangled right whale ( Eubalaena glacialis ) weigh? Calculating the weight at sea, to facilitate accurate dosing of sedatives to enable disentanglement - Ashley Barratclough; Paul D. Jepson; Philip K. Hamilton; Carolyn A. Miller; Kenady Wilson; Michael J. Moore (Marine Mammal Science, 2014)

Four species of arboreal folivore show differential tolerance to a secondary metabolite - Lora M. Jensen; Ian R. Wallis; Karen J. Marsh; Ben D. Moore; Natasha L. Wiggins; William J. Foley (Oecologia, 2014)

Anthropogenic‐based regional‐scale factors most consistently explain plot‐level exotic diversity in grasslands - Andrew S. MacDougall; Joseph R. Bennett; Jennifer Firn; Eric W. Seabloom; Elizabeth T. Borer; Eric M. Lind; John L. Orrock; W. Stanley Harpole; Yann Hautier; Peter B. Adler; Elsa Cleland; Kendi Davies; et al. (Global Ecology and Biogeography, 2014)
Aim Evidence linking the accumulation of exotic species to the suppression of native diversity is equivocal, often relying on data from studies that have used different methods. Plot‐level studies often attribute inverse relationships between native and exotic diversity to competition, but regional abiotic filters, including anthropogenic influences, can produce similar patterns. We seek to test these alternatives using identical scale‐dependent sampling protocols in multiple grasslands on two continents. Location Thirty‐two grassland sites in N orth A merica and A ustralia. Methods We use multiscale observational data, collected identically in grain and extent at each site, to test the association of local and regional factors with the plot‐level richness and abundance of native and exotic plants. Sites captured environmental and anthropogenic gradients including land‐use intensity, human population density, light and soil resources, climate and elevation. Site selection occurred independently of exotic diversity, meaning that the numbers of exotic species varied randomly thereby reducing potential biases if only highly invaded sites were chosen. Results Regional factors associated directly or indirectly with human activity had the strongest associations with plot‐level diversity. These regional drivers had divergent effects: urban‐based economic activity was associated with high exotic : native diversity ratios; climate‐ and landscape‐based indicators of lower human population density were associated with low exotic : native ratios. Negative correlations between plot‐level native and exotic diversity, a potential signature of competitive interactions, were not prevalent; this result did not change along gradients of productivity or heterogeneity. Main conclusion We show that plot‐level diversity of native and exotic plants are more consistently associated with regional‐scale factors relating to urbanization and climate suitability than measures indicative of competition. These findings clarify the long‐standing difficulty in resolving drivers of exotic diversity using single‐factor mechanisms, suggesting that multiple interacting anthropogenic‐based processes best explain the accumulation of exotic diversity in modern landscapes.

Evolution of reaction center mimics to systems capable of generating solar fuel - Benjamin D. Sherman; Michael D. Vaughn; Jesse J. Bergkamp; Devens Gust; Ana L. Moore; Thomas A. Moore (Photosynthesis Research, 2014)

FXR-induced secretion of FGF15/19 inhibits CYP27 expression in cholangiocytes through p38 kinase pathway - Dongju Jung; J. Philippe York; Li Wang; Chaofeng Yang; Aijun Zhang; Heather L. Francis; Paul Webb; Wallace L. McKeehan; Gianfranco Alpini; Gene D. LeSage; David D. Moore; Xuefeng Xia (Pflügers Archiv - European Journal of Physiology, 2014)

Tree species partition N uptake by soil depth in boreal forests - D. Houle; J.-D. Moore; R. Ouimet; C. Marty (Ecology, 2014)
It is recognized that the coexistence of herbaceous species in N‐depleted habitats can be facilitated by N partitioning; however, the existence of such a phenomenon for trees has not yet been demonstrated. Here, we show from both foliage and soil 15 N natural abundance values and from a 12‐year in situ 15 N addition experiment, that black spruce ( Picea mariana ) and jack pine ( Pinus banksiana ), two widespread species of the Canadian boreal forest, take up N at different depths. While black spruce takes up N from the organic soil, jack pine acquires it deeper within the highly N‐depleted mineral soil. Systematic difference in foliar 15 N natural abundance between the two species across seven sites distributed throughout the eastern Canadian boreal forest shows that N spatial partitioning is a widespread phenomenon. Distinct relationships between δ 15 N and N concentration in leaves of both species further emphasize their difference in N acquisition strategies. This result suggests that such complementary mechanisms of N acquisition could facilitate tree species coexistence in such N‐depleted habitats and could contribute to the positive biodiversity–productivity relationship recently revealed for the eastern Canadian boreal forest, where jack pine is present. It also has implications for forest management and provides new insights to interpret boreal forest regeneration following natural or anthropogenic perturbations.

Mark recapture estimates of dispersal ability and observations on the territorial behaviour of the rare hoverfly, Hammerschmidtia ferruginea (Diptera, Syrphidae) - E. L. Rotheray; L. F. Bussière; Pete Moore; Linnea Bergstrom; D. Goulson (Journal of Insect Conservation, 2014)

Feeding rates of a mammalian browser confirm the predictions of a ‘foodscape’ model of its habitat - Karen J. Marsh; Ben D. Moore; Ian R. Wallis; William J. Foley (Oecologia, 2014)

Importance of macroalgal fields as coral reef fish nursery habitat in north-west Australia - R. D. Evans; S. K. Wilson; S. N. Field; J. A. Y. Moore (Marine Biology, 2014)

Synchronisation and stability in river metapopulation networks - J. D. Yeakel; J. W. Moore; P. R. Guimarães; M. A. M. de Aguiar (Ecology Letters, 2014)
Spatial structure in landscapes impacts population stability. Two linked components of stability have large consequences for persistence: first, statistical stability as the lack of temporal fluctuations; second, synchronisation as an aspect of dynamic stability, which erodes metapopulation rescue effects. Here, we determine the influence of river network structure on the stability of riverine metapopulations. We introduce an approach that converts river networks to metapopulation networks, and analytically show how fluctuation magnitude is influenced by interaction structure. We show that river metapopulation complexity (in terms of branching prevalence) has nonlinear dampening effects on population fluctuations, and can also buffer against synchronisation. We conclude by showing that river transects generally increase synchronisation, while the spatial scale of interaction has nonlinear effects on synchronised dynamics. Our results indicate that this dual stability – conferred by fluctuation and synchronisation dampening – emerges from interaction structure in rivers, and this may strongly influence the persistence of river metapopulations.

A non-destructive method for identifying the sex of ant larvae - C. A. Penick; J. Ebie; D. Moore (Insectes Sociaux, 2014)

Business analysis and market potential of drug screening technology for preventive and personalized therapy - Igor V Volchek; Philip D Cotter; Andrei S Petrov; Mathew W Moore (EPMA Journal, 2014)

Phenological responses of juvenile pecan and white oak on an upland site - D. M. Burner; D. K. Brauer; J. L. Snider; C. A. Harrington; P. A. Moore (Agroforestry Systems, 2014)

A prospective evaluation of changes in brain structure and cognitive functions in adult stem cell transplant recipients - D. D. Correa; J. C. Root; R. Baser; D. Moore; K. K. Peck; E. Lis; T. B. Shore; H. T. Thaler; A. Jakubowski; N. Relkin (Brain Imaging and Behavior, 2013)

Stability and Broad-Sense Heritability of Mineral Content in Potato: Potassium and Phosphorus - C. R. Brown; K. G. Haynes; M. Moore; M. J. Pavek; D. C. Hane; S. L. Love; R. G. Novy (American Journal of Potato Research, 2013)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Thermodynamic parameters for Eu(III) binding to Datura innoxia root material - Jessica L. Moore; Gary D. Rayson (BioMetals, 2013)

A faecal index of diet quality that predicts reproductive success in a marsupial folivore - Hannah R. Windley; Ian R. Wallis; Jane L. DeGabriel; Ben D. Moore; Christopher N. Johnson; William J. Foley (Oecologia, 2013)

Three nights of sleep deprivation does not alter thermal strain during exercise in the heat - Jonathan P. Moore; Adam D. Harper Smith; Umberto Di Felice; Neil P. Walsh (European Journal of Applied Physiology, 2013)

A hybrid life cycle assessment of water treatment chemicals: an Australian experience - Juan Pablo Alvarez-Gaitan; Gregory M. Peters; Hazel V. Rowley; Stephen Moore; Michael D. Short (The International Journal of Life Cycle Assessment, 2013)

Towards improved socio-economic assessments of ocean acidification’s impacts - Nathalie Hilmi; Denis Allemand; Sam Dupont; Alain Safa; Gunnar Haraldsson; Paulo A. L. D. Nunes; Chris Moore; Caroline Hattam; Stéphanie Reynaud; Jason M. Hall-Spencer; Maoz Fine; Carol Turley; et al. (Marine Biology, 2013)

Radon in indoor concentrations and indoor concentrations of metal dust particles in museums and other public buildings - G. L. Carneiro; D. Braz; E. F. de Jesus; S. M. Santos; K. Cardoso; A. A. Hecht; Moore K. Dias da Cunha (Environmental Geochemistry and Health, 2013)

Puny males punch above their weight to preserve genetic diversity in a declining A tlantic salmon population - J.‐S. Moore; D. J. Fraser (Molecular Ecology, 2013)
Many salmonid fish populations have anadromous (i.e. migratory) and nonanadromous individuals co‐existing in sympatry. The nonanadromous individuals, frequently males, mature at a much smaller size in freshwater without undergoing marine migrations and often successfully fertilize many eggs laid by anadromous females. Because these small males do not recruit to fisheries, they are often not regarded in high esteem by fishers. In this issue of Molecular Ecology , Johnstone et al . ( ) demonstrate that by substantially contributing to reproduction, such males help maintain genetic diversity in a declining population of A tlantic salmon ( S almo salar ). Their results show that estimates of effective population size ( N e ), obtained by counting the number of anadromous adults returning from sea and correcting for unequal sex ratios, are lower than estimates generated from genetic markers. Many mechanisms are expected to reduce N e below the adult census population size ( N ); the opposite pattern of N e > N observed by Johnstone et al . ( ) is difficult to explain unless the reproductive effort of nonanadromous males is accounted for. The results have important implications for the conservation of small populations and highlight the challenges of relating N e to N in organisms with complex life histories.

Climate change and broadacre livestock production across southern A ustralia. 1. Impacts of climate change on pasture and livestock productivity, and on sustainable levels of profitability - Andrew D. Moore; Afshin Ghahramani (Global Change Biology, 2013)
Broadacre livestock production is a major but highly diverse component of agriculture in A ustralia that will be significantly exposed to predicted changes in climate over coming decades. We used the GRAZPLAN simulation models to assess the impacts of climate change under the SRES A2 scenario across southern Australia. Climate change impacts were examined across space (25 representative locations) and time (1970–99, 2030, 2050 and 2070 climate) for each of five livestock enterprises. Climate projection uncertainty was considered by analysing projections from four global circulation models ( GCM s). Livestock production scenarios were compared at their profit‐maximizing stocking rate, constrained to ensure that risks of soil erosion were acceptable. Impacts on net primary productivity ( ANPP ) varied widely between GCM projections; the average declines from historical climate were 9% in 2030, 7% in 2050 and 14% in 2070. Declines in ANPP were larger at lower‐rainfall locations. Sensitivity of ANPP to changes in rainfall ranged from 0.4 to 1.7, to temperature increase from −0.15 to +0.07 °C −1 and to CO 2 increase from 0.11 to 0.32. At most locations the dry summer period lengthened, exacerbating the greater erosion risk due to lower ANPP . Transpiration efficiency of pastures increased by 6–25%, but the proportion of ANPP that could safely be consumed by livestock fell sharply so that operating profit (at constant prices) fell by an average of 27% in 2030, 32% in 2050 and 48% in 2070. This amplification of ANPP reductions into larger profitability declines is likely to generalize to other extensive livestock systems. Profit declines were most marked at drier locations, with operating losses expected at 9 of the 25 locations by 2070. Differences between livestock enterprises were smaller than differences between locations and dates. Future research into climate change impacts on A ustralian livestock production needs to emphasise the dry margin of the cereal‐livestock zone.

Bleaching, coral mortality and subsequent survivorship on a West Australian fringing reef - M. Depczynski; J. P. Gilmour; T. Ridgway; H. Barnes; A. J. Heyward; T. H. Holmes; J. A. Y. Moore; B. T. Radford; D. P. Thomson; P. Tinkler; S. K. Wilson (Coral Reefs, 2013)

Shark predation on North Atlantic right whales ( Eubalaena glacialis ) in the southeastern United States calving ground - Jessica K. D. Taylor; John W. Mandelman; William A. McLellan; Michael J. Moore; Gregory B. Skomal; David S. Rotstein; Scott D. Kraus (Marine Mammal Science, 2013)

Modelling the migratory behaviour of salmonids in relation to environmental and physiological parameters using telemetry data - B. BENDALL; A. MOORE; D. MAXWELL; P. DAVISON; N. EDMONDS; D. ARCHER; D. SOLOMON; V. GREEST; R. WYATT; K. BROAD (Fisheries Management and Ecology, 2012)
Advances in the field of telemetry techniques during the last few decades have greatly expanded our knowledge on migratory behaviour and provided the opportunity to obtain practically useful data for the conservation and management of salmonid populations. However, applying this information to the development of much needed population‐based migration models has been limited. Furthermore, this research has generally been restricted to assessing the role of river flow on fish movement. Models derived from a 6‐year telemetry study on the movements of Atlantic salmon, Salmo salar L., and sea trout, Salmo trutta L., in the River Tyne are presented together with an assessment of counter data from the same river to highlight the importance of additional environmental and physiological parameters in regulating fish movement. The data are discussed in relation to the advantages of telemetry data, the need to develop predictive models, the statistical methods used and the potential direction of future work in this area.

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

The International Mouse Phenotyping Consortium: past and future perspectives on mouse phenotyping - Steve D. M. Brown; Mark W. Moore (Mammalian Genome, 2012)

Plant pest and disease diagnosis using electronic nose and support vector machine approach - Reza Ghaffari; Jullada Laothawornkitkul; Daciana Iliescu; Evor Hines; Mark Leeson; Richard Napier; Jason P Moore; Nigel D Paul; C Nicholas Hewitt; Jane E Taylor (Journal of Plant Diseases and Protection, 2012)

Securing the Demographic and Genetic Future of Tuatara through Assisted Colonization - KIMBERLY A. MILLER; HILARY C. MILLER; JENNIFER A. MOORE; NICOLA J. MITCHELL; ALISON CREE; FRED W. ALLENDORF; STEPHEN D. SARRE; SUSAN N. KEALL; NICOLA J. NELSON (Conservation Biology, 2012)
Climate change poses a particular threat to species with fragmented distributions and little or no capacity to migrate. Assisted colonization, moving species into regions where they have not previously occurred, aims to establish populations where they are expected to survive as climatic envelopes shift. However, adaptation to the source environment may affect whether species successfully establish in new regions. Assisted colonization has spurred debate among conservation biologists and ecologists over whether the potential benefits to the threatened species outweigh the potential disruption to recipient communities. In our opinion, the debate has been distracted by controversial examples, rather than cases where assisted colonization may be a viable strategy. We present a strategic plan for the assisted migration of tuatara ( Sphenodon punctatus ), an endemic New Zealand reptile. The plan includes use of extant populations as reference points for comparisons with assisted‐colonization populations with respect to demography, phenotypic plasticity, and phenology; optimization of genetic variation; research to fill knowledge gaps; consideration of host and recipient communities; and inclusion of stakeholders in the planning stage. When strategically planned and monitored, assisted colonization could meet conservation and research goals and ultimately result in the establishment of long‐term sustainable populations capable of persisting during rapid changes in climate.

Stability and Broad-Sense Heritability of Mineral Content in Potato: Calcium and Magnesium - C. R. Brown; K. G. Haynes; M. Moore; M. J. Pavek; D. C. Hane; S. L. Love; R. G. Novy; J. C. Miller (American Journal of Potato Research, 2012)

Parasites and Dung Beetles as Ecosystem Engineers in a Forest Ecosystem - Broox G. V. Boze; Alexander D. Hernandez; Michael A. Huffman; Janice Moore (Journal of Insect Behavior, 2012)

Estimation of forest harvesting-induced stream temperature changes and bioenergetic consequences for cutthroat trout in a coastal stream in British Columbia, Canada - J. A. Leach; R. D. Moore; S. G. Hinch; T. Gomi (Aquatic Sciences, 2012)

Parasites as indicators of movement and population connectivity of a non‐diadromous, tropical estuarine teleost: king threadfin Polydactylus macrochir - B. R. Moore; D. J. Welch; S. J. Newman; R. J. G. Lester (Journal of Fish Biology, 2012)
Temporal and spatial patterns in parasite assemblages were examined to evaluate the degree of movement and connectivity of post‐recruitment life‐history stages of a large, non‐diadromous tropical estuarine teleost, king threadfin Polydactylus macrochir , collected from 18 locations across northern Australia. Ten parasites types (juvenile stages of two nematodes and seven cestodes, and adults of an acanthocephalan) were deemed to be suitable for use as biological tags, in that they were considered to have a long residence time in the fish, were relatively easy to find and were morphologically very different to each other which aided discrimination. Univariate and discriminant function analysis of these parasites revealed little difference in temporal replicates collected from five locations, suggesting that the parasite communities were stable over the timeframes explored. Univariate, discriminant function, and Bray–Curtis similarity analyses indicated significant spatial heterogeneity, with Bray–Curtis classification accuracies ranging from 55 to 100% for locations in north‐western and northern Australia, 24 to 88% in the Gulf of Carpentaria, and 39 to 88% on the east coast of Queensland. Few differences were observed among locations separated by P . macrochir in that they indicate a complex population structure across northern Australia. These results should be considered when reviewing the management arrangements for this species.

The roles of climate and soil nutrients in shaping the life histories of grasses native to the Cape Floristic Region - G. Anthony Verboom; Timothy E. Moore; Vera Hoffmann; Michael D. Cramer (Plant and Soil, 2012)

Species, sex, size and male maturity composition of previously unreported elasmobranch landings in Kuwait, Qatar and Abu Dhabi Emirate - A. B. M. Moore; I. D. McCarthy; G. R. Carvalho; R. Peirce (Journal of Fish Biology, 2012)
This paper presents data from the first major survey of the diversity, biology and fisheries of elasmobranchs in the Persian (Arabian) Gulf. Substantial landings of elasmobranchs, usually as gillnet by‐catch, were recorded in Kuwait, Qatar and the Emirate of Abu Dhabi (part of the United Arab Emirates), although larger elasmobranchs from targeted line fisheries were landed in Abu Dhabi. The elasmobranch fauna recorded was distinctive and included species that are undescribed, rare and have a highly restricted known distribution. Numerical abundance was dominated by sharks ( c. 80%), of which carcharhinids were by far the most important. The milk shark Rhizoprionodon acutus and whitecheek shark Carcharhinus dussumieri together comprised just under half of all recorded individuals. Around 90% of recorded sharks were small (50–90 cm total length, L T ) individuals, most of which were mature individuals of species with a small maximum size ( L T ), although immature individuals of larger species ( e.g . Carcharhinus sorrah and other Carcharhinus spp.) were also important. The most frequently recorded batoid taxa were cownose rays Rhinoptera spp., an undescribed whipray, and the granulated guitarfish Rhinobatos granulatus. The first size, sex and maturity data for a wide range of Gulf elasmobranch species are presented (including L T at 50% maturity for males of four shark species) and include some notable differences from other locations in the Indo‐West Pacific Ocean. A number of concerns regarding the sustainability of the fishery were highlighted by this study, notably that most of the batoid species recorded are classed by the IUCN Red List as vulnerable, endangered, data deficient or not evaluated. Despite their considerable elasmobranch landings, none of the three countries sampled have developed a ‘Shark Plan’ as encouraged to do so under the FAO International Plan of Action: Sharks. Furthermore, Kuwait and Qatar currently report zero or no elasmobranch landings to the FAO.

Total ozone and surface UV trends in the United Kingdom: 1979–2008 - Andrew R. D. Smedley; John S. Rimmer; David Moore; Ralf Toumi; Ann R. Webb (International Journal of Climatology, 2012)
In this study we present the UK's total ozone and UV data records, their measurement and preliminary processing, and discuss the observed trends. Notably, we combine the records from the Camborne and Reading sites to obtain a single ozone data series for southern England—a total duration of 30 years. Two‐section linear trends and cross‐over years are determined for Lerwick and southern England, both annually and seasonally. The observed minimum using this technique in the UK ozone record is found to occur during the year 1993. Significant trends of − 4.8% per decade for southern England and − 5.8% per decade for Lerwick are seen prior to the mid‐1990s; the rate of decrease in the UK being at the upper limit of other European stations. No significant ozone trend is seen for the latter period in either location in contrast with Europe as a whole. We, additionally, compare the satellite‐derived total ozone trends for both locations. The UV record at Reading showed a significant trend from 1993 to 2008 in the daily maximum UV index record (6.6% per decade), despite no significant recovery in the total ozone data series, suggesting a reduction in cloud cover during the midday period. Filtering data to remove other factors shows the erythemal UV to have an ozone‐dependent trend of − 0.11% per year, but this is not statistically significant. We find no correlation between anomalies in the surface UV and total ozone records suggesting that the majority of the inter‐annual variability is due to changes in cloud cover and other effects. Copyright © 2011 Royal Meteorological Society

Rapid Biomass Quality Determination of Corn Stover Using Near-Infrared Reflectance Spectroscopy - Patrick T. Murphy; Kenneth J. Moore; D. Raj Raman; Robert P. Anex; Steven L. Fales (BioEnergy Research, 2012)

Editorial - Edwin D. W. Moore; Geoffrey O. Wasteneys (Protoplasma, 2012)

The structure and functioning of the couplon in the mammalian cardiomyocyte - Parisa Asghari; David R. L. Scriven; Jeremy Hoskins; Nicola Fameli; Cornelis van Breemen; Edwin D. W. Moore (Protoplasma, 2012)

Characterization and developmental expression of genes encoding the early carotenoid biosynthetic enzymes in Citrus paradisi Macf. - Marcio G. C. Costa; Cristina D. Moreira; John R. Melton; Wagner C. Otoni; Gloria A. Moore (Molecular Biology Reports, 2012)

Artificial gravity training reduces bed rest-induced cardiovascular deconditioning - Michael B. Stenger; Joyce M. Evans; Charles F. Knapp; Stuart M. C. Lee; Tiffany R. Phillips; Sondra A. Perez; Alan D. Moore; William H. Paloski; Steven H. Platts (European Journal of Applied Physiology, 2012)

Effects of biotic disturbances on forest carbon cycling in the U nited S tates and C anada - Jeffrey A. Hicke; Craig D. Allen; Ankur R. Desai; Michael C. Dietze; Ronald J. Hall; Edward H. (Ted) Hogg; Daniel M. Kashian; David Moore; Kenneth F. Raffa; Rona N. Sturrock; James Vogelmann (Global Change Biology, 2012)
Forest insects and pathogens are major disturbance agents that have affected millions of hectares in N orth A merica in recent decades, implying significant impacts to the carbon ( C ) cycle. Here, we review and synthesize published studies of the effects of biotic disturbances on forest C cycling in the U nited S tates and C anada. Primary productivity in stands was reduced, sometimes considerably, immediately following insect or pathogen attack. After repeated growth reductions caused by some insects or pathogens or a single infestation by some bark beetle species, tree mortality occurred, altering productivity and decomposition. In the years following disturbance, primary productivity in some cases increased rapidly as a result of enhanced growth by surviving vegetation, and in other cases increased slowly because of lower forest regrowth. In the decades following tree mortality, decomposition increased as a result of the large amount of dead organic matter. Net ecosystem productivity decreased immediately following attack, with some studies reporting a switch to a C source to the atmosphere, and increased afterward as the forest regrew and dead organic matter decomposed. Large variability in C cycle responses arose from several factors, including type of insect or pathogen, time since disturbance, number of trees affected, and capacity of remaining vegetation to increase growth rates following outbreak. We identified significant knowledge gaps, including limited understanding of carbon cycle impacts among different biotic disturbance types (particularly pathogens), their impacts at landscape and regional scales, and limited capacity to predict disturbance events and their consequences for carbon cycling. We conclude that biotic disturbances can have major impacts on forest C stocks and fluxes and can be large enough to affect regional C cycling. However, additional research is needed to reduce the uncertainties associated with quantifying biotic disturbance effects on the N orth A merican C budget.

A New Tool for Inundation Modeling: Community Modeling Interface for Tsunamis (ComMIT) - V. V. Titov; C. W. Moore; D. J. M. Greenslade; C. Pattiaratchi; R. Badal; C. E. Synolakis; U. Kânoğlu (Pure and Applied Geophysics, 2011)

A primer for data assimilation with ecological models using Markov Chain Monte Carlo (MCMC) - J. M. Zobitz; A. R. Desai; D. J. P. Moore; M. A. Chadwick (Oecologia, 2011)

Advances in winter pulse pathology research in Australia - Moin U. Salam; Jennifer A. Davidson; Geoff J. Thomas; Rebecca Ford; Roger A. C. Jones; Kurt D. Lindbeck; William J. MacLeod; Rohan B. E. Kimber; Jean Galloway; Nitin Mantri; Joop A. G. van Leur; Brenda A. Coutts; et al. (Australasian Plant Pathology, 2011)

Current concentrations and spatial and temporal trends in mercury in Great Lakes Herring Gull eggs, 1974–2009 - D. V. Chip Weseloh; David J. Moore; Craig E. Hebert; Shane R. de Solla; Birgit M. Braune; Daryl J. McGoldrick (Ecotoxicology, 2011)

A geological interpretation of the Echuca magnetotelluric survey, Victoria - Z. R. Dennis; D. H. Moore; J. P. Cull (Australian Journal of Earth Sciences, 2011)

Synthesis and characterization of an unsymmetrical cobalt(III) active site analogue of nitrile hydratase - Jennifer K. Angelosante; Lauren M. Schopp; Breia J. Lewis; Amber D. Vitalo; Dustin T. Titus; Rebecca A. Swanson; April N. Stanley; Brendan P. Abolins; Michelle J. Frome; Lisa E. Cooper; David L. Tierney; Curtis Moore; et al. (JBIC Journal of Biological Inorganic Chemistry, 2011)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 1. Overview and Problem Formulation - Donald D. MacDonald; Dwayne R. J. Moore; Christopher G. Ingersoll; Dawn E. Smorong; R. Scott Carr; Ron Gouguet; David Charters; Duane Wilson; Tom Harris; Jon Rauscher; Susan Roddy; John Meyer (Archives of Environmental Contamination and Toxicology, 2011)

Residual Effects of Fresh and Composted Dairy Manure Applications on Potato Production - Amber D. Moore; Nora L. Olsen; Anna M. Carey; April B. Leytem (American Journal of Potato Research, 2011)

Designing Interventions to Overcome Poor Numeracy and Improve Medication Adherence in Chronic Illness, Including HIV/Aids - John O. Moore; Edward W. Boyer; Steven Safren; Gregory K. Robbins; Edwin D. Boudreaux; Rochelle Rosen; Bruce Barton; Frank Moss (Journal of Medical Toxicology, 2011)

Biomass Yield and Quality of Reed Canarygrass under Five Harvest Management Systems for Bioenergy Production - M. Hammad Nadeem Tahir; Michael D. Casler; Kenneth J. Moore; E. Charles Brummer (BioEnergy Research, 2011)

Virulence of a South African isolate of the Cryptophlebia leucotreta granulovirus to Thaumatotibia leucotreta neonate larvae - Sean D. Moore; Don A. Hendry; Garth I. Richards (BioControl, 2011)

Crustal architecture of central Victoria: results from the 2006 deep crustal reflection seismic survey - R. A. Cayley; R. J. Korsch; D. H. Moore; R. D. Costelloe; A. Nakamura; C. E. Willman; T. J. Rawling; V. J. Morand; P. B. Skladzien; P. J. O'Shea (Australian Journal of Earth Sciences, 2011)

Paleogene basalts prove early uplift of Victoria's Eastern Uplands - G. R. Holdgate; M. W. Wallace; S. J. Gallagher; B. E. Wagstaff; D. Moore (Australian Journal of Earth Sciences, 2011)

Magnetotelluric survey for undercover structural mapping, Central Victoria - Z. R. Dennis; D. H. Moore; J. P. Cull (Australian Journal of Earth Sciences, 2011)

Nature and nurture in the dynamics of C, N and P during litter decomposition in Canadian forests - Tim R. Moore; J. A. Trofymow; Cindy E. Prescott; B. D. Titus (Plant and Soil, 2011)

Structural Interpretation in Composite Systems Using Powder X-ray Diffraction: Applications of Error Propagation to the Pair Distribution Function - Michael D. Moore; Zhenqi Shi; Peter L. D. Wildfong (Pharmaceutical Research, 2010)

Palatability mapping: a koala's eye view of spatial variation in habitat quality - Ben D. Moore; Ivan R. Lawler; Ian R. Wallis; Colin M. Beale; William J. Foley (Ecology, 2010)
Ecologists trying to understand the value of habitat to animals must first describe the value of resources contained in the habitat to animals and, second, they must describe spatial variation in resource quality at a resolution relevant to individual animal foraging. We addressed these issues in a study of koalas ( Phascolarctos cinereus ) in a Eucalyptus woodland. We measured beneficial and deterrent chemical characteristics as well as the palatability of trees using a near‐infrared spectroscopic model based on direct feeding experiments. Tree use by koalas was influenced by tree size and foliar quality but was also context‐dependent: trees were more likely to be visited if they were surrounded by small, unpalatable trees or by large, palatable trees. Spatial autocorrelation analysis and several mapping approaches demonstrated that foliar quality is spatially structured in the woodland at a scale relevant to foraging decisions by koalas and that the spatial structure is an important component of habitat quality.

Estimating parameters of a forest ecosystem C model with measurements of stocks and fluxes as joint constraints - Andrew D. Richardson; Mathew Williams; David Y. Hollinger; David J. P. Moore; D. Bryan Dail; Eric A. Davidson; Neal A. Scott; Robert S. Evans; Holly Hughes; John T. Lee; Charles Rodrigues; Kathleen Savage (Oecologia, 2010)

Mitochondrial retention of Opa1 is required for mouse embryogenesis - Billie A. Moore; Gladys D. Gonzalez Aviles; Christine E. Larkins; Michael J. Hillman; Tamara Caspary (Mammalian Genome, 2010)

Erratum to: Mass spectral data for 64 eluted peptides and structural modeling define peptide binding preferences for class I alleles in two chicken MHC-B haplotypes associated with opposite responses to Marek’s disease - Mark A. Sherman; Ronald M. Goto; Roger E. Moore; Henry D. Hunt; Terry D. Lee; Marcia M. Miller (Immunogenetics, 2010)

The effects of farming system, habitat type and bait type on the isolation of entomopathogenic fungi from citrus soils in the Eastern Cape Province, South Africa - T. A. Goble; J. F. Dames; M. P Hill; S. D. Moore (BioControl, 2010)

Single receiver phase ambiguity resolution with GPS data - Willy Bertiger; Shailen D. Desai; Bruce Haines; Nate Harvey; Angelyn W. Moore; Susan Owen; Jan P. Weiss (Journal of Geodesy, 2010)

A meta‐analysis of context‐dependency in plant response to inoculation with mycorrhizal fungi - Jason D. Hoeksema; V. Bala Chaudhary; Catherine A. Gehring; Nancy Collins Johnson; Justine Karst; Roger T. Koide; Anne Pringle; Catherine Zabinski; James D. Bever; John C. Moore; Gail W. T. Wilson; John N. Klironomos; et al. (Ecology Letters, 2010)
Ecology Letters (2010) 13: 394–407 Abstract Mycorrhizal fungi influence plant growth, local biodiversity and ecosystem function. Effects of the symbiosis on plants span the continuum from mutualism to parasitism. We sought to understand this variation in symbiotic function using meta‐analysis with information theory‐based model selection to assess the relative importance of factors in five categories: (1) identity of the host plant and its functional characteristics, (2) identity and type of mycorrhizal fungi (arbuscular mycorrhizal vs. ectomycorrhizal), (3) soil fertility, (4) biotic complexity of the soil and (5) experimental location (laboratory vs. field). Across most subsets of the data, host plant functional group and N‐fertilization were surprisingly much more important in predicting plant responses to mycorrhizal inoculation (‘plant response’) than other factors. Non‐N‐fixing forbs and woody plants and C 4 grasses responded more positively to mycorrhizal inoculation than plants with N‐fixing bacterial symbionts and C 3 grasses. In laboratory studies of the arbuscular mycorrhizal symbiosis, plant response was more positive when the soil community was more complex. Univariate analyses supported the hypothesis that plant response is most positive when plants are P‐limited rather than N‐limited. These results emphasize that mycorrhizal function depends on both abiotic and biotic context, and have implications for plant community theory and restoration ecology.

Cliniconeuropathologic correlates of human immunodeficiency virus in the era of antiretroviral therapy - I Everall; F Vaida; N Khanlou; D Lazzaretto; C Achim; S Letendre; D Moore; R Ellis; M Cherner; B Gelman; S Morgello; E Singer; et al. (Journal of NeuroVirology, 2009)

Asenapine effects in animal models of psychosis and cognitive function - Hugh M. Marston; Jared W. Young; Frederic D. C. Martin; Kevin A. Serpa; Christopher L. Moore; Erik H. F. Wong; Lisa Gold; Leonard T. Meltzer; Marc R. Azar; Mark A. Geyer; Mohammed Shahid (Psychopharmacology, 2009)

A Structural Investigation into the Compaction Behavior of Pharmaceutical Composites Using Powder X-ray Diffraction and Total Scattering Analysis - Michael D. Moore; Alison M. Steinbach; Ira S. Buckner; Peter L. D. Wildfong (Pharmaceutical Research, 2009)

Green abalone, Haliotis fulgens infected with the agent of withering syndrome do not express disease signs under a temperature regime permissive for red abalone, Haliotis rufescens - James D. Moore; Christy I. Juhasz; Thea T. Robbins; L. Ignacio Vilchis (Marine Biology, 2009)

Inter-population differences in the tolerance of a marsupial folivore to plant secondary metabolites - Jane L. DeGabriel; Ben D. Moore; Lisa A. Shipley; Andrew K. Krockenberger; Ian R. Wallis; Christopher N. Johnson; William J. Foley (Oecologia, 2009)

Hepatic P450 Enzyme Activity, Tissue Morphology and Histology of Mink (Mustela vison) Exposed to Polychlorinated Dibenzofurans - Jeremy N. Moore; John L. Newsted; Markus Hecker; Matthew J. Zwiernik; Scott D. Fitzgerald; Denise P. Kay; Xiaowei Zhang; Eric B. Higley; Lesa L. Aylward; Kerrie J. Beckett; Robert A. Budinsky; Steven J. Bursian; et al. (Archives of Environmental Contamination and Toxicology, 2009)

C-type natriuretic peptide receptor expression in pancreatic alpha cells - Matthew D. Burgess; Kim D. Moore; Gay M. Carter; Abdel A. Alli; Christopher S. Granda; Hirohito Ichii; Camillo Ricordi; William R. Gower (Histochemistry and Cell Biology, 2009)

Magnetic particles associated with the lateral line of the European eel Anguilla anguilla - A. Moore; W. D. Riley (Journal of Fish Biology, 2009)
Magnetization measurements of the European eel Anguilla anguilla demonstrated the presence of magnetic material concentrated in the region of the mandibular canals of the lateral line system. The data suggest that the material is magnetite, has a size suitable for magnetoreception and is of biogenic origin. The presence of magnetic particles in the lateral line system is discussed in relation to their possible role in allowing the fish to orientate with respect to the geomagnetic field during their extensive oceanic spawning migrations.

Mississippi Oxbow Lake Sediment Quality During an Artificial Flood - S. S. Knight; R. E. Lizotte; M. T. Moore; S. Smith; F. D. Shields (Bulletin of Environmental Contamination and Toxicology, 2009)

Aqueous Solubility Enhancement Through Engineering of Binary Solid Composites: Pharmaceutical Applications - Michael D. Moore; Peter L. D. Wildfong (Journal of Pharmaceutical Innovation, 2009)

The effects of plant defensive chemistry on nutrient availability predict reproductive success in a mammal - Jane L. DeGabriel; Ben D. Moore; William J. Foley; Christopher N. Johnson (Ecology, 2009)
Plants contain a variety of chemical defenses that strongly affect feeding rates in captive mammals, but their effects on the fitness of wild herbivores are largely unknown. This is because the complexity of defensive compounds, and herbivores' counteradaptations to them, make their effects in the wild difficult to measure. We show how tannins interact with protein to produce spatial variation in the nutritional quality of eucalypt foliage, which is related to demography in a wild population of a marsupial folivore, the common brushtail possum ( Trichosurus vulpecula Kerr). Tannins reduced the digestibility of nitrogen (N) in vitro, creating variation in available N concentrations among the home ranges of individual possums in an otherwise homogeneous habitat. This was strongly correlated with reproductive success: females with better quality trees in their home range reproduced more often and had faster‐growing offspring. These results demonstrate a powerful mechanism by which spatial variation in plant chemistry may control herbivore population dynamics in nature.

Monophyly of terrestrial adephagan beetles as indicated by three nuclear genes (Coleoptera: Carabidae and Trachypachidae) - David R. Maddison; Wendy Moore; Michael D. Baker; Tana M. Ellis; Karen A. Ober; Jamie J Cannone; Robin R. Gutell (Zoologica Scripta, 2009)
The beetle suborder Adephaga is traditionally divided into two sections on the basis of habitat, terrestrial Geadephaga and aquatic Hydradephaga. Monophyly of both groups is uncertain, and the relationship of the two groups has implications for inferring habitat transitions within Adephaga. Here we examine phylogenetic relationships of these groups using evidence provided by DNA sequences from all four suborders of beetles, including 60 species of Adephaga, 4 Archostemata, 3 Myxophaga, and 10 Polyphaga. We studied 18S ribosomal DNA and 28S ribosomal DNA, aligned with consideration of secondary structure, as well as the nuclear protein‐coding gene wingless . Independent and combined Bayesian, likelihood, and parsimony analyses of all three genes supported placement of Trachypachidae in a monophyletic Geadephaga, although for analyses of 28S rDNA and some parsimony analyses only if Coleoptera is constrained to be monophyletic. Most analyses showed limited support for the monophyly of Hydradephaga. Outside of Adephaga, there is support from the ribosomal genes for a sister group relationship between Adephaga and Polyphaga. Within the small number of sampled Polyphaga, analyses of 18S rDNA, wingless , and the combined matrix supports monophyly of Polyphaga exclusive of Scirtoidea. Unconstrained analyses of the evolution of habitat suggest that Adephaga was ancestrally aquatic with one transition to terrestrial. However, in analyses constrained to disallow changes from aquatic to terrestrial habitat, the phylogenies imply two origins of aquatic habit within Adephaga.

Male–female differences in the genetic regulation of t-PA and PAI-1 levels in a Ghanaian population - J. A. Schoenhard; F. W. Asselbergs; K. A. Poku; S. A. Stocki; S. Gordon; D. E. Vaughan; N. J. Brown; J. H. Moore; Scott M. Williams (Human Genetics, 2008)

Effect of low dose and moderate dose gamma irradiation on the mechanical properties of bone and soft tissue allografts - Colleen R. Balsly; Andrew T. Cotter; Lisa A. Williams; Barton D. Gaskins; Mark A. Moore; Lloyd Wolfinbarger (Cell and Tissue Banking, 2008)

The impact of a pesticide on the physiology and behaviour of hatchery‐reared Atlantic salmon, Salmo salar , smolts during the transition from fresh water to the marine environment - A. MOORE; D. COTTER; V. QUAYLE; G. ROGAN; R. POOLE; N. LOWER; L. PRIVITERA (Fisheries Management and Ecology, 2008)
Atlantic salmon, Salmo salar L., smolts were exposed to environmental levels of the pesticide atrazine in a hatchery, tagged with acoustic transmitters and released into fresh water at the peak of the smolt run. The subsequent movements of the smolts were monitored within the freshwater and immediate coastal zones using an array of acoustic receivers. In laboratory‐based studies, exposure to a 0.1 μg L −1 concentration of atrazine over a 72‐h period significantly reduced gill Na + K + ATPase activity but not plasma thyroxine (T 4 ) and triiodothyronine (T 3 ) levels compared with the control group, and on transfer to 33‰ saltwater resulted in 100% mortality. However, exposure to atrazine did not have a significant effect on the subsequent movements of the smolts in the freshwater, estuarine and marine environments. The results are discussed in relation to the impact of diffuse pollution on salmon populations.

Reproduction in the sea pen Pennatula phosphorea (Anthozoa: Pennatulacea) from the west coast of Scotland - D. C. B. Edwards; C. G. Moore (Marine Biology, 2008)

Mass spectral data for 64 eluted peptides and structural modeling define peptide binding preferences for class I alleles in two chicken MHC-B haplotypes associated with opposite responses to Marek's disease - Mark A. Sherman; Ronald M. Goto; Roger E. Moore; Henry D. Hunt; Terry D. Lee; Marcia M. Miller (Immunogenetics, 2008)

Experimental evidence for extreme dispersal limitation in tropical forest birds - R. P. Moore; W. D. Robinson; I. J. Lovette; T. R. Robinson (Ecology Letters, 2008)
Movements of organisms between habitat remnants can affect metapopulation structure, community assembly dynamics, gene flow and conservation strategy. In the tropical landscapes that support the majority of global biodiversity and where forest fragmentation is accelerating, there is particular urgency to understand how dispersal across habitats mediates the demography, distribution and differentiation of organisms. By employing unique dispersal challenge experiments coupled with exhaustive inventories of birds in a Panamanian lacustrine archipelago, we show that the ability to fly even short distances (

Expression and evolutionary features of the hexokinase gene family in Arabidopsis - Abhijit Karve; Bradley L. Rauh; Xiaoxia Xia; Muthugapatti Kandasamy; Richard B. Meagher; Jen Sheen; Brandon d. Moore (Planta, 2008)

Restoring plant species diversity and community composition in a ponderosa pine-bunchgrass ecosystem - Daniel C. Laughlin; Jonathan D. Bakker; Mark L. Daniels; Margaret M. Moore; Cheryl A. Casey; Judith D. Springer (Plant Ecology, 2008)

Factors affecting hatching success of golden apple snail eggs: Effects of water immersion and cannibalism - Katherine C. Horn; Sally D. Johnson; Kate M. Boles; Anthony Moore; Evan Siemann; Christopher A. Gabler (Wetlands, 2008)

Repeated social defeat stress-induced sensitization to the locomotor activating effects of d-amphetamine: role of individual differences - D. M. Dietz; K. C. Dietz; S. Moore; C. C. Ouimet; M. Kabbaj (Psychopharmacology, 2008)

A simple, integrative assay to quantify nutritional quality of browses for herbivores - Jane L. DeGabriel; Ian R. Wallis; Ben D. Moore; William J. Foley (Oecologia, 2008)

No mountains to snow on: major post-Eocene uplift of the East Victoria Highlands; evidence from Cenozoic deposits - G. R. Holdgate; M. W. Wallace; S. J. Gallagher; B. E. Wagstaff; D. Moore (Australian Journal of Earth Sciences, 2008)

Integration of Process-based Soil Respiration Models with Whole-Ecosystem CO2 Measurements - J. M. Zobitz; D. J. P. Moore; W. J. Sacks; R. K. Monson; D. R. Bowling; D. S. Schimel (Ecosystems, 2008)

Meteorological influence on the occurrence of gastric dilatation-volvulus in military working dogs in Texas - George E. Moore; Michael Levine; Johnna D. Anderson; Robert J. Trapp (International Journal of Biometeorology, 2008)

Efficacy of Vegetated Buffers in Preventing Transport of Fecal Coliform Bacteria from Pasturelands - Timothy J. Sullivan; James A. Moore; David R. Thomas; Eric Mallery; Kai U. Snyder; Mark Wustenberg; Judith Wustenberg; Sam D. Mackey; Deian L. Moore (Environmental Management, 2007)

Studying Daphnia feeding behavior as a black box: a novel electrochemical approach - D. C. Peñalva-Arana; P. A. Moore; B. A. Feinberg; J. DeWall; J. R. Strickler (Hydrobiologia, 2007)

Germ-line DNA copy number variation frequencies in a large North American population - George Zogopoulos; Kevin C. H. Ha; Faisal Naqib; Sara Moore; Hyeja Kim; Alexandre Montpetit; Frederick Robidoux; Philippe Laflamme; Michelle Cotterchio; Celia Greenwood; Stephen W. Scherer; Brent Zanke; et al. (Human Genetics, 2007)

High efficiency Agrobacterium rhizogenes-mediated transformation of Saponaria vaccaria L. (Caryophyllaceae) using fluorescence selection - Janice F. Schmidt; Maria D. Moore; Lawrence E. Pelcher; Patrick S. Covello (Plant Cell Reports, 2007)

Impact of trapping and tagging on the timing of continued seaward migration of wild Atlantic salmon, Salmo salar , smolts - W. D. Riley; A. Moore; I. C. Russell; I. C. Davidson; R. J. Cove; M. J. Ives (Fisheries Management and Ecology, 2007)

Occurrence of Cryptosporidium parvum and Bacterial Pathogens in Faecal Material in the Red Fox (Vulpes vulpes) Population - Y. Nagano; M. B. Finn; C. J. Lowery; T. Murphy; J. Moriarty; E. Power; D. Toolan; A. O’Loughlin; M. Watabe; K. A. McCorry; E. Crothers; J. S. G. Dooley; et al. (Veterinary Research Communications, 2007)

Food availability and physiological state of sea urchin larvae (Strongylocentrotus purpuratus) - E. Meyer; A. J. Green; M. Moore; D. T. Manahan (Marine Biology, 2007)

Functional MRI of Language in Aphasia: A Review of the Literature and the Methodological Challenges - Bruce Crosson; Keith McGregor; Kaundinya S. Gopinath; Tim W. Conway; Michelle Benjamin; Yu-Ling Chang; Anna Bacon Moore; Anastasia M. Raymer; Richard W. Briggs; Megan G. Sherod; Christina E. Wierenga; Keith D. White (Neuropsychology Review, 2007)

A QTL on chromosome 6A in bread wheat (Triticum aestivum) is associated with longer coleoptiles, greater seedling vigour and final plant height - W. Spielmeyer; J. Hyles; P. Joaquim; F. Azanza; D. Bonnett; M. E. Ellis; C. Moore; R. A. Richards (Theoretical and Applied Genetics, 2007)

The Stanley unconformity in Lake Huron basin: evidence for a climate-driven closed lowstand about 7900 14C BP, with similar implications for the Chippewa lowstand in Lake Michigan basin - C. F. M. Lewis; C. W. Heil; J. B. Hubeny; J. W. King; T. C. Moore; D. K. Rea (Journal of Paleolimnology, 2007)

Fires in tropical forests – what is really the problem? lessons from Indonesia - L. Tacconi; P. F. Moore; D. Kaimowitz (Mitigation and Adaptation Strategies for Global Change, 2006)

Synoptic sea‐level pressure patterns generated by a general circulation model: comparison with types derived from NCEP/NCAR re‐analysis and implications for downscaling - I. G. McKendry; K. Stahl; R. D. Moore (International Journal of Climatology, 2006)
A principal component analysis (PCA)‐based synoptic typing scheme is used to assess the ability of the Canadian Centre for Climate Modelling and Analysis (CCCma) Coupled Global Climate Model (CGCM2) to reproduce daily mean‐sea‐level (MSL) synoptic patterns and their frequencies for the Pacific Northwest region of North America. Model output for the ‘control’ period 1961–1989 is compared against the climatology based on National Center for Environmental Prediction (NCEP) re‐analysis data. Although CGCM2 is able to reproduce the full range and seasonality of 13 synoptic types it significantly under‐represents three cold types and over‐represents (by about 50%) three warm/wet winter types. This effect is most pronounced in winter months. Differences in frequencies between the CGCM2 runs (1961–1989 climatology and 1990–2100 IPCC SRES ‘A2’ greenhouse gases (GHG) and aerosol forcing scenario) are smaller than the differences between NCEP and CGCM2 synoptic type frequencies for the 1961–1989 control. Unresolved orographic influences and atmosphere‐ocean coupling are cited as possible explanations for model deficiencies. Results suggest that application of CGCM2 output in downscaling studies examining regional impacts should take account of these potential biases. The approach adopted provides a methodology for not only assessing progress in emerging generations of more sophisticated higher resolution General Circulation Models (GCMs) (e.g. CGCM4 is under development), but also choosing the most appropriate model for regional downscaling studies. Copyright © 2006 Royal Meteorological Society.

Morphology and response of roots of pasture species to phosphorus and nitrogen nutrition - J. O. Hill; R. J. Simpson; A. D. Moore; D. F. Chapman (Plant and Soil, 2006)

In vitro Survival and Growth of Salmonella Typhimurium inoculated on Yolk Membrane after long Term refrigerated Storage of Shell Eggs - Z. R. Howard; R. W. Moore; I. B. Zabala Diaz; W. K. Kim; S. G. Birkhold; J. A. Byrd; L. F. Kubena; D. J. Nisbet; S. C. Ricke (Journal of Consumer Protection and Food Safety, 2006)

Introduced Alien or Persecuted Native? Resolving the Origin of the Viperine Snake (Natrix Maura) on Mallorca - Daniela Guicking; Richard A. Griffiths; Robin D. Moore; Ulrich Joger; Michael Wink (Biodiversity and Conservation, 2006)

Identification ofArcobacter species using phospholipid and total fatty acid profiles - D. Jelínek; P. Miketová; L. Khailová; K. H. Schram; I. M. (Ki) Moore; J. Vytřasová (Folia Microbiologica, 2006)

Prosthetic valve endocarditis due to coagulase-negative staphylococci: findings from the International Collaboration on Endocarditis Merged Database - T. Lalani; Z. A. Kanafani; V. H. Chu; L. Moore; G. R. Corey; P. Pappas; C. W. Woods; C. H. Cabell; B. Hoen; C. Selton-Suty; T. Doco-Lecompte; C. Chirouze; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Glacier-mediated streamflow teleconnections to the Arctic Oscillation - Sean W. Fleming; R. D. (Dan) Moore; Garry K. C. Clarke (International Journal of Climatology, 2006)

Enhanced clinical utility of the NucliSens EasyQ RSV A+B Assay for rapid detection of respiratory syncytial virus in clinical samples - C. Moore; M. Valappil; S. Corden; D. Westmoreland (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Patterns of Carbon, Nitrogen and Phosphorus Dynamics in Decomposing Foliar Litter in Canadian Forests - T. R. Moore; J. A. Trofymow; C. E. Prescott; J. Fyles; B. D. Titus (Ecosystems, 2006)

In vitro Survival and Growth of Salmonella Typhimurium inoculated on Yolk Membrane after long Term refrigerated Storage of Shell Eggs - Z. R. Howard; R. W. Moore; I. B. Zabala Diaz; W. K. Kim; S. G. Birkhold; J. A. Byrd; L. F. Kubena; D. J. Nisbet; S. C. Ricke (Journal of Consumer Protection and Food Safety, 2006)

The Genomic Organization of Retrotransposons in Brassica oleracea - Karine Alix; Carol D. Ryder; Jay Moore; Graham J. King; J. S. (Pat) Heslop-Harrison (Plant Molecular Biology, 2005)

Classical collection - Peter D. Moore (Journal of Biogeography, 2005)

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

A non‐invasive method to assess the impact of electronic tag insertion on stress levels in fishes - N. Lower; A. Moore; A. P. Scott; T. Ellis; J. D. James; I. C. Russell (Journal of Fish Biology, 2005)
The present study investigated, for the first time, a non‐invasive technique for monitoring cortisol levels in fishes that had been implanted with electronic transmitters. This technique involved the measurement of cortisol released into the water by individual fish. Carp Cyprinus carpio and roach Rutilus rutilus that had been tagged with miniature dummy acoustic transmitters responded to the surgical implantation of the tags with an immediate (1 to 4 h) increase in cortisol concentrations in the water. These amounts of cortisol were higher than in ‘handled only’ and ‘handled and anaesthetized’ groups. Estimated cortisol release rates for both species correlated well with the direct measurements in the water. In both species, water cortisol concentration and cortisol release rates returned to pre‐stress levels within 12 h of tag‐insertion, and remained low for the remainder of the experiment. The calculation of cortisol release rates highlighted a difference of a factor of about four between peak release rates in carp and roach. There was no evident long‐term cortisol stress response to the presence of a tag in the body cavity in either species.

Life Cycle Assessment of Water Recycling Technology - N. Tangsubkul; P. Beavis; S. J. Moore; S. Lundie; T. D. Waite (Water Resources Management, 2005)

Low gene flow but high genetic diversity in the threatened Mallorcan midwife toad Alytes muletensis - F. J. L. KRAAIJEVELD‐SMIT; T. J. C. BEEBEE; R. A. GRIFFITHS; R. D. MOORE; L. SCHLEY (Molecular Ecology, 2005)
We investigated fine‐scale genetic structuring in the rare and vulnerable Mallorcan midwife toad Alytes muletensis using eight polymorphic microsatellite markers. The current range of this amphibian is restricted to some 19 sites of which six are derived from reintroductions, all located in the mountain ranges of Mallorca. We sampled tadpoles from 14 pools covering 10 natural sites and two reintroduction sites for microsatellite DNA analyses. Relatively high levels of genetic variation were found in most pools ( H E = 0.38–0.71, allelic richness = 2.6–6.2). Only at one pool has the population recently gone through a bottleneck. Dispersal between pools in different torrents does not occur whereas downstream dispersal between pools within the same torrent does happen at low frequencies. This occasional exchange of individuals does not lead to neighbouring pools in the same torrent being panmictic. This can be concluded because all F ST values (0.12–0.53) differ significantly from zero and structure analyses identified neighbouring pools as separate populations. Furthermore, assignment and migration tests showed little exchange between neighbouring pools. If upstream locations or complete torrents go extinct, they are unlikely to be recolonized naturally. For conservation purposes, reintroductions of tadpoles to sites where local extinctions have occurred may therefore be advisable.

Seistec Seismic Profiles: A Tool to Differentiate Gas Signatures - A. Baltzer; B. Tessier; H. Nouzé; R. Bates; C. Moore; D. Menier (Marine Geophysical Research, 2005)

Bacterial community dynamics during in-situ bioremediation of petroleum waste sludge in landfarming sites - E. Katsivela; E. R. B. Moore; D. Maroukli; C. Strmpl; D. Pieper; N. Kalogerakis (Biodegradation, 2005)

Discrepancy Between Antennal and Behavioral Responses for Enantiomers of α-Pinene: Electrophysiology and Behavior of Helicoverpa armigera (Lepidoptera) - C. D. Hull; J. P. Cunningham; C. J. Moore; M. P. Zalucki; B. W. Cribb (Journal of Chemical Ecology, 2004)

Induced defences in an endangered amphibian in response to an introduced snake predator - Robin D. Moore; Richard A. Griffiths; Cliona M. O’Brien; Adam Murphy; David Jay (Oecologia, 2004)

Antiherbivore Chemistry of Eucalyptus--Cues and Deterrents for Marsupial Folivores - Ben D. Moore; Ian R. Wallis; Jesús Palá-Paúl; Joseph J. Brophy; Richard H. Willis; William J. Foley (Journal of Chemical Ecology, 2004)

Detritus, trophic dynamics and biodiversity - John C. Moore; Eric L. Berlow; David C. Coleman; Peter C. de Ruiter; Quan Dong; Alan Hastings; Nancy Collins Johnson; Kevin S. McCann; Kim Melville; Peter J. Morin; Knute Nadelhoffer; Amy D. Rosemond; et al. (Ecology Letters, 2004)
Traditional approaches to the study of food webs emphasize the transfer of local primary productivity in the form of living plant organic matter across trophic levels. However, dead organic matter, or detritus, a common feature of most ecosystems plays a frequently overlooked role as a dynamic heterogeneous resource and habitat for many species. We develop an integrative framework for understanding the impact of detritus that emphasizes the ontogeny and heterogeneity of detritus and the various ways that explicit inclusion of detrital dynamics alters generalizations about the structure and functioning of food webs. Through its influences on food web composition and dynamics, detritus often increases system stability and persistence, having substantial effects on trophic structure and biodiversity. Inclusion of detrital heterogeneity in models of food web dynamics is an essential new direction for ecological research.

Species distributions, surrogacy, and important conservation regions in Canada - Leanna D. Warman; David M. Forsyth; A. R. E. Sinclair; Kathryn Freemark; Harold D. Moore; Thomas W. Barrett; R. L. Pressey; Denis White (Ecology Letters, 2004)
Conservation actions could be more efficient if there is congruence among taxa in the distribution of species. Patterns in the geographical distribution of five taxa were used to identify nationally important regions for conservation in Canada. Two measures of surrogacy were significantly and positively correlated among taxa, and conservation areas selected for one taxon represented other taxa significantly better than random selections. However, few large protected areas exist in the sites of highest conservation value in southern Canada; these regions are therefore a priority for future conservation regard. By focusing this effort on threatened and endangered species, which are a national priority in Canada, most other species could also benefit.

Disturbance of freshwater habitats by anadromous salmon in Alaska - Jonathan W. Moore; Daniel E. Schindler; Mark D. Scheuerell (Oecologia, 2004)

Pseudomonas anguilliseptica infection in farmed cod, Gadus morhua L. - H W Ferguson; R O Collins; M Moore; M Coles; D D MacPhee (Journal of Fish Diseases, 2004)

Construction of a genetic map for arabica coffee - H. M. Pearl; C. Nagai; P. H. Moore; D. L. Steiger; R. V. Osgood; R. Ming (Theoretical and Applied Genetics, 2004)

Association of cone thermogenesis and volatiles with pollinator specificity in Macrozamia cycads - I. Terry; C. J. Moore; G. H. Walter; P. I. Forster; R. B. Roemer; J. D. Donaldson; P. J. Machin (Plant Systematics and Evolution, 2004)

Wollastonite at the Sterling Hill Fe?Zn?Mn ore body, Ogdensburg, New Jersey - A. Dzs-Moore; P. B. Leavens; R. E. Jenkins II; N. M. Altounian (Mineralogy and Petrology, 2003)

Forest Certification of State and University Lands in North Carolina: A Comparison - F. Cubbage; S. Moore; J. Cox; L. Jervis; J. Edeburn; D. Richter; W. Boyette; M. Thompson; M. Chesnutt (Journal of Forestry, 2003)
North Carolina State University, Duke University, and the North Carolina Division of Forest Resources (DFR) recently received both Forest Stewardship Council (FSC) and Sustainable Forestry Initiative (SFI) certification for their forests. Meeting SFI standards required better environmental management systems, improved use of best management practices, and better recordkeeping but few subsequent forest management changes. FSC required about the same environmental system changes but more forest management changes to favor future natural stand management and biodiversity protection. Costs included changes in forest management and recordkeeping to achieve forest certification, inspection expenses, prescribed changes in forest management, forgone timber revenues, and more stakeholder consultation. Benefits can include an improved professional reputation, better worker safety and training, better records and processes, more active public involvement, enhanced knowledge for outreach, better environmental management systems, more holistic management, and perhaps higher timber prices or greater market access.

An ancient linked fluid migration system: cold-seep deposits and sandstone intrusions in the Panoche Hills, California, USA - Hilde Schwartz; James Sample; Kevin D. Weberling; Daniel Minisini; J. Casey Moore (Geo-Marine Letters, 2003)

Environmental variability and biogeography: the relationship between bathymetric distribution and geographical range size in marine algae and gastropods - Christopher D. G. Harley; Katherine F. Smith; Vicki L. Moore (Global Ecology and Biogeography, 2003)
Aims Gradients of environmental variability have been proposed to explain spatial variation in patterns of geographical range size. We explore this relationship in NE Pacific algae and NW Atlantic gastropods by using the characteristics of species’ bathymetric distributions as a proxy for tolerance of environmental variability. Location NE Pacific and NW Atlantic. Methods Data on species bathymetric and geographical distributions were compiled from the literature. Results For both algae and gastropods, species that inhabit highly seasonal, shallow depth zones have broader latitudinal ranges, and occupy more biogeographical provinces, than species that live in more temporally stable, deeper zones. Furthermore, species that tolerate spatial variability along the bathymetric axis, i.e. those that occur in multiple depth zones, have broader geographical ranges than species restricted to fewer depth zones. Main conclusions Within‐range environmental variability, through both space and time, is predictive of large geographical ranges for marine algae and gastropods. Analysis of species distributions across perpendicular gradients (e.g. depth and latitude) is a powerful approach to discerning the mechanisms that govern biogeographical patterns, and provides easily obtainable broad‐brush predictions regarding the biogeographical outcomes of global change.

Acute Toxicity of Methyl-Parathion in Wetland Mesocosms: Assessing the Influence of Aquatic Plants Using Laboratory Testing with Hyalella azteca - R. Schulz; M. T. Moore; E. R. Bennett; C. D. Milam; J. L. Bouldin; J. L. Farris; S. Smith; C. M. Cooper (Archives of Environmental Contamination and Toxicology, 2003)

Integrating biodiversity priorities with conflicting socio-economic values in the Guinean–Congolian forest region - P.H. Williams; J.L. Moore; A. Kamden Toham; T.M. Brooks; H. Strand; J. D'Amico; M. Wisz; N.D. Burgess; A. Balmford; C. Rahbek (Biodiversity and Conservation, 2003)

Sedimentary Nonylphenol Contamination in an Urbanized, Industrialized Segment of the Delaware River Estuary, USA - J. T. F. Ashley; A. Moore; H. M. Stapleton; D. J. Velinsky; M. P. Wilhelm (Bulletin of Environmental Contamination and Toxicology, 2003)

DMT1: A mammalian transporter for multiple metals - Michael D. Garrick; Kevin G. Dolan; Craig Horbinski; Andrew J. Ghio; Dennis Higgins; Michael Porubcin; Elizabeth G. Moore; Lucille N. Hainsworth; Jay N. Umbreit; Marcel E. Conrad; Lee Feng; Agnieska Lis; et al. (BioMetals, 2003)

Performance of Sub‐Saharan Vertebrates as Indicator Groups for Identifying Priority Areas for Conservation - Joslin L. Moore; Andrew Balmford; Thomas Brooks; Neil D. Burgess; Louis A. Hansen; Carsten Rahbek; Paul H. Williams (Conservation Biology, 2003)
The aim of continental and global identification of priority areas for conservation is to identify particularly valuable areas for conservation on which to focus more‐detailed effort. Often, these sets of important areas, referred to as priority sets, have been identified through use of data on a single taxon (e.g., birds), which is assumed to act as an indicator for all biodiversity. Using a database of the distributions of 3882 vertebrate species in sub‐Saharan Africa, we conducted one of very few large‐scale tests of this assumption. We used six potential indicator groups—birds, mammals, amphibians, snakes, threatened birds, and threatened mammals—to find priority sets of 200 areas that best represent the species in that group. Priority sets of grid cells designed to maximize representation of a single indicator group captured 83–93% of species in the other groups. This high degree of representation is consistent with observed high levels of overlap in the patterns of distribution of species in different groups. Those species of highest conservation interest were more poorly represented, however, with only 75–88% of other groups' threatened species and 63–76% of other groups' narrow‐range species represented in the priority sets. We conclude that existing priority sets based on indicator groups provide a pragmatic basis for the immediate assessment of priorities for conservation at a continental scale. However, complete and efficient representation—especially of narrow‐range species—will not be achieved through indicator groups alone. Therefore, priority‐setting procedures must remain flexible so that new areas important for other taxa can be incorporated as data become available.

Pedigree and taxonomic credentials of Pseudomonas putida strain KT2440 - D. Regenhardt; H. Heuer; S. Heim; D. U. Fernandez; C. Strömpl; E. R. B. Moore; K. N. Timmis (Environmental Microbiology, 2002)

Size variability of juvenile Atlantic salmon: links to environmental conditions - E. Swansburg; G. Chaput; D. Moore; D. Caissie; N. El‐Jabi (Journal of Fish Biology, 2002)
Climate change models predict a 2 to 6° C increase in air temperature within the next 100 years in the Maritime Provinces of eastern Canada. Higher air temperatures are expected to contribute to increased water temperatures, alterations in stream flow conditions, and ultimately reductions in fish growth. Mean annual size‐at‐age of juvenile Atlantic salmon Salmo salar decreased in the Northwest Miramichi and Southwest Miramichi Rivers between 1971–1999. Lengths‐at‐age of juveniles were significantly correlated between the two rivers. For Atlantic salmon parr, stronger associations between inter‐cohort fork length ( L F ) than intra‐cohort L F were observed, suggesting that environmental conditions in the current year of growth have the more significant effects on size of age 2 year parr than conditions encountered the previous year by age 1 year parr of the same cohort. Fork lengths of parr were significantly and negatively associated with spring air and water temperatures. In the Miramichi River, increases in air and water temperature as predicted from climate change models may adversely affect growth of juvenile Atlantic salmon parr, reducing the overall productivity of the Atlantic salmon populations in this region.

AFLP analysis of genetic diversity within and among Coffea arabica cultivars - D. Steiger; C. Nagai; P. Moore; C. Morden; R. Osgood; R. Ming (Theoretical and Applied Genetics, 2002)

Nutritional regulation of somatostatin expression in rainbow trout, Oncorhynchus mykiss - Melissa M. Ehrman; Gregory T. Melroe; Craig A. Moore; Jeffrey D. Kittilson; Mark A. Sheridan (Fish Physiology and Biochemistry, 2002)

An Evaluation of the Use of Colonized Periphyton as an Indicator of Wastewater Impact in Near-Coastal Areas of the Gulf of Mexico - M. A. Lewis; D. L. Weber; J. C. Moore (Archives of Environmental Contamination and Toxicology, 2002)

Identification of the Sex Pheromone of Holotrichia reynaudi - Andrew Ward; Chris Moore; V. Anitha; John Wightman; D. John Rogers (Journal of Chemical Ecology, 2002)

Influence of Leaching Protocol Regimes on Losses of Wood Preservative Biocides - J. A. Hingston; A. Bacon; J. Moore; C. D. Collins; R. J. Murphy; J. N. Lester (Bulletin of Environmental Contamination and Toxicology, 2002)

Influence of Leaching Protocol Regimes on Losses of Wood Preservative Biocides - J. A. Hingston; A. Bacon; J. Moore; C. D. Collins; R. J. Murphy; J. N. Lester (Bulletin of Environmental Contamination and Toxicology, 2002)

Ultrafast Flow Quantification With Segmented k-Space Magnetic Resonance Phase Velocity Mapping - Haosen Zhang; Sandra S. Halliburton; James R. Moore; Orlando P. Simonetti; Paulo R. Schvartzman; Richard D. White; George P. Chatzimavroudis (Annals of Biomedical Engineering, 2002)

An Interactive Management System for Operational Control of Kirazdere Reservoir (Turkey) - Z. Rao; I. N. Moore; P. E. O’Connell; D. G. Jamieson (Water Resources Management, 2001)

Modeling Northern Peatland Decomposition and Peat Accumulation - Steve Frolking; Nigel T. Roulet; Tim R. Moore; Pierre J. H. Richard; Martin Lavoie; Serge D. Muller (Ecosystems, 2001)

Terrestrial nemerteans thirty years on - Janet Moore; Ray Gibson; Hugh D. Jones (Hydrobiologia, 2001)

Changes in the haemagglutinin and the neuraminidase genes prior to the emergence of highly pathogenic H7N1 avian influenza viruses in Italy - J. Banks; E. S. Speidel; E. Moore; L. Plowright; A. Piccirillo; I. Capua; P. Cordioli; A. Fioretti; D. J. Alexander (Archives of Virology, 2001)

Quantitative Electroencephalography (QEEG) and Neuropsychological Syndrome Analysis - B. V. Shenal; R. D. Rhodes; T. M. Moore; D. A. Higgins; D. W. Harrison (Neuropsychology Review, 2001)

The Effect of Mercury and PCBs on Organisms from Lower Trophic Levels of a Georgia Salt Marsh - V. D. Wall, J. J. Alberts, D. J. Moore (Archives of Environmental Contamination and Toxicology, 2001)

An isotopic labeling method for determining production of volatile organohalogens by marine microalgae - Cormac D. Murphy; Robert M. Moore; Robert L. White (Limnology and Oceanography, 2000)
An isotopic method has been developed to establish the biological production of volatile organohalogens. The marine microalgae Porphyridium purpureum and Dunaliella tertiolecta were grown in seawater medium containing NaH 13 CO 3 , and volatile organohalogens were extracted and analyzed by gas chromatography‐mass spectrometry (GC‐MS). Isotopically labeled methyl halides were formed in each microalgal culture, and the 13 CHCl 3 found in the P. purpureum culture confirmed the production of chloroform reported by Scarratt and Moore (Limnol. Oceanogr. 1999. 44: 703–707). No incorporation of 13 C into dichloromethane was observed, even though slightly increased CH 2 Cl 2 concentrations were detected in both algal cultures at the end of the incubation period.

Misidentification of soil bacteria by fatty acid methyl ester (FAME) and BIOLOG analyses - N. Oka; P. G. Hartel; O. Finlay-Moore; J. Gagliardi; D. A. Zuberer; J. J. Fuhrmann; J. S. Angle; H. D. Skipper (Biology and Fertility of Soils, 2000)

A novel restriction fragment length polymorphism for petrels or tube‐nosed seabirds - C. D. Millar; G. A. Taylor; P. J. Moore; J. L. Halverson; D. M. Lambert (Molecular Ecology, 2000)

Peroxidases from marine microalgae - Cormac D. Murphy; Robert M. Moore; Robert L. White (Journal of Applied Phycology, 2000)

Emergence of Atlantic salmon, Salmo salar L., fry in a chalk stream - W. D. Riley; A. Moore (Fisheries Management and Ecology, 2000)

An investigation into the efficacy of intravenous diclofenac in post-operative dental pain - R. A. Seymour; U. Moore; J. Hawkesford; P. Coulthard; D. Jackson-Leech; D. Thomas; M. Hill; M. L. Combs; T. Renton; M. McGurk (European Journal of Clinical Pharmacology, 2000)

Climatic and biotic controls on annual carbon storage in Amazonian ecosystems - H. Tian; J. M. Melillo; D. W. Kicklighter; A. D. McGuire; J. Helfrich Iii; B. Moore Iii; C. J. Vörösmarty (Global Ecology and Biogeography, 2000)
The role of undisturbed tropical land ecosystems in the global carbon budget is not well understood. It has been suggested that interannual climate variability can affect the capacity of these ecosystems to store carbon in the short term. In this paper, we use a transient version of the Terrestrial Ecosystem Model (TEM) to estimate annual carbon storage in undisturbed Amazonian ecosystems during the period 1980–94, and to understand the underlying causes of the year‐to‐year variations in net carbon storage for this region.

Fate of the Dietary Terpene, P-Cymene, in the Male Koala - Rebecca Boyle; Stuart McLean; William J. Foley; Ben D. Moore; Noel W. Davies; Sue Brandon (Journal of Chemical Ecology, 2000)

Experimental and Computational Flow Evaluation of Coronary Stents - Joel L. Berry; Aland Santamarina; James E. Moore, Jr.; Suranjan Roychowdhury; William D. Routh (Annals of Biomedical Engineering, 2000)

Comparative analysis of aphid vector behavior in response to potato plants grown from field tubers, minitubers or plantlets - G. Boiteau; L. M. Moore; D. Wattie (American Journal of Potato Research, 2000)

Susceptibility of Five Nontarget Organisms to Aqueous Diazinon Exposure - D. E. Burkepile; M. T. Moore; M. M. Holland (Bulletin of Environmental Contamination and Toxicology, 2000)

Specific inhibitors of inducible nitric oxide synthase: Efficacy in a rodent model of sepsis - D. J. Fretland; D. L. Widomski; C. P. Anglin; W. Moore , G. Jerome , C. Kornmeier ,; E. A. Hallinan; T. Hagen; A. Bergmanis; B. Pitzele (Inflammation Research, 1999)

Codon optimization, genetic insulation, and an rtTA reporter improve performance of the tetracycline switch - Kevin D. Wells; Juli A. Foster; Karen Moore; Vernon G. Pursel; Robert J. Wall (Transgenic Research, 1999)

RELATIVE ABUNDANCE OF LARGE WHALES AROUND SOUTH GEORGIA (1979–1998) 1 - M. J. Moore; S. D. Berrow; B. A. Jensen; P. Carr; R. Sears; V. J. Rowntree; R. Payne; P. K. Hamilton (Marine Mammal Science, 1999)
A bstract To assess large‐whale stocks following the cessation of land‐based South Georgia whaling in 1965, we report three independent sighting databases: a cruise in 1997, observations from Bird Island (NW of South Georgia) between 1979 and 1998, and mariner sightings between 1992 and 1997. All species were rare, with sightings of southern right whales being the most common event. Two right whales photographed off South Georgia matched animals known from Peninsula Valdés, Argentina, a population known to be growing at 7% per annum . In contrast, blue and fin whales appeared to be less abundant. A single blue whale mother‐calf pair was observed off the Shag Rocks in February 1997. Extirpation of animals from this particular feeding ground is the most likely reason for ongoing low numbers of all species. Other factors may include competition for krill by traditional predators such as penguins and seals and more recently by humans, an unusually high rate of natural mortality, habitat change such as alteration in sea ice coverage, and/or the impact of ongoing whaling. The history of this critical area of large‐whale habitat and this report demonstrate the need for improved, consistent longterm monitoring of population trends for these depleted stocks.

Optical Thin-Film Sensors for the Determination of Aqueous Halide Ions - Chris D. Geddes; Peter Douglas; Christopher P. Moore; Trevor J. Wear; Peter L. Egerton (Journal of Fluorescence, 1999)

Comparing global models of terrestrial net primary productivity (NPP): overview and key results - W. Cramer; D. W. Kicklighter; A. Bondeau; B. Moore Iii; G. Churkina; B. Nemry; A. Ruimy; A. L. Schloss; ThE. Participants OF. ThE. Potsdam NpP. Model Intercomparison (Global Change Biology, 1999)
Summary Seventeen global models of terrestrial biogeochemistry were compared with respect to annual and seasonal fluxes of net primary productivity (NPP) for the land biosphere. The comparison, sponsored by IGBP‐GAIM/DIS/GCTE, used standardized input variables wherever possible and was carried out through two international workshops and over the Internet. The models differed widely in complexity and original purpose, but could be grouped in three major categories: satellite‐based models that use data from the NOAA/AVHRR sensor as their major input stream (CASA, GLO‐PEM, SDBM, SIB2 and TURC), models that simulate carbon fluxes using a prescribed vegetation structure (BIOME‐BGC, CARAIB 2.1, CENTURY 4.0, FBM 2.2, HRBM 3.0, KGBM, PLAI 0.2, SILVAN 2.2 and TEM 4.0), and models that simulate both vegetation structure and carbon fluxes (BIOME3, DOLY and HYBRID 3.0). The simulations resulted in a range of total NPP values (44.4–66.3 Pg C year –1 ), after removal of two outliers (which produced extreme results as artefacts due to the comparison). The broad global pattern of NPP and the relationship of annual NPP to the major climatic variables coincided in most areas. Differences could not be attributed to the fundamental modelling strategies, with the exception that nutrient constraints generally produced lower NPP. Regional and global NPP were sensitive to the simulation method for the water balance. Seasonal variation among models was high, both globally and locally, providing several indications for specific deficiencies in some models.

The evolution of empty nuptial gifts in a dance fly, Empis snoddyi (Diptera: Empididae): bigger isn't always better - Jennifer A. Sadowski; Allen J. Moore; Edmund D. Brodie III (Behavioral Ecology and Sociobiology, 1999)

Accuracy of Computational Hemodynamics in Complex Arterial Geometries Reconstructed from Magnetic Resonance Imaging - J. A. Moore; D. A. Steinman; D. W. Holdsworth; C. R. Ethier (Annals of Biomedical Engineering, 1999)

An adjoint data assimilation approach to diagnosis of physical and biological controls on Pseudocalanus spp. in the Gulf of Maine–Georges Bank region - D. J. MCGILLICUDDY; D. R. LYNCH; A. M. MOORE; W. C. GENTLEMAN; C. S. DAVIS; C. J. MEISE (Fisheries Oceanography, 1998)
The underlying scientific objective here is to determine the mechanisms that control seasonal variations in the abundance of Pseudocalanus spp. in the Georges Bank–Gulf of Maine region. It is postulated that the observed distributions result from the interaction of the population dynamics with the climatological circulation. The problem is posed mathematically as a 2‐D advection–diffusion–reaction equation for a scalar variable. Given an initial distribution of animals, we seek the population dynamics source term R ( x , y ) such that integration of the forward model will result in predictions3 that minimize the sum of squares of differences with observed concentrations at a later time. An adjoint data assimilation technique has been designed for these purposes. This approach has been used to invert for the population dynamics associated with the transition between bimonthly (i.e. for 2 months) climatological Pseudocalanus spp. distributions derived from MARMAP data. Vertically averaged velocity and diffusivity fields diagnosed from hydrodynamical simulations of the climatological flow are specified. Solutions converge rapidly, and the procedure reduces the cost function by an order of magnitude within 50 iterations. The resulting population dynamics vary considerably in space and time, as does the balance between local tendency, physical transport and biological source terms. Generally speaking, the patterns in population dynamics are not inconsistent with current knowledge concerning potential controls such as predation and food limitation. Analysis of the solutions indicates that the Pseudocalanus spp. population centres located in the western Gulf of Maine and on Georges Bank may be self‐sustaining, in contrast to prior studies which characterize the former as a source region for the latter.

The take of fish species by seabirds and marine mammals in the Australian Fisheries Zone around Heard Island: the potential for competition with a commercial fishery - K. Green; D. J. Slip; G. J. Moore (Polar Biology, 1998)

Responses of Non-Target Aquatic Organisms to Aqueous Propanil Exposure - M. T. Moore; J. R. Pierce; C. D. Milam; J. L. Farris; E. L. Winchester (Bulletin of Environmental Contamination and Toxicology, 1998)

Pharmacological evaluation of 1-(carboxymethyl)-3,5-diphenyl-2-methylbenzene, a novel arylacetic acid with potential anti-inflammatory properties - S. J. Cutler; C. DeWitt Blanton Jr.; D. T. Akin; F. B. Steinberg; A. B. Moore; J. A. Lott; T. C. Price; S. W. May; S. H. Pollock (Inflammation Research, 1998)

Sequence Comparison of Avian Infectious Bronchitis Virus S1 Glycoproteins of the Florida Serotype and Five Variant Isolates from Georgia and California - Kristi M. Moore; Joyce D. Bennett; Bruce S. Seal; Mark W. Jackwood (Virus Genes, 1998)

Stability Dependence of the Eddy-Accumulation Coefficients for Momentum and Scalars - Edgar L. Andreas; Reginald J. Hill; James R. Gosz; Douglas I. Moore; William D. Otto; Achanta D. Sarma (Boundary-Layer Meteorology, 1998)

Statistics of Surface-Layer Turbulence Over Terrain with Metre-Scale Heterogeneity - Edgar L Andreas; Reginald J. Hill; James R. Gosz; Douglas I. Moore; William D. Otto; Achanta D. Sarma (Boundary-Layer Meteorology, 1998)

Comparative Toxicity of Chlordane, Chlorpyrifos, and Aldicarb to Four Aquatic Testing Organisms - M. T. Moore; D. B. Huggett; W. B. Gillespie Jr.; J. H. Rodgers Jr.; C. M. Cooper (Archives of Environmental Contamination and Toxicology, 1998)

Structure, functions, and evolution of the third complement component and viral molecular mimicry - Arvind Sahu; J. Oriol Sunyer; William T. Moore; Maria Rosa Sarrias; Athena M. Soulika; John D. Lambris (Immunologic Research, 1998)

Germline diversity within the mouse Igk-V9 gene family - H. D. Ulrich; Frederick L. Moore; Peter G. Schultz (Immunogenetics, 1997)

Subunit Regulation of the Human Brain α 1E Calcium Channel - L. Parent; T. Schneider; C.P. Moore; D. Talwar (The Journal of Membrane Biology, 1997)

Tentacular diversity in deep-sea deposit-feeding holothurians: implications for biodiversity in the deep sea - D. Roberts; H. M. Moore (Biodiversity and Conservation, 1997)

Identification of amino acids involved in a serotype and neutralization specific epitope with in the s1 subunit of avian infectious bronchitis virus - K. M. Moore; M. W. Jackwood; D. A. Hilt (Archives of Virology, 1997)

Y chromosome polymorphisms in Native American and Siberian populations: identification of Native American Y chromosome haplotypes - Jeffrey T. Lell; Michael D. Brown; Theodore G. Schurr; R. I. Sukernik; Yelena B. Starikovskaya; Antonio Torroni; Lorna G. Moore; Gary M. Troup; D. C. Wallace (Human Genetics, 1997)

Factors affecting Agrobacterium-mediated transformation in Citrus and production of sour orange (Citrus aurantium L.) plants expressing the coat protein gene of citrus tristeza virus - M. A. Gutiérrez-E.; D. Luth; G. A. Moore (Plant Cell Reports, 1997)

Evaluating climate indices and their geochemical proxies measured in corals - R. G. Fairbanks; M. N. Evans; J. L. Rubenstone; R. A. Mortlock; K. Broad; M. D. Moore; C. D. Charles (Coral Reefs, 1997)

Tenidap inhibits 5-lipoxygenase product formation in vitro, but this activity is not observed in three animal models - T. J. Carty; F. J. Sweeney; R. J. Griffiths; J. D. Eskra; M. J. Ernest; J. S. Pillar; J. D. Cheng; L. D. Loose; P. A. Joseph; P. P. Pazoles; P. F. Moore; A. Nagahisa; et al. (Inflammation Research, 1997)

Regional Biodiversity Planning and Lemur Conservation with GIS in Western Madagascar - A. P. Smith; N. Horning; D. Moore (Conservation Biology, 1997)
Primary forest cover in western Madagascar declined from 12.5% in 1950 to 2.8% in 1990. Approximately 23% of remaining forest is located within reserves, but this is no guarantee of protection. Forest cover in the Andranomena Reserve in western Madagascar has been reduced by 44% since 1950. The identification of priority areas for establishment of development projects has been constrained by lack of information on the distribution, abundance, and habitat requirements of threatened species and the size, condition, and threats to survival of forest remnants. We evaluate a rapid fauna survey and habitat modeling procedure specifically designed to generate information for reserve selection and design using Geographical Information Systems (GIS). The study was conducted in the largest remnant (94,000 ha) of primary monsoon rainforest in western Madagascar, using lemurs as an indicator group. Lemur abundance and microhabitat variables were measured at 64 stratified survey sites dispersed throughout the region. These records were incorporated into a GIS with other environmental and landuse data derived from maps and satellite imagery. Statistical procedures were applied to analyze species habitats, predict and map species distributions, and estimate species population sizes throughout the study area. Patterns of slash and burn agriculture and anthropogenic disturbance were also analyzed to identify areas at low risk of cultural disturbance. A map of disturbance risk was overlaid with a map of relative lemur biodiversity to identify conservation priority areas with high biodiversity and low risk of short term disturbance. Lemur diversity was most strongly influenced by habitat clearing and human disturbance (harvesting, stock grazing, and hunting) within 8 km of villages. Lemur diversity was highest in a region of higher elevation and rainfall, distant from villages and roads. The only existing reserve in the study area was located in a region of high disturbance risk. Almost half the reserve has been degraded during the past 45 years. There is considerable scope for re‐allocation of land use within the study area to include a core protected area, a buffer zone with controlled hunting and timber harvesting, and an adjacent ecotourism facility. We found that information generated by a stratified biodiversity and landuse survey at a sampling intensity of less than 0.1% was sufficient to provide an objective foundation for regional biodiversity planning.

Chromoplast development in ripening tomato fruit: identification of cDNAs for chromoplast-targeted proteins and characterization of a cDNA encoding a plastid-localized low-molecular-weight heat shock protein - Susan D. Lawrence; Kenneth Cline; Gloria A. Moore (Plant Molecular Biology, 1997)

An EBV-transformed owl monkey B-lymphocyte cell line - J. G. Scammell; P. D. Reynolds; M. Y. Elkhalifa; J. A. Tucker; C. M. Moore (In Vitro Cellular & Developmental Biology - Animal, 1997)

A medium-density genetic linkage map of the bovine genome - W. Barendse; D. Vaiman; S. J. Kemp; Y. Sugimoto; S. M. Armitage; J. L. Williams; H. S. Sun; A. Eggen; M. Agaba; S. A. Aleyasin; M. Band; M. D. Bishop; et al. (Mammalian Genome, 1997)

Host preference of the facultative hyperparasitoidTetrastichus howardi (Hym.: Eulophidae) - S. D. Moore; Rami Kfir (BioControl, 1995)

Effect of sunscreens, irradiance and resting periods on the germination ofMetarhizium flavoviride conidia - T. R. Hunt; D. Moore; P. M. Higgins; C. Prior (BioControl, 1994)

Simple calculation of the velocity profiles for pulsatile flow in a blood vessel using Mathematica - X. He; D. N. Ku; J. E. Moore (Annals of Biomedical Engineering, 1993)

Erratum to: “A rapid shake-elution procedure for quantifying root lesion nematodes (Pratylenchus thornei) in chickpea and wheat” - K. J. Moore; R. J. Southwell; M. W. Schwinghamer; R. D. Murison (Australasian Plant Pathology, 1992)

Coastal Chip: A chipping potato variety resistant to heat stress - K. G. Haynes; R. W. Goth; S. B. Sterrett; B. J. Christ; D. E. Halseth; G. A. Porter; M. R. Henninger; D. R. Wilson; R. E. Webb; D. F. Hammond; R. Moore; F. L. Haynes; et al. (American Journal of Potato Research, 1992)

Dispersal ofAleochara bilineata [Col.: Staphylinidae] following inundative releases in urban gardens - A. D. Tomlin; D. G. R. McLeod; L. V. Moore; J. W. Whistlecraft; J. J. Miller; J. H. Tolman (BioControl, 1992)

Interaction betweenRastrococcus invadens [Hom.: Pseudococcidae] and two natural enemies - M. Akalach; E. Fernandez-Garcia; D. Moore (BioControl, 1992)

Uptake of aromatic and chlorinated hydrocarbons by juvenile chinook salmon (Oncorhynchus tshawytscha) in an urban estuary - B. B. McCain; D. C. Malins; M. M. Krahn; D. W. Brown; W. D. Gronlund; L. K. Moore; S -L. Chan (Archives of Environmental Contamination and Toxicology, 1990)

NemaRus: A golden nematode resistant, russet-skin potato variety - R. W. Goth; J. R. Shumaker; R. E. Webb; D. R. Wilson; R. Moore; L. L. Sanford; K. G. Haynes (American Journal of Potato Research, 1989)

Coastal Russet: a mid-season Russet-skinned potato cultivar - J. B. Sieczka; R. E. Webb; D. R. Wilson; D. E. Halseth; S. B. Sterrett; M. R. Henninger; G. A. Porter; J. R. Shumaker; R. Moore (American Journal of Potato Research, 1988)

Coastal Russet: A mid-season Russet-skinned potato cultivar - J. B. Sieczka; R. E. Webb; D. R. Wilson; D. E. Halseth; S. B. Sterrett; M. R. Henninger; G. A. Porter; J. R. Shumaker; R. Moore (American Journal of Potato Research, 1988)

Synchronizing human movement with an external clock source - D. Hary; G. P. Moore (Biological Cybernetics, 1987)

Avoidance of super-parasitism of stem-boring larvae byChasmodon apterus [Hym.: Braconidae] - D. Moore; M. S. Ridout (BioControl, 1987)

Graded recruitment in a ponerine ant - Michael D. Breed; Jennifer H. Fewell; Allen J. Moore; Kristina R. Williams (Behavioral Ecology and Sociobiology, 1987)

A glycine betaine transport system in Aphanothece halophytica and other glycine betaine-synthesising cyanobacteria - D. J. Moore; R. H. Reed; W. D. P. Stewart (Archives of Microbiology, 1987)

Associations between metabolites of aromatic compounds in bile and the occurrence of hepatic lesions in English sole (Parophrys vetulus) from Puget Sound, Washington - Margaret M. Krahn; Linda D. Rhodes; Mark S. Myers; Leslie K. Moore; William D. MacLeod; Donald C. Malins (Archives of Environmental Contamination and Toxicology, 1986)

Food sharing by sibling vs nonsibling spiny mice (Acomys cahirinus) - Richard H. Porter; John D. Moore; David M. White (Behavioral Ecology and Sociobiology, 1981)

Prediction of potato yield using temperature and insolation data - T. K. Hartz; F. D. Moore (American Journal of Potato Research, 1978)

Die Aminosäuresequenz des Mureins vonSarcina ventriculi undSarcina maxima - O. Kandler; D. Claus; A. Moore (Archives of Microbiology, 1972)

Sectional notes - H. G. Zuckerman; C. H. Metzger; B. A. Brown; W. B. Ward; C. L. Fitch; John S. Gardner; Frank W. Hussey; Ralph W. Donaldson; H. C. Moore; H. O. Werner; W. H. Martin; K. H. Fernow; et al. (American Journal of Potato Research, 1935)

Notes - E. A. Stokdyk; W. H. Olin; G. S. Kelch; J. T. Quinn; B. A. Brown; Lou D. Sweet; H. C. Moore; Daniel Dean; J. G. Milward (American Journal of Potato Research, 1928)

Some important diseases of the potato in South Carolina - W. D. Moore (American Journal of Potato Research, 1928)

Crop and market news - B. A. Brown; K. P. Bemis; E. A. Stokdyk; G. D. Clark; H. C. Moore; A. G. Tolaas; H. O. Werner; Wm. Martin; E. V. Hardenburg; W. K. McCulock; H. H. Zimmerly; J. G. Milward (American Journal of Potato Research, 1926)

Potato notes - C. Tice; W. C. Edmundson; Ray D. Hews; H. C. Moore; H. O. Werner; W. H. Martin; Daniel Dean; W. A. McCubbin; W. H. Zimmerly (American Journal of Potato Research, 1924)

Potato notes - Lou D. Sweet; J. H. Woolf; A. E. Wilkinson; F. C. Gaylord; E. A. Stodyke; R. D. Hews; H. C. Moore; J. W. Weston; W. V. Longley; J. Norton Woodruff; W. H. Martin; J. C. Crissey; et al. (American Journal of Potato Research, 1924)

Potato notes - J. T. Rosa; C. Tice; A. E. Wilkinson; B. G. Southwick; E. A. Stokdyk; Ray D. Hews; E. L. Newdick; W. Stuart; H. C. Moore; H. O. Werner; J. F. Hockey; C. L. Bailey; et al. (American Journal of Potato Research, 1924)

Potato notes - Lou D. Sweet; W. Stuart; E. V. Hardenburg; H. C. Moore; W. H. Martin (American Journal of Potato Research, 1923)